Official Languages Recognition Program (OLRP) - Accreditation Canada (2022)
Accreditation Canada’s Official Languages Recognition Program (OLRP) supports and awards organizations that are committed to improving access to health and social services in official languages. This brochure answers questions such as: - How does the program work? - How does this program integrate with our current language accessibility efforts? - Who developed this program? - Why is this the right time to participate? - How much does it cost to participate in the program?

Programme de reconnaissance des langues officielles (PRLO) - Agrément Canada (2022)
Le Programme de reconnaissance des langues officielles (PRLO) d'Agrément Canada appuie et certifie les organismes qui sont engagés à améliorer l'accès aux services de santé et services sociaux en langues officielles. Ce feuillet d'information à l'intention des fournisseurs de services répond aux questions suivantes: - Comment le programme fonctionne‐t‐il ? - Comment ce programme s'intègre-t-il à nos efforts actuels d'accessibilité linguistique ? - Qui a élaboré ce programme ? - Pourquoi est-ce le bon moment de participer ? - Quel est le coût pour participer au programme ?

Lost in policy translation: Canadian minority Francophones and health disparities - Alimezelli, Hubert Tote; Leis, Anne; Denis, Wilfrid; Karunanayake, Chandima (Canadian Public Policy, 2015)
We reviewed Canadian federal, provincial, and territorial policies related to the health of official language minorities (OLMs) and found important provincial and territorial differences as well as policies penalizing OLMs, which thus contribute significantly to health disparities and to the low vitality of OLM communities. These findings suggest the need for more aggressive, hands-on, and concerted federal and provincial/territorial government efforts to address social inequities and health disparities. Increased policy coherence between these levels of government will not only increase the health and vitality of these populations but also help close the disparity gap and lead to better health and well-being for all Canadians.

L’implantation du Projet transdisciplinaire en santé communautaire à l’Université de Saint-Boniface - Archambault, Hélène; de Rocquigny, Janelle; Ba, Halimatou; Giasson, Florette; Lapointe, Gisèle (Reflets, 2014)

Besoins criants, gains modestes : l'accès à des soins de santé mentale en français en Ontario, 1968–1986 - Arsenault, Mathieu; Martel, Marcel (Besoins criants, gains modestes : l'accès à des soins de santé mentale en français en Ontario, 2017)
Les gains en matière de soins de santé mentale en français arrivent au compte-goutte entre 1968 et 1986. L'État ontarien agit avec prudence dans ce dossier. Malgré les pressions des individus et de l'Association canadienne-française de l'Ontario, la mise en place de soins de santé mentale en français s'est butée à de nombreux obstacles tels que la pénurie de personnel parlant français, les difficultés à attirer ce personnel et à les inciter à demeurer notamment dans le Nord, les carences du système d'éducation à former des francophones, les hésitations du gouvernement ontarien, mais aussi l'hostilité au fait français.

Compétences linguistiques et culturelles des organisations de santé. Analyse critique de la littérature - Aucoin, Léonard (InfoVeille Santé, 2008)

New Brunswick: Development of a Web-based orientation program and enhancing senior nurses' mentoring skills - Auffrey, Marise; Cormier-Daigle, Monique; Gagnon-Ouellette, Anne (Nursing Leadership, 2012)
This project to help new nurse recruits integrate into the hospital work environment had two components: the development of a new web-based orientation tool in French for new recruits and mentor training for more experienced nurses. The aim of the first component was to redesign delivery of the nursing orientation program by assessing individual needs of new recruits and developing "just in time" information sessions with online access and e-learning modules. The second component aimed to develop a voluntary mentorship training program for senior nurses that offered training on the role and responsibility of mentors. A total of 30 orientation modules were created as resources that could be adapted to the needs of each nursing unit and accessed online. Sixty nurse recruits used the programs. A mentor training program was developed, and 28 nurses were trained as mentors. The mentorship literature and guides, produced in French, will be a valuable resource for francophone nurses across Canada.

État de la situation et étude de modèles de soins de santé primaires offerts aux francophones vivant en situation minoritaire au Canada - Axion (2016)

Facteurs favorisant l’offre de services de santé en français : études de cas en milieu hospitalier anglophone - Bahi, Boniface; Forgues, Éric (Minorités linguistiques et société, 2015)
Par une approche à la fois qualitative et quantitative, la présente étude analyse les modalités de prise en compte de la langue dans l’organisation des services de santé au sein des établissements majoritairement anglophones, de même que les possibilités favorables à l’offre de services de santé en français en milieu minoritaire francophone. L’examen des facteurs favorisant l’offre de services de santé en français en milieu minoritaire francophone porte sur les dimensions organisationnelles (internales) et sur les dimensions environnementales (externales) du milieu hospitalier. Ces possibilités et ces facteurs favorables ont trait notamment à la volonté de l’administration et des professionnels de la santé des établissements hospitaliers, au renforcement et à la mise en valeur du bilinguisme dans la gestion des services, mais aussi à l’émergence aussi bien d’une demande active de services en français que d’une volonté politique, juridique et réglementaire des autorités gouvernementales. Mots-clés : santé, services en français, milieu minoritaire, francophonie, offre active

Comparison of dietary intake between Francophones and Anglophones in Canada: Data from CCHS2.2 - Batal, Malek; Makvandi, Ewa; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Grenier, Jean; Chomienne, Marie-Hélène; Bouchard, Louise (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objective To compare the dietary intake and food choices between Francophone Canadians in a state of linguistic minority (outside of Quebec) and the English-speaking majority. Methods We used the 2004 Canadian Community Health Survey (CCHS) cycle 2.2 (general health and 24-hour dietary recalls) to describe dietary intake of Francophone Canadians (excluding Quebec) and compare them to the English-speaking majority. The linguistic variable was determined by languages spoken at home, first language learned and still understood, language of interview, and language of preference. The mean differences in daily nutrient and food intake were assessed by t and chi-square tests. Results Differences in total energy and daily food intakes by language groups were not observed in the sample; however, significant differences in weekly consumption were found in different age and sex categories: lower fruits and vegetables consumption, and vitamins and macronutrients intakes for older Francophone men and higher intakes of energy and saturated fat from “unhealthy” foods for Francophone men 19–30 years of age. Based on the Acceptable Macronutrients Distribution Range (AMDR), approximately 50% of the sample exceeded their acceptable energy intake from saturated fats, and 80% were below their required intake of linoleic fatty acid. Conclusion We confirmed that belonging to Francophone minorities in Canada affects food choices and nutritional well-being of this population. The most vulnerable groups identified by our study were Francophone men in the youngest (19-30) and older (50 and over) age categories. The extent to which the cultural setting influences the diet and, in turn, the health of the minority population needs further examination.

Ascertaining the Francophone population in Ontario: validating the language variable in health data - Batista, Ricardo; Hsu, Amy T.; Bouchard, Louise; Reaume, Michael; Rhodes, Emily; Sucha, Ewa; Guerin, Eva; Prud'homme, Denis; Manuel, Douglas G.; Tanuseputro, Peter (BMC Medical Research Methodology, 2024)
Abstract Background Language barriers can impact health care and outcomes. Valid and reliable language data is central to studying health inequalities in linguistic minorities. In Canada, language variables are available in administrative health databases; however, the validity of these variables has not been studied. This study assessed concordance between language variables from administrative health databases and language variables from the Canadian Community Health Survey (CCHS) to identify Francophones in Ontario.

Recruiting doctors from and for underserved groups: Does New Brunswick's initiative to recruit doctors for its linguistic minority help rural communities? - Beauchamp, Jacinthe; Bélanger, Mathieu; Schofield, Aurel; Bordage, Rachel; Donovan, Denise; Landry, Michel (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objectives Within health care, there are underserved groups. New Brunswick’s French-speaking minority, which also mostly lives in rural communities, is one such group. A physician shortage potentially prevents this population from accessing health promotion and clinical prevention services. This study analyzes whether New Brunswick Francophone doctors with rural backgrounds are more likely than doctors from urban regions to set up practice in rural communities of the province. Methods A questionnaire was sent to 390 New Brunswick Francophone physicians admitted in medicine between 1973 and 2000. It collected information on geographic origin and history of medical practice. Multivariate logistic regressions were used to identify whether a rural background is associated with the likelihood of ever and currently practicing in rural communities. We used the General Practice Rurality Index-simplified to quantify the rurality level of communities. Results In total, 264 (67%) physicians participated. A rural background was positively associated with the establishment of a first medical practice in a rural community. This relationship was only significant among family physicians. There was no statistically significant relationship between rurality of community of origin and rurality of current community of practice among either family or specialty physicians. Conclusion Although Francophone doctors with a rural background were more likely than their urban counterparts to set up their first practice in a rural community, this effect was not sustained. This raises questions as to why they leave rural communities and highlights the importance of measures to retain doctors as a way to promote public health for underserved rural groups.

Formation linguistique, adaptation culturelle et services de santé en français - Beaulieu, Marielle (Consortium national de formation en santé et Société Santé en français, 2010)

Norme pédagogique et infirmières bilingues en milieu francophone minoritaire - Beaulieu, Suzie (The Canadian Modern Language Review/ La revue canadienne des langues vivantes, 2011)
Les infirmières œuvrant dans leur langue seconde (L2) font face à divers problèmes langagiers en milieu clinique dont la difficulté à comprendre l'accent des patients et les expressions appartenant au registre familier qu'ils emploient. Ces résultats sont peu surprenants puisque l'enseignement des L2 est souvent implicitement orienté vers l'acquisition de la variété standard de la langue cible. Pour intégrer une plus grande variété linguistique dans l'enseignement des L2, le concept de norme pédagogique, qui en premier lieu vise à refléter le comportement linguistique observable des locuteurs de la langue cible, peut être utilisé. Cette étude propose de déterminer la norme pédagogique à adopter dans la formation langagière en français L2 d’étudiants en sciences infirmières en milieu minoritaire francophone.

Distance, access and equity: A cross-sectional geospatial analysis of disparities in acess to primary care for French-only speakers in Ottawa, Ontario - Belanger, Christopher; Carr, Kady; Peixoto, Cayden; Bjerre, Lise M. (CMAJ Open, 2023)
Background: Although language concordance between patients and primary care physicians results in better quality of care and health outcomes, little research has explored inequities in travel burden to access primary care people of linguistic minority groups in Canada. We sought to investigate the travel burden of language-concordant primary care among people who speak French but not English (French-only speakers) and the general public in Ottawa, Ontario, and any inequities in access across language groups and neighbourhood ruralities. Methods: Using a novel computational method, we estimated travel burden to language-concordant primary care for the general population and French-only speakers in Ottawa. We used language and population data from Statistics Canada’s 2016 Census, neighbourhood demographics from the Ottawa Neighbourhood Study, and collected the main practice location and language of primary care physicians from the College of Physicians and Surgeons of Ontario. We measured travel burden using Valhalla, an open-source road-network analysis platform. Results: We included data from 869 primary care physicians and 916 855 patients. Overall, French-only speakers faced greater travel burdens than the general population to access language-concordant primary care. Median differences in travel burden were statistically significant but small (median difference in drive time 0.61 min, p < 0.001, interquartile range 0.26–1.17 min), but inequities in travel burden between groups were larger among people living in rural neighbourhoods.

Patient and Provider Satisfaction With a Geomapping Tool for Finding Community Family Physicians in Ontario, Canada: Cross-Sectional Online Survey Study. - Belanger, Christopher; Peixoto, Cayden; Francoeur, Sara; Bjerre, Lise M. (JMIR formative research, 2024)
Background: Language-concordant health care, or health care in a patient’s language of choice, is an important element of health accessibility that improves patient safety and comfort and facilitates an increased quality of care. However, prior research has found that linguistic minorities often face higher travel burdens to access language-concordant care compared to the general population. Objective: This study intended to assess patient experiences and satisfaction with an online interactive physician map that allows patients to find family physicians who speak their preferred language in and around Ottawa, Ontario, Canada, as a means of identifying areas of improvement. Methods: This study used an online survey with questions related to user satisfaction. Responses to Likert-scale questions were compiled as summary statistics and short-answer responses underwent thematic analysis. The study setting was Ottawa and Renfrew County, Ontario, and the surrounding region, including the province of Quebec. Results: A total of 93 respondents completed the survey and self-identified as living in Ontario or Quebec. Overall, 57 (61%) respondents were “very satisfied” or “somewhat satisfied” with the map, 16 (17%) were “neither satisfied nor dissatisfied,” and 20 (22%) were “very dissatisfied” or “somewhat dissatisfied.” We found no significant differences in satisfaction by preferred language, age group, physician attachment, or intended beneficiary. A total of 56 respondents provided short-answer responses to an open-ended question about map improvements. The most common specific suggestion was to show which physicians are accepting new patients (n=20). Other suggestions included data refreshes (n=6), user interface adjustments (n=23), and additional languages (n=2). Some participants also provided positive feedback (n=5) or expressed concern with their inability to find a family physician (n=5). Several comments included multiple suggestions. Conclusions: While most patients were satisfied with the online map, a significant minority expressed dissatisfaction that the map did not show which family physicians were accepting new patients. This suggests that there may be public interest in an accessible database of which family physicians in Ontario are currently accepting new patients.

Perceived Health status of Francophones and Anglophones in an official bilingual Canadian province - Bélanger, Mathieu; Bouchard, Louise; Gaboury, Isabelle; Sonier, Brigitte; Gagnon-Arpin, Isabelle; Schofield, Aurel; Bourque, Paul-Emile (Canadian Journal of Public health, 2011)
Objective: It has been reported that being part of a minority group may be negatively associated with self-perceived health. The objective of this analysis was to determine whether there are differences in perceived health between the Francophone minority and Anglophone majority in New Brunswick, the only officially bilingual province in Canada. Methods: Data from the first four primary cycles of the Canadian Community Health Survey (2001 to 2007) were obtained for 17,729 New Brunswick residents. Odds of reporting good health among Francophones and Anglophones were compared using multivariate logistic regressions accounting for age, health-related behaviours, socio-demographic variables, and medical conditions. Results: In the final models, Francophone men and women were less likely than Anglophones to report their health as being good, although these differences were not statistically significant (Odds ratio, 95% confidence interval: 0.88, 0.61–1.26; 0.71, 0.49-1.04, in men and women, respectively). Conclusion: This study suggests that being part of the linguistic minority in New Brunswick is not associated with statistically significant differences in self-perceived health.

L’accès aux soins de santé pour les communautés minoritaires de langue officielle : fondements juridiques, initiatives actuelles et perspectives d’avenir - Bélanger, Mauril; Comité permanent des langues officielles (Gouvernement du Canada, Chambre des communes, 2003)

Enquête sur l’offre active pour les services auxiliaires de santé du Nord-Est de l’Ontario - Bélanger, Roxanne; Mayer-Crittenden, Chantal; Mainguy, Josée; Coutu, Anie (Reflets, 2018)
Au Canada, il existe peu de données décrivant les services auxiliaires de santé en français disponibles dans les communautés francophones en situation minoritaire. L’objectif de cette étude était d’examiner l’accès aux services d’orthophonie, de physiothérapie et d’ergothérapie en français dans le Nord-Est de l’Ontario. Un outil mesurant la disponibilité et l’offre active des services a été créé et validé. Ce dernier a été distribué aux personnes fournissant les services et aux personnes les utilisant afin de déterminer leurs perceptions concernant l’offre de ces services en français, ainsi que l’accessibilité aux services auxiliaires de santé en français. Les résultats ont montré un manque de services en français dans cette région. Mots-clés : situation minoritaire francophone, services auxiliaires de santé, offre active, Nord-Est de l’Ontario, questionnaires

L’intégration des diplômés internationaux en santé francophones dans les communautés francophones en situation minoritaire. Rapport final de recherche - Belkhodja, Chedly; Forgues, Éric; Gaboury, Isabelle; Guignard Noël, Josée; Bahi, Boniface; Nkolo, Christine; Tawil, Nada (Consortium national de formation en santé et Institut canadien de recherche sur les minorités linguistiques, 2009)

Pratique # 24 : Communauté accueillante 2.0 et Formation Les Communautés de Pratique : une démarche collaborative pour accroître l’offre de services en français (Ontario) - Benoît, Josée; Dagnogo, Djenaba Sarah; Renaud, Alexandre (2023)

Pratique # 18 : Le plan de contingence du Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (2021)

Pratique # 19 : Les outils de rappel du Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (2021)

La formation à l’offre de services en français dans les programmes de santé et de service social en milieu minoritaire francophone au Canada - Benoît, Josée; Dubouloz, Claire-Jehanne; Guitard, Paulette; Brosseau, Lucie; Kubina, Lucy-Ann; Savard, Jacinthe; Drolet, Marie (Minorités linguistiques et société, 2015)
Les professionnels des services sociaux et de santé disent être peu outillés pour travailler auprès des communautés francophones en situation minoritaire (CFSM). Une meilleure connaissance des pratiques d’enseignement professionnel utilisées dans ces domaines, et axées sur des approches pédagogiques congruentes et des contenus de formation significatifs sur les besoins particuliers des CFSM, aiderait à bonifier la formation des futurs professionnels. Une recension des écrits sur les approches pédagogiques utilisées dans divers contextes linguistiques minoritaires a inspiré l’élaboration d’un questionnaire adressé aux formateurs des programmes de langue française en santé et en service social au Canada. Les résultats indiquent que les formateurs eux-mêmes se sentent peu outillés pour bien former leurs étudiants à travailler en contexte francophone minoritaire. Mots-clés : approches pédagogiques, formation professionnelle, santé, service social, francophonie minoritaire

Les inégalités sociales de santé chez les communautés francophones en situation minoritaire (CFSM) au Canada [numéro thématique] - Benoit, Monique; Bouchard, Louise; Garceau, Marie-Luce (Reflets, 2012)

Poids, santé générale et santé mentale : la situation de divers sous-groupes d'immigrants au Canada - Bergeron, Pascale; Auger, Nathalie; Hamel, Denis (Revue canadienne de santé publique, 2009)
Contexte Au Canada, l’immigrant récent est souvent en meilleure santé que le non-immigrant. L’état de santé des sous-groupes d’immigrants (ethniques, culturels, linguistiques) est moins bien connu. Méthode En utilisant des données de l’Enquête sur la santé dans les collectivités canadiennes 2005 (Cycle 3.1), les associations entre trois caractéristiques des immigrants (1-temps écoulé depuis l’immigration, 2-être une minorité visible, 3-parler une langue officielle) et trois indicateurs de santé (1-santé générale perçue, 2-santé mentale perçue, 3-indice de masse corporelle (IMC)) ont été modélisées à l’aide de régressions logistiques multiples pour les immigrants des régions métropolitaines de recensement de Montréal, Toronto et Vancouver. Elles ont été ajustées pour des facteurs sociodémographiques. Résultats Les immigrants récemment arrivés qui appartiennent à une minorité visible sont moins susceptibles d’avoir une mauvaise santé perçue, tant générale (RC 0,72; IC95 % 0,54–0,97) que mentale (RC 0,64; IC95 % 0,43–0,96) et un IMC≥25 (RC 0,51; IC95 % 0,43–0,61) que les non-immigrants. Ceux qui n’appartiennent pas à une minorité visible ne présentent pas ces associations. Les immigrants qui ne parlent pas une langue officielle sont plus susceptibles d’avoir une mauvaise santé générale perçue (RC 1,49; IC95 % 1,06–2,10) que les non-immigrants. À Toronto et Vancouver, les immigrants tendent à être associés à un IMC moindre que les non-immigrants alors que ce n’est pas le cas à Montréal. Conclusion Cette étude témoigne de la présence du phénomène de l’immigrant en bonne santé au Canada mais démontre qu’une grande variabilité existe entre les sous-groupes d’immigrants. Ces constats sont importants pour une planification adéquate des services aux immigrants.

Citoyens de deuxième classe ? Perceptions de la santé et du système de soins chez les francophones du nord-est de l’Ontario - Bernier, Christiane (Francophonies d'Amérique, 2009)
Cette enquête a pour objectif d’analyser les représentations que les francophones vivant en situation minoritaire ont de leur santé et de celle de leur communauté, de même que leurs perceptions des systèmes de soins auxquels ils ont accès, particulièrement lorsqu’ils vivent dans des régions rurales ou éloignées. De type qualitatif, l’enquête a été réalisée dans le nord-est de l’Ontario auprès de 32 francophones provenant de dix villes différentes. Les résultats montrent que le mépris de la langue minoritaire, le manque de services et de considération pour les francophones ainsi que le faible intérêt accordé par le gouvernement aux usagers des régions éloignées sont les pivots autour desquels se construisent l’insécurité et les désillusions par rapport au système de santé de la province.

Professionnels de la santé et minorités de langue officielle au Canada, 2001 et 2006 (n°91-550-X) - Blaser, Christine (Statistique Canada, 2009)

Rapport spécial. L'offre active de services en français : la clé de voûte à l'atteinte des objectifs de la Loi sur les services en français de l'Ontario - Boileau, François (Commissariat aux services en français de l'Ontario, 2016)

Special report on French language health services planning in Ontario, 2009 - Boileau, François (Office of the French Language Services Commissioner, 2009)

Inventaires des services de santé en français dans l’Ouest canadien : entre improvisation et gouvernance : 2000‐2010 - Boily, Frédéric; Gagné, Learry (Revue Gouvernance, 2013)
La difficulté pour les communautés francophones en situation minoritaire au Canada d’obtenir des services de santé dans leur langue est bien connue. Le problème est encore plus criant dans l’Ouest canadien, défavorisé par une faiblesse démographique et une grande dispersion de la population par rapport à l’Est (surtout l’Ontario et le Nouveau-Brunswick). Dans ce contexte, la mobilisation des francophones pour la défense de leurs intérêts est essentielle. Ce projet porte sur les relations entre les gouvernements provinciaux de l’Ouest, le gouvernement fédéral et les groupes francophones minoritaires en matière de politique de santé. Nous proposons de nous concentrer sur les provinces de la Colombie-Britannique, de l’Alberta et de la Saskatchewan pour la période récente allant de 2000 à 2010. L’analyse porte principalement sur les facteurs en politique publique qui ont permis à ces groupes de revendiquer un certain nombre de services de santé. Nous établissons une relation entre la participation active du fédéral durant cette période, la participation plutôt passive des provinces, et la préférence pour les projets de santé publique où le fédéral a pu jouer un rôle sans empiéter sur les pouvoirs provinciaux.

Santé et mieux-être des élèves francophones au Nouveau-Brunswick (Canada) - Boivin, Nathalie; Foulem, Ghislaine; Desjardins, Isabelle Perron (La Revue de Santé Scolaire et Universitaire, 2025)

Littératie en matière de santé : des moyens novateurs de stimuler la prise en charge par la population francophone du Nord-Est du Nouveau-Brunswick - Boivin, Nathalie; Réseau Communauté en santé de Bathurst (Francophonies d'Amérique, 2009)
L’Organisation mondiale de la santé (OMS) définit la promotion de la santé comme le processus qui confère aux populations les moyens d’assurer une plus grande maîtrise de leur propre santé et de l’améliorer. Or, comment parler de prise en charge de sa santé alors qu’une partie importante de la population francophone du nord-est du Nouveau-Brunswick ne possède pas le niveau minimal d’alphabétisation requis pour fonctionner dans notre société actuelle ? Une démarche habilitante auprès de cette population a été menée. Les résultats préliminaires sont exposés, dévoilant les avantages et les obstacles d’une campagne médiatique.

La cartographie conceptuelle des représentations de l'avenir des services de santé en français en situation linguistique minoritaire - Bouchard, Louise (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectif Dans le contexte de l’incomplétude institutionnelle qui affecte les communautés de langue officielle minoritaire, nous voulons rendre compte des représentations des francophones en situation linguistique minoritaire, eu égard à l’avenir des services de santé en français. Méthode L’étude repose sur une méthodologie participative: la cartographie conceptuelle permettant de recenser l’univers conceptuel d’une problématique donnée. À partir d’un énoncé maître, tel que « Quand je pense à l’avenir des services de santé en français, je pense à… », les participants sont conviés à émettre autant d’énoncés qui leur viennent à l’esprit. Ces énoncés sont par la suite catégorisés individuellement et traités collectivement au moyen d’analyses multivariées. Résultats Les thématiques principales qui ressortent de l’exercice de cartographie indiquent les enjeux et défis que se représentent les participants, à savoir: les réalités géographiques, les besoins spécifiques, les droits linguistiques, l’éducation et la formation, les ressources humaines, le bilinguisme et la traduction, le vécu minoritaire, l’offre active, le rôle des instances gouvernementales, la mobilisation communautaire, la collaboration et le réseautage. Conclusion La démarche participative que permet la cartographie conceptuelle s’avère intéressante à plus d’un égard. Souple et flexible, elle donne un espace de réflexion à la fois individuel et collectif; elle permet de cerner et de structurer les dimensions cruciales d’une problématique; les matériaux issus de la démarche sont utiles autant aux chercheurs qu’aux participants pour orienter l’action et l’atteinte d’objectifs. Les acteurs peuvent ainsi bénéficier d’une dynamique collective pour penser les bases du développement et de l’organisation des services de santé en français.

Le mouvement de santé en français en contexte linguistique minoritaire : les représentations des acteurs sur l'avenir des services - Bouchard, Louise (Revue canadienne de sociologie, 2011)
Le plan d'action pour les langues officielles lancé en 2003 projette de revitaliser la dualité linguistique du pays. Parmi les domaines prioritaires, la santé se voit privilégier dans le but d'assurer la formation des professionnels de la santé pour desservir les communautés de langue officielle minoritaire et de réseauter les principaux acteurs préoccupés par l'organisation des services dans la langue minoritaire. L'objectif de cet article est de rendre compte des représentations des francophones en situation linguistique minoritaire eu égard à l'avenir des services de santé en français. L'étude repose sur une méthodologie participative: la cartographie conceptuelle permettant de recenser l'univers conceptuel d'une problématique donnée.

La santé des francophones de l'Ontario. Un portrait régional tiré des Enquêtes sur la santé dans les collectivités canadiennes (ESCC) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)

The health of Francophones in Ontario. A region-by-region portrait developed from the Canadian community health survey (CCHS) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makvandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)

Santé mentale et maladies mentales des jeunes francophones de 15 à 24 ans : données de l’Enquête sur la santé dans les collectivités canadiennes – Santé mentale 2012 - Bouchard, Louise; Batista, Ricardo; Colman, Ian (Minorités linguistiques et société, 2018)
a plupart des maladies mentales apparaissent à l’adolescence ou au début de la vie adulte ; elles influent sur les réussites scolaires, les possibilités et les succès professionnels ainsi que les relations personnelles et peuvent avoir des répercussions tout au long de la vie. Bien que la majorité des jeunes traversent leur adolescence sans problèmes, une proportion suffisamment importante montre toutefois un profil préoccupant dont il faut prendre acte. L’objectif de cet article est de brosser, à partir des données de l’Enquête sur la santé dans les collectivités canadiennes – Santé mentale (ESCC-SM 2012), un portrait de la santé mentale des jeunes francophones de 15 à 24 ans vivant en situation linguistique minoritaire et de le comparer à celui des jeunes francophones vivant au Québec. Mots-clés : identité ethnolinguistique, continuité culturelle, minorité francophone, jeunes adultes, santé mentale

Santé de la population francophone et anglophone âgée de 65 ans et plus de l’Ontario [affiche] - Bouchard, Louise; Batista, Ricardo; Duong, Patrick; Sauvé-Schenk, Katrine; Lizotte, Mathieu (Colloque 103 – L’offre des services de santé dans les langues minoritaires, 92e Congrès de l’Acfas, 2025)

Évolution de principaux indicateurs de la santé de la population francophone et anglophone de l’Ontario : 2001-2014. Résultats de l’enquête sur la santé dans les collectivités canadiennes - Bouchard, Louise; Batista, Ricardo; Reaume, Michael (Université d’Ottawa et Institut du savoir Montfort, 2021)

L'offre active des services de santé en français en Ontario : une mesure d'équité - Bouchard, Louise; Beaulieu, Marielle; Desmeules, Martin (Reflets, 2012)
Cet article fait état d’une recherche sur l’offre active de services en français en Ontario. L’étude avait pour objectifs de recenser les définitions de l’offre active de services en français; d’identifier les pratiques d’offre active (facilitateurs ou obstacles); d’identifier les indicateurs de mesure de l’offre active et de proposer des recommandations permettant d’améliorer l’offre active de services en français. À cette fin, une revue documentaire, une enquête auprès de professionnels oeuvrant dans le domaine de la planification des services de santé en français ainsi qu’un atelier de cartographie conceptuelle ont été entrepris. Mots-clés : minorité linguistique, services de santé, offre active, Loi 8

Santé mentale chez les francophones en situation linguistique minoritaire - Bouchard, Louise; Colman, Ian; Batista, Ricardo (Reflets, 2018)
Bien que la plupart des études considèrent l’importance des déterminants sociaux sur l’existence des troubles mentaux, aucune ne désagrège les données en fonction de l’appartenance à une communauté de langue officielle en situation minoritaire, un fait pourtant reconnu pouvant avoir un impact sur la santé. L’incidence des langues et de la communication sur l’accès, la qualité et la sécurité des soins acquiert une portée plus grande dans le contexte canadien où coexistent deux langues officielles. Nous partons de cette prémisse pour dresser ici le portrait de la santé mentale de la population francophone vivant en situation linguistique minoritaire à partir des données de l’Enquête de santé dans les collectivités canadiennes — Santé mentale (ESCC, 2012)[1]. Mots-clés : santé et maladies mentales, francophones en situation minoritaire, Canada, Enquête de santé dans les collectivités canadiennes — Santé mentale (ESCC)

La santé mentale des francophones en situation minoritaire au Canada : un portrait tiré de l’Enquête sur la santé dans les collectivités canadiennes-Santé mentale 2012 - Bouchard, Louise; Colman, Ian; Dubois, Alejandra; Sucha, Ewa (Université d’Ottawa et Institut du Savoir Montfort, 2019)

The mental health of Francophone minorities: An overview from the Canadian community health survey-Mental health 2012 - Bouchard, Louise; Colman, Ian; Dubois, Alejandra; Sucha, Ewa (University of Ottawa & Institut du Savoir Montfort, 2019)

Les minorités linguistiques du Canada et la santé - Bouchard, Louise; Desmeules, Martin (Politiques de santé, 2013)
Résumé Les minorités de langue officielle (les francophones hors-Québec et les anglophones du Québec) représentent près de 6,4 % de la population canadienne. Bien que le français et l’anglais aient un statut d’égalité juridique selon la Constitution canadienne, il y a lieu de s’interroger sur leur égalité dans le domaine de la santé : les communautés francophones et anglophones du Canada, selon leur statut de minorité ou de majorité, présentent-elles le même profil santé ? Ont-elles accès aux mêmes services de santé et dans les mêmes conditions ? L’objectif de cet article cet article est de rendre compte des enjeux de santé reliés au fait d’appartenir à une minorité linguistique. Nos recherches permettent de mettre en évidence des disparités sociales et de santé qui peuvent être attribuées au fait minoritaire. Dans le contexte canadien des deux langues officielles, une politique de santé équitable devra dorénavant pren dre en considération la situation linguistique minoritaire comme déterminant de la santé. Abstract Official language minorities (Francophones outside of Quebec and Anglophones in Quebec) make up about 6.4% of the Canadian population. Even though the Canadian constitution gives legal equality status to French and English, there is still room to ask if this equality is maintained in the health sector. In other words, do Francophone and Anglophone communities of Canada have the same health profiles regardless of their minority or majority status? Do they have access to the same health services and in the same conditions? The objective of this paper is to identify the health issues associated with belonging to a linguistic minority. Our research allows us to highlight the social and health disparities that can be attributed to belonging to a minority. In the Canadian context, which has two official languages, an equitable health policy will have to take into consideration language as a determinant of health.

Minorités de langue officielle du Canada : égales devant la santé ? - Bouchard, Louise; Desmeules, Martin (Presses de l’Université du Québec, 2011)

Les représentations de l'avenir des services de santé en français en francophonie minoritaire. Rapport national de cartographie conceptuelle - Bouchard, Louise; Desmeules, Martin; Gagnon-Arpin, Isabelle (Réseau de recherche interdisciplinaire sur la santé des francophones en contexte minoritaire au Canada et Institut de recherche sur la santé des populations, 2010)

La santé mentale des francophones et des anglophones vivant en situation minoritaire au Canada [infographie] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

Mental health status of Francophones and Anglophones living in minority situations in Canada [infographic] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

Profil santé mentale des communautés francophones en situation minoritaire au Canada. Rapport abrégé - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa; Colman, Ian (Université d'Ottawa et Institut du Savoir Montfort, 2019)

La santé en francophonie canadienne : vivre en situation minoritaire influence-t-il la santé ? - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène (Bulletin de l’association des médecins de langue française, 2009)
La littérature suggère l'hypothèse d'une santé différentielle des francophones en situation minoritaire au Canada. L'effet de minorité sur la santé perçue a été mesuré à l'aide des Enquêtes sur la santé dans les collectivités canadiennes (ESCC) de 2001 et 2003. Une analyse de régression logistique multivariée séquentielle montre que les francophones minoritaires – hommes et femmes – sont plus enclins à déclarer une moins bonne santé que les anglophones majoritaires. Contrairement aux femmes, cette disparité chez les hommes demeure significative même lorsque nous ajustons pour certains grands déterminants de la santé. L'étude illustre que l'action des déterminants de santé peut être ainsi modulée par le rapport minoritaire/majoritaire. Les inégalités ainsi révélées appellent à une réflexion sur les politiques d'accès linguistique aux soins de santé.

Health profile of French-speaking minority communities in Canada [infographic] - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gagnon-Arpin, Isabelle (2009)

Profil santé des communautés francophones minoritaires au Canada [infographie] - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gagnon-Arpin, Isabelle (2009)
Contexte : Les communautés francophones vivant en situation minoritaire évaluées à 1 million de personnes (4,4% de la population canadienne) sont dispersées un peu partout au pays. Les plus fortes concentrations sont en Ontario (509 265) et au Nouveau Brunswick (239 400), alors qu'ailleurs, on peut compter de 63 000 francophones (Alberta) à moins de 500 francophones (Nunavut). Ces communautés présentent un profil diversifié : elles sont en général moins jeunes, moins scolarisées, ont de plus faibles revenus. Elles sont davantage concentrés dans des régions où l'économie est plus instable rendant ainsi plus difficile le développement et l'accès aux ressources sociales. L'objectif de cette affiche est de présenter une sélection d'indicateurs décrivant certains aspects des déterminants de la santé de la population francophone en situation linguistique minoritaire. Méthode : Les indicateurs de santé sont extraits d'une analyse secondaire de l'ESCC combinant les cycles 2001, 2003 et 2005. L'analyse se fonde sur un échantillon d'adultes de 25 ans et plus de 244 382 : 12 583 francophones ; 256 966 anglophones. Le profil montre les situations et les déterminants les plus défavorables comparant la communauté minoritaire à la majorité anglophone dans l'ensemble du Canada excluant le Québec. Résultats : Sur l'ensemble des indicateurs sélectionnés (variables sociodémographiques, santé perçue, présence de maladie, difficulté à accomplir une tâche, services de santé, styles de vie, le sentiment d'appartenance), les communautés francophones présentent un profil de santé plus défavorable que la majorité anglophone et ce de façon plus marquée dans certaines zones géographiques. Conclusion : Les résultats permettent de soutenir que le rapport minoritaire/majoritaire semble traduire une inégalité sociale et d'accès aux ressources qui, traversée par les autres déterminants sociaux de la santé (statut socioéconomique, éducation et littératie, immigration) contribue de facto aux disparités de santé. Ils montrent l'importance d'approfondir et de mieux comprendre l'ensemble des déterminants de la santé ainsi que les interactions entre les contextes, les milieux de vie locaux, l'impact des politiques et la santé.

La santé en situation linguistique minoritaire - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gilbert, A.; Dubois, L. (Politiques de Santé, 2009)

Rapport d'enquête d'évaluation des besoins et de services de santé des francophones du Sud-Est - Bouchard, Louise; Gagnon-Arpin, Isabelle; Makvandi, E.wa (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, 2012)

Capital social et minorités francophones au Canada - Bouchard, Louise; Gilbert, Anne (Francophonies d’Amérique, 2005)

Capital social, santé et minorités francophones - Bouchard, Louise; Gilbert, Anne; Landry, Rodrigue; Deveau, Kenneth (Revue canadienne de santé publique / Canadian Journal of Public Health, 2006)

Social capital, health and Francophone minorities - Bouchard, Louise; Gilbert, Anne; Landry, Rodrigue; Deveau, Kenneth (Canadian Journal of Public Health / Revue canadienne de santé publique, 2006)
The goal of this article is to outline the analytical perspectives of the concept of social capital regarding health and health management. Social capital, as defined in terms of social networks and resources, has a positive impact on a number of areas, notably the health, well-being, and social and economic development of communities. It is also a useful tool for implementing social policy, especially for marginal populations, the elderly, social assistance payments, etc. An action strategy based on the support and development of networks is the key to achieving the social development, health, and well-being of populations. The social ties promoted by these networks provide people with social, cognitive, and emotional support. This has a direct impact on their self-esteem and sense of personal achievement. They also facilitate access to social resources, including social advancement opportunities. In this paper, we examine the vitality, determinants of health, and health management of Canada’s minority Francophone communities.

La santé en français - Bouchard, Louise; Leis, Anne (L’espace francophone en milieu minoritaire au Canada : nouveaux enjeux, nouvelles mobilisations, 2008)

Les données linguistiques pour la recherche et la planification en santé : possibilité et limites pour l'étude des francophones en situation minoritaire - Bouchard, Louise; Lizotte, Mathieu (Minorités linguistiques et société, 2024)
Malgré de remarquables avancées de recherche sur la problématique de la santé en contexte francophone minoritaire, la disponibilité de variables linguistiques complètes et cohérentes dans les bases de données nationales de santé demeure lacunaire et fragmentée, constituant un défi considérable pour l’étude de la santé des membres des communautés francophones en situation minoritaire (CFSM) et la planification de services adaptés à cette population dispersée. Cet article offre un bilan exhaustif des possibilités et des limites des données disponibles permettant l’étude de la santé des CFSM. Ce faisant, il met en lumière une série de problèmes méthodologiques, dont le manque de données pertinentes, l’absence de variables standardisées et les faibles effectifs pour l’analyse régionale, entre autres. Ces lacunes entravent considérablement la capacité des chercheuses et chercheurs à étudier les conditions et les besoins spécifiques des CFSM en ce qui concerne la santé et la planification de la santé. Mots-clés : données linguistiques, problèmes méthodologiques, francophone, minorité, quantification

Public policy and citizen-based practices that support social and health services for official and co-official language minority communities. An international perspective: What has really been achieved and what are the gaps | Politiques publiques et pratiques citoyennes soutenant les services sociaux et de santé pour les communautés minoritaires de langue officielle et coofficielles. Une perspective internationale : ce qui a été accompli et ce qui reste à faire - Bouchard, Louise; Nyqvist, Fredrica; Mari Mayans, Isidor; van Kemenade, Solange; Maisonneuve, Alexander. R. (Linguistic Minorities and Society / Minorités linguistiques et société, 2021)

Health profile of French-speaking minority communities in Canada [infographic] - Bouchard, Louise; Sampasa-Kanyinga, Hugues; Mukaneza, Anne (2018)

Profil santé des communautés francophones en situation minoritaire au Canada [infographie] - Bouchard, Louise; Sampasa-Kanyinga, Hugues; Mukaneza, Anne (2018)

La santé en contexte francophone minoritaire au Canada : 20 ans de recherche: Introduction - Bouchard, Louise; Savard, Jacinthe; Dumond, Morgan (Minorités linguistiques et société, 2024)

Francophone men and women in Ontario: A health portrait - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario & University of Ottawa, 2014)

Les hommes et les femmes francophones en Ontario : un portrait de leur santé - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario et Université d’Ottawa, 2014)

The health of Francophone men and women in Ontario. A region-by-region portrait based on the Canadian community health survey (CCHS) - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario & University of Ottawa, 2014)

Conclusion : des connaissances nouvelles pour des services en français de qualité et sécuritaires à l’intention des communautés francophones en situation minoritaire - Bouchard, Pier; Savard, Jacinthe; Savard, Sébastien; Vézina, Sylvain; Drolet, Marie (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Le cadre théorique en filigrane de cet ouvrage, soit le modèle de l’analyse stratégique, est repris la conclusion et contribuer à améliorer la compréhension du rôle de l’acteur et du système dans l’actualisation des principes de l’offre active de services sociaux et de santé dans la langue au choix de l’usager. Le chapitre aborde les enjeux de l'accès à des services sociaux et de santé en français, le jeu des acteurs au sein des communautés francophones en situation minoritaire, le système et les leviers d'action ainsi que les stratégies en faveur de l'offre active. Plus spécificement, on articule les principales propositions contenues dans l’ouvrage autour des six stratégies suivantes : levier juridique et politique, formation et engagement des futurs professionnels, culture organisationnelle axée sur l’offre active, leadership des acteurs sociaux et de la communauté, mesures d’attraction et de rétention des intervenants et enfin mobilisation et collaboration des acteurs. En terminant, les stratégies sont énoncées en 6 recommandatons en faveur de l'offre active de services sociaux et de santé en français en contexte minoritaire.

Conclusion: New insights into safe, quality services in official language minority communities - Bouchard, Pier; Savard, Jacinthe; Savard, Sébastien; Vézina, Sylvain; Drolet, Marie (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Document de réflexion pour le DVD : « Quand la santé c’est aussi la langue ! » - Bouchard, Pier; Savoie, Mylène (Groupe de recherche sur l’innovation et l’organisation des services de santé, 2011)

Engaging future professionals in the promotion of active offer for a culturally and linguistically appropriate system - Bouchard, Pier; Vézina, Sylvain; Cormier, Manon; Laforge, Marie-Josée (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

L’engagement des futurs professionnels en faveur de l’offre active et d’un système adapté linguistiquement et culturellement - Bouchard, Pier; Vézina, Sylvain; Cormier, Manon; Laforge, Marie-Josée (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Dans ce chapitre, les auteurs proposent de revisiter, à la lumière des propositions de l’analyse stratégique, la démarche empruntée par le Consortium national de formation en santé (CNFS) en matière d’offre active de services sociaux et de santé en français. Le CNFS étant un consortium d’établissements de formation postsecondaire francophones offrant des programmes dans le domaine de la santé et des services sociaux, il sera question de suivre son parcours vers la conception et la transmission d’outils pour préparer les professionnels francophones à relever les défis relatifs à l’accès aux ser vices en français en contexte minoritaire. Nous y verrons comment, en réponse à une recommandation contenue dans un rapport d’évaluation datant de 2008, le CNFS a entrepris une démarche pour faire en sorte que les diplômés issus des programmes qu’il soutient deviennent des ambassadeurs capables d’intervenir pour un meilleur accès à des services de qualité et sécuritaires à l’intention des communautés francophones en situation minoritaire. Le lecteur y découvrira une stratégie axée sur l’acteur selon laquelle un professionnel sensibilisé et outillé serait en mesure d’influencer le système pour améliorer l'offre active de services en français. Il y fera également le constat d’une série de défis, d’enjeux et de pistes d’action qui se sont profilés tout au long de la démarche. Le processus étant dynamique, nous conclurons en présentant quelques mesures en cours d’élaboration ou d’implantation. Mots-clés : langue et santé, enjeux et défis de l’offre active, qualité et sécurité des soins, acteur, stratégie, engagement et formation.

Rapport du dialogue sur l’engagement des étudiants et des futurs professionnels pour de meilleurs services de santé en français dans un contexte minoritaire - Bouchard, Pier; Vézina, Sylvain; Savoie, Mylène (Consortium national de formation en santé, 2010)

Programme de formation clinique dans les communautés francophones en situation minoritaire du Consortium national de formation en santé - Volet La Cité - Boulet, Mélanie (Reflets, 2018)

Acculturation, vitality, and bilingual healthcare - Bourhis, Richard Y.; Montreuil, Annie (The Oxford handbook of acculturation and health, 2017)

Barrières linguistiques dans l'accès aux soins de santé - Bowen, Sarah (Santé Canada, 2001)

Impact des barrières linguistiques sur la sécurité des patients et la qualité des soins. Rapport final - Bowen, Sarah (Société Santé en français, 2015)

Language barriers in access to health care - Bowen, Sarah (Health Canada, 2001)

Language barriers within the Winnipeg regional health authority. Evidence and implications - Bowen, Sarah (Winnipeg Regional Health Authority, 2004)

The impact of language barriers on patient safety and quality of care. Final report - Bowen, Sarah (Société Santé en français, 2015)

Repérage et analyse de l'information sur la santé dans Internet : le cas des CLOSM dans la province de l'Alberta - Bowker, Lynne (Francophonies d'Amérique, 2009)
La présente étude examine, dans le contexte des langues officielles, quelques-uns des besoins insatisfaits des communautés de langue officielle en situation minoritaire (CLOSM) au Canada sur le plan de la santé. Nous présentons les résultats d’une analyse de l’information sur la santé offerte dans Internet aux francophones de l’Alberta. Nous avons procédé à une évaluation comparative de l’information sur la santé destinée à la population albertaine en français et en anglais dans Internet. En présentant les résultats, cette analyse compare le nombre de textes en français et en anglais et se penche sur la qualité de la langue des textes en français.

La formation des professionnels de la santé au Nouveau-Brunswick ou l'application du principe de I'inégalité - Braën, André (Administration publique du Canada, 2008)
Sommaire: Comme partout ailleurs au Canada, le régime des soins médicaux et hospitaliers du Nouveau-Brunswick est universel. Les services de santé qui sont ainsi offerts à la population sont fournis sur une base individuelle, sans égard à la race ou à la langue de l'individu. D'autre part, le Nouveau-Brunswick est la seule province canadienne qui a proclamé officiellement l'egalité juridique des deux communautés linguistiques qui la composent. Dans un tel contexte, l'assurance de la disponibilité de services de santé dans sa propre langue devient un principe général important; elle affecte directement la qualité des services fournis à la minorité francophone de cette province ainsi que le développement de ses institutions hospitalières. L'auteur cherche ici a analyser si, au-delà de cette dialectique juridique dont semble friand le Nouveau-Brunswick, l'égalité de fait est recherchée dans le secteur de la formation des spécialistes de la santé. Puisque cette formation est extrêmement onéreuse et étant donné le nombre restreint de ses habitants, le Nouveau-Brunswick a conclu plusieurs accords avec des provinces voisines dans le but de permettre à ses étudiants de s'inscrire dans des programmes de sciences de la santé non disponibles dans la province. Ayant choisi l'angle linguistique, l'auteur examine les structures mises en place pour appliquer ces accords, le nombre et la qualité linguistique des étudiants ainsi que les sommes dépensées par le Nouveau-Brunswick dans le cadre de l'application de ces ententes. Finalement, il mesure l'intensité de l'effort que fournit cette province pour former des spécialistes francophones.

Comparaisons internationales : un aperçu de l'accès aux soins de santé pour les communautés de langue officielle en situation minoritaire au Canada, en Espagne, en Belgique et en Finlande - Bureau d'appui aux communautés de langue officielle (Santé Canada, 2007)

Programme de contribution pour l'amélioration de l'accès aux services de santé pour les communautés de langue officielle en situation minoritaire. Évaluation formative. - Bureau d'appui aux communautés de langue officielle (Santé Canada, 2007)

Instantané de recherche : portrait de la santé mentale des Canadiens francophones en situation minoritaire - CAMH-Evidence Exchange Network (2020)

La recherche en temps réel : projet ECHO pour francophones - Détermination des besoins des fournisseurs de services desservant les communautés franco-ontariennes afin de créer un programme de formation en français sur le traitement des dépendances - CAMH-Evidence Exchange Network (2023)

Research as it Happens : ECHO project for Francophones - Assessing the needs of service providers working with Franco-Ontarian communities to create a French-language, substance use management training program - CAMH-Evidence Exchange Network (2023)

La santé des francophones en situation minoritaire au cœur de nos actions - Cardinal, Dominique; Borris, Caroline; Pinet, Bernard; Leclair, F. (Reflets, 2018)
Au Canada, plus d’un million de francophones habitent à l’extérieur du Québec, parmi lesquels 35 % rapportent avoir peu ou aucunement accès à des services de santé dans leur langue (Gagnon-Arpin, et collab., 2014). En vue de contrer les défis de la santé dans les communautés francophones en situation minoritaire (CFSM), le Consortium national de formation en santé — Volet Université d’Ottawa a développé plusieurs pratiques prometteuses en matière de soutien aux futurs étudiants et étudiantes, à la population étudiante inscrite aux programmes ciblés par le CNFS ainsi qu’aux professionnelles et professionnels, chercheuses et chercheurs du domaine de la santé. Divers programmes sont mis à profit pour soutenir la génération et la diffusion des connaissances. Ces initiatives ainsi que leurs retombées positives méritent l’attention de tous les partenaires qui ont à coeur la santé des francophones.

La supervision de stagiaires : un art qui s'apprend - Cardinal, Dominique; Couturier, Lucie; Savard, Jacinthe; Tremblay, Manon; Desmarais, Mélanie (Reflets, 2014)
L’Art de superviser des stagiaires est un programme de formation du CNFS — volet Université d’Ottawa visant à outiller les superviseurs qui accompagnent des stagiaires dans leur processus de professionnalisation. Ces ateliers, offerts en ligne ou en présentiel aux professionnels de la santé et des services sociaux oeuvrant dans les communautés francophones minoritaires au Canada, abordent des thèmes comme l’évaluation du rendement et la gestion de conflits. Des données recueillies par questionnaires indiquent qu’à la suite de la formation, les superviseurs se sentent plus à l’aise et intègrent dans leurs tâches de supervision des stratégies et des outils d’encadrement. Mots-clés : formation de superviseurs, supervision de stagiaires, outils d’encadrement, milieu francophone minoritaire, professionnalisation

Les minorités francophones hors Québec et la gouvernance des langues officielles : portrait et enjeux - Cardinal, Linda; Lang, Stéphanie; Sauvé, Anik (Francophonies d'Amérique, 2008)
L’article porte sur l’évolution des formes et des rapports de gouvernance entre le gouvernement fédéral et les communautés minoritaires de langue officielle au Canada. La gouvernance horizontale vise à concrétiser l’engagement du gouvernement fédéral envers les minorités de langue officielle et apparaît comme une forme novatrice d’organisation. Par contre, jusqu’en 2003, elle a aussi servi à compenser l’absence d’action directe et soutenue de la part du gouvernement fédéral envers les minorités de langue officielle. Ce texte étudie et montre comment l’évolution de la gouvernance a suscité des enjeux importants pour le développement de la francophonie en milieu minoritaire.

Évaluer le potentiel de soins linguistiquement concordants pour les francophones de l’Ontario : une étude populationnelle transversale. - Carr, Kady; Batista Moliner, Ricardo; Fitzgerald, Michael; Lamontagne, Sophie; Bader Eddeen, Anan; Timony, Patrick E.; Bédard, Daniel; Gauthier, Alain; Prud’homme, Denis; Landry, Josette-Renée; Chomienne, Marie-Hélène; Denis-Leblanc, Manon; et al. (Minorités linguistiques et société, 2024)
Cette étude a utilisé les données sur les médecins, la facturation et le recensement de 2016 dont dispose l’ICES pour examiner l’accès potentiel à des médecins de famille francophones pour les francophones résidant dans 1 643 aires de diffusion agrégées (ADA) de l’Ontario. L’Ontario compte 550 280 francophones, soit 4,1 % de sa population. Nous avons identifié 8 199 médecins de famille, parmi lesquels 1 169 se sont autodéclarés francophones. Le ratio provincial global pour les francophones était de 2,12 médecins par 1 000 résidentes et résidents, comparativement à un ratio de 0,66 pour les anglophones. Dans les ADA où les francophones étaient majoritaires, le ratio pour les francophones était inférieur au ratio pour les anglophones (0,63 vs 2,02), alors que dans toutes les autres ADA, le ratio francophone était plus élevé (3,46 vs 0,62 dans les 83,4 % des ADA où les francophones représentaient >0 % à <5 % de la population). Huit ADA du Nord-Est et de l’Est de l’Ontario présentaient un déficit relatif important de médecins de famille francophones par rapport au ratio provincial. Ces résultats donnent un aperçu des régions qui pourraient bénéficier de programmes visant à éliminer les barrières linguistiques. Mots-clés : Concordance linguistique, médecins de famille, accès aux soins primaires, francophones, Ontario

Modèle d’apport de services en santé communautaires aux francophones du Sud de l’Ontario : entrevue avec Janet Rajroop - Casimiro, Lynn (Reflets, 2002)

Le recensement des outils de travail disponibles en français pour les professionnels oeuvrant dans le domaine de la santé : un rapport de la méthodologie utilisée par les physiothérapeutes - Casimiro, Lynn; Fortin, Murielle; Moisan, France; Tremblay, Louis E. (Reflets, 2002)

Questionnaire d’aiguillage pour dépister les besoins de formation quant à l’offre active de services en français - Casimiro, Lynn; Savard, Jacinthe; Sauvé-Schenk, Katrine; Atchessi, Nicole (Reflets, 2018)
Des recherches antérieures montrent que certaines caractéristiques personnelles influencent la fréquence des comportements d’offre active des professionnelles et professionnels de la santé et du travail social. Un nouveau questionnaire d’aiguillage rempli par des étudiantes et étudiants de ces domaines aux niveaux collégial et universitaire a permis de déterminer leurs caractéristiques (profil sociolangagier) et de cibler des besoins en formation à l’offre active. Des formations en ligne, repérées parmi les formations déjà sur le Web, leur ont ensuite été proposées, en fonction de leur profil. Nos données montrent qu’il est possible de dresser des profils sociolangagiers utiles pour identifier des besoins de formation d’une manière acceptable pour les répondantes et répondants. Le type de formation qui répondra le mieux aux besoins de chaque profil reste à évaluer[1]. Mots-clés : offre active, formation des professionnelles et professionnels de la santé et des services sociaux, questionnaire d’aiguillage, francophones en situation minoritaire

Un regard sur la distribution des médecins de famille qui parlent français dans les communautés francophones de l’Ontario - Centre de recherche en santé dans les milieux ruraux et du nord (FOCUS sur la recherche [Université Laurentienne], 2013)

Examining the distribution of French speaking family physicians in Ontario’s Francophone communities - Centre for Rural and Northern Health Research (FOCUS on research [Laurentian University], 2013)

Profil génétique et prévalence de la fibrose kystique dans les communautés acadiennes et francophones des Maritimes - Chappe, Frédéric; McGrath, Karla; Robinson, Walter; Chappe, Valérie (Francophone d'Amérique, 2009)
Nous évaluons ici la situation des Acadiens et des francophones des provinces maritimes (Nouvelle-Écosse, Nouveau-Brunswick, Île-du-Prince-Édouard) face à la fibrose kystique, la maladie génétique létale la plus répandue en Amérique du Nord. Nos résultats indiquent que plusieurs familles acadiennes et francophones sont touchées par cette maladie et qu’il existe un besoin de documentation et de services en français, spécifiques aux communautés acadiennes. Des disparités régionales ont été observées pour l’âge au diagnostic et le profil génétique, notamment dans les régions à majorité francophone. Cette analyse confirme le besoin d’études spécifiques sur la santé des Acadiens et des francophones des Maritimes.

Plaidoyer pour la santé - Un guide pratique - Chaput, Sarah (Réseau francophone international pour la promotion de la santé, 2022)

Dans la langue officielle de son choix : la loi canadienne sur les langues officielles et la notion de « choix » en matière de services publics - Charbonneau, François (Lien social et Politiques, 2011)
L’article s’intéresse à la notion de choix en matière de services publics à la lumière de l’expérience de la notion de « langue de son choix » incluse dans les diverses législations canadiennes depuis plus de quarante ans, c’est-à-dire depuis l’adoption de la Loi sur les langues officielles au Canada. Cet exemple montre bien comment le choix en matière de services publics peut avoir des conséquences délétères non intentionnelles pour les populations les plus vulnérables, dans ce cas-ci, les francophones vivant en situation minoritaire.

Le moment Monfort dans la francophonie canadienne. - Charbonneau, François (Presses de l’Université d’Ottawa, 2024)

Vivre et travailler en français à Iqaluit (Nunavut) : regards de professionnels de la santé sur le capital social de la communauté francophone - Charrier, Marie-Josée (Revue du Nouvel-Ontario, 2019)

Les communautés francophones en situation minoritaire : un portrait de famille - Charron, Mathieu (Francophonies d’Amérique, 2014)
Les francophones du Canada vivent dans des environnements linguistiques diversifiés et doivent donc composer avec des contraintes et des conditions spécifiques. Ces particularités impliquent une variété de situations et proscrivent l’application d’un projet unique de développement des communautés. L’article propose une classification des communautés francophones qui tient compte des nombreuses réalités vécues. S’appuyant sur les données du recensement, une typologie de sept catégories est proposée : communautés traditionnelles, diversifiées, assimilées, volatiles, globales, cosmopolites et anglophones. Les spécificités statistiques et les distributions géographiques de chacune des catégories y sont présentées.

Are there mental health differences between Francophone and non-Francophone populations in Manitoba? - Chartier, Mariette Jeanne; Finlayson, Gregory; Prior, Heather; McGowan, Kari-Lynne; Chen, Hui; Walld, Randy; De Rocquigny, Janelle (The Canadian Journal of Psychiatry, 2014)
Objective: Francophones may experience poorer health due to social status, cultural differences in lifestyle and attitudes, and language barriers to health care. Our study sought to compare mental health indicators between Francophones and non-Francophones living in the province of Manitoba. Methods: Two populations were used: one from administrative datasets housed at the Manitoba Centre for Health Policy and the other from representative survey samples. The administrative datasets contained data from physician billings, hospitalizations, prescription drug use, education, and social services use, and surveys included indicators on language variables and on self-rated health. Results: Outside urban areas, Francophones had lower rates of diagnosed substance use disorder (rate ratio [RR] = 0.80; 95% CI 0.68 to 0.95) and of suicide and suicide attempts (RR = 0.59; 95% CI 0.43 to 0.79), compared with non-Francophones, but no differences were found between the groups across the province in rates of diagnosed mood disorders, anxiety disorders, dementia, or any mental disorders after adjusting for age, sex, and geographic area. When surveyed, Francophones were less likely than non-Francophones to report that their mental health was excellent, very good, or good (66.9%, compared with 74.2%). Conclusions: The discrepancy in how Francophones view their mental health and their rates of diagnosed mental disorders may be related to health seeking behaviours in the Francophone population. Community and government agencies should try to improve the mental health of this population through mental health promotion and by addressing language and cultural barriers to health services.

How healthy are Manitoba’s Francophones? A summary of report, Health and healthcare utilization of Francophones in Manitoba - Chartier, Mariette; Finlayson, Greg; Prior, Heather; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Ottawa, Manitoba Center for Health Policy, 2012)
A summary of the report, Health and Healthcare Utilization of Francophones in Manitoba / La santé et l’utilisation des services de santé des francophones du Manitoba by Mariette Chartier, Greg Finlayson, Heather Prior, Kari-Lynne McGowan, Hui Chen, Janelle de Rocquigny, Randy Walld, Michael Gousseau Summary written by Michelle Houlden

Quel est l’état de santé des francophones du Manitoba ? Sommaire du rapport intitulé La santé et l'utilisation des services de santé des francophones du Manitoba - Chartier, Mariette; Finlayson, Greg; Prior, Heather; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Manitoba, Manitoba Center for Health Policy, University of Manitoba, 2012)

Health and healthcare utilization of Francophones in Manitoba - Chartier, Mariette; Finlayson, Gregory. S.; Prior, Heather. J.; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Manitoba, Manitoba Center for Health Policy, 2012)

La santé et l'utilisation des services de santé des francophones du Manitoba - Chartier, Mariette; Finlayson, Gregory. S.; Prior, Heather. J.; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Manitoba, Manitoba Center for Health Policy, 2012)

La pénurie de professeures de sciences infirmières au Canada et ses effets sur les programmes de formation en sciences infirmières offerts en français - Chartrand, Julie; Vandyk, Amanda; Beké, Émilie; Balasa, Rebecca; Loranger, Catherine; Muray, Mwali; Chartrand, Mariève; Baker, Cynthia (Minorités linguistiques et société, 2019)
Cette étude qualitative décrit la pénurie de professeures en sciences infirmières et ses effets actuels et potentiels sur les programmes canadiens de formation en sciences infirmières offerts en français, ainsi que les stratégies préconisées par les directrices de ces programmes afin d’en atténuer les effets. Les effets de la pénurie sont particulièrement préoccupants dans le cas des programmes offerts dans un contexte francophone minoritaire ou en région éloignée. La pénurie mettrait en péril les programmes offerts en français et menacerait, par le fait même, la qualité des services de santé offerts aux communautés francophones minoritaires au Canada. Mots-clés : pénurie professorale, sciences infirmières, professionnels de la santé, services et soins de santé en français, communautés francophones en situation minoritaire

Portrait des minorités de langue officielle au Canada : les francophones de l’Île-du-Prince-Édouard - Chavez, Brigitte; Lepage, Jean-François; Bouchard-Coulombe, Camille (Statistique Canada, 2012)
Réalisé grâce au soutien financier du Secrétariat des langues officielles de Patrimoine canadien, de Ressources Humaines et Développement des Compétences Canada (RHDCC) ainsi que du ministère de la Justice Canada, ce portrait de la population de langue française de l’Île-du-Prince-Édouard est le dixième d’une série de portraits démolinguistiques des minorités de langue officielle au Canada rédigés par la Section des statistiques linguistiques de Statistique Canada. Cette étude brosse un portrait statistique général de la minorité de langue officielle de l’Île-du-Prince-Édouard en s’appuyant sur des données de recensements de la population ainsi que sur celles de l’Enquête sur la vitalité des minorités de langue officielle au Canada menée en 2006. Le but d’un tel portrait est de présenter un ensemble de caractéristiques, de comportements et de perceptions de la population de langue officielle minoritaire en mettant en évidence les possibilités d’analyse que recèlent les données. Le présent document ne se veut ni un simple assemblage de tableaux ni une étude approfondie de la dynamique démolinguistique de la population de langue française de l’Île-du-Prince-Édouard. Il présente une information diversifiée sur un ensemble de thèmes et de problématiques qui revêtent un intérêt pour les minorités de langue officielle et pour quiconque s’intéresse à la situation passée, actuelle et future des populations de langue officielle en situation minoritaire au Canada. La première section de ce portrait démolinguistique porte sur le choix des critères de définition de la population de langue française de l’Île-du-Prince-Édouard qui seront utilisés aux fins de ce document ainsi que sur une brève description des sources de données utilisées. La seconde section présente différentes informations qui rendent compte de l’évolution de la population de langue française ainsi que sur la répartition et la concentration de cette population sur le territoire de l’Île-du-Prince-Édouard. Cette information est accompagnée d’une carte géographique présentée en annexe et d’un tableau détaillé sur l’effectif, le poids relatif et la répartition de la population de langue française de l’Île. La troisième section de ce portrait porte sur les principaux facteurs qui influent sur l’évolution de la population de langue française dans cette province ou qui en résultent, soit la transmission de la langue maternelle et l’effet de l’exogamie, la structure par âge, la mobilité linguistique intragénérationnelle et la migration interprovinciale. De plus, on y présente de l’information sur l’usage du français dans la sphère publique et sur l’évolution de la capacité de soutenir une conversation selon le groupe de langue maternelle. La quatrième section porte sur quelques secteurs clés pour la vitalité des communautés de langue officielle en situation minoritaire tels qu’identifiés dans la Feuille de route pour la dualité linguistique canadienne 2008-2013 : agir pour l’avenir1, soit la santé, la justice, l’éducation et les médias, les arts et la culture. Nous y présentons également des statistiques sur la participation communautaire, les caractéristiques de l’emploi et du revenu ainsi que sur l’utilisation du français au travail. Finalement, la dernière section de ce portrait présente des statistiques sur l’appartenance identitaire des francophones et leurs perceptions à l’égard de la présence du français dans leur communauté, de l’offre de services en français de la part du gouvernement fédéral, du respect des droits linguistiques ainsi qu’à l’égard du fait que des gens travaillent au développement de la communauté francophone.

Portrait of Official-Language Minorities in Canada: Francophones in Prince Edward Island - Chavez, Brigitte; Lepage, Jean-François; Bouchard-Coulombe, Camille (Statistics Canada, 2012)
This demolinguistic portrait of the French-speaking population in Prince Edward Island was undertaken with the financial support of Canadian Heritage’s Official Languages Secretariat, Human Resources and Skills Development Canada (HRSDC) and Justice Canada. It is the tenth in a series of demolinguistic portraits of official-language minorities in Canada, prepared by Statistics Canada’s Language Statistics Section. This study paints a general statistical portrait of the official-language minority in Prince Edward Island based on data from the Census of Population and the Survey on the Vitality of Official-Language Minorities in Canada, conducted in 2006. The purpose of such a portrait is to present a set of characteristics, behaviours and perceptions of the minority official-language population, exploiting the analytical opportunities contained in the data. This document is intended to be neither a mere collection of tables nor an in-depth study of the demolinguistic dynamics of the English-speaking population in Prince Edward Island. It presents a range of themes and issues that will be of interest to official-language minorities and anyone concerned with the past, present and future situation of minority official-language populations in Canada. Section 1 of this demolinguistic portrait concerns the criteria chosen in this study to define Prince Edward Island’s French-speaking population. It also provides a brief description of the data sources used. Section 2 presents varied information on the evolution of the French-speaking population and its geographic distribution and concentration in Prince Edward Island. This includes an appended map and a detailed table on the size, relative weight and distribution of the Island’s French-speaking population. Section 3 concerns the main factors that affect or are affected by changes over time in this province’s French-speaking population: transmission of mother tongue and the effect of exogamy; age structure; intragenerational linguistic mobility; and interprovincial migration. It also discusses the use of French in the public sphere and how the ability to conduct a conversation in that language has evolved according to mother-tongue group. Section 4 looks at a few sectors essential to the vitality of minority official-language communities, as identified in the Roadmap for Canada’s Linguistic Duality 2008–2013: Acting for the Future,1 namely health, justice, education and the media, the arts and culture. It also provides statistics on community participation, employment and income characteristics, and the use of French at work. The last section of this portrait presents statistics on the identity of Francophones and their perceptions regarding the presence of French in their community, the provision of federal government services in French, the respect for linguistic rights, and the fact that people are working to develop the Francophone community.

Enquête exploratoire sur le recueil de la variable linguistique dans les données administratives des hôpitaux de la région du RLISS-Champlain - Chomienne, Marie-Hélène; LeClerc, Chantale; Schnarch, Brian; Bouchard, Louise; McKay, Martine; Farmanova, Elina (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, Réseau local d’intégration des services de santé de Champlain, 2011)

La question de l’autonomie des francophones hors Québec. Trois décennies d’activisme judiciaire en matière de droits linguistiques au Canada - Chouinard, Stéphanie (Université d'Ottawa, 2016)
La thèse étudie la question de l’autonomie des francophones hors Québec au regard de trente ans d’activisme judiciaire dans le domaine des droits linguistiques depuis l’adoption de la Charte canadienne des droits et libertés. Nous étudions la jurisprudence importante dans ce domaine, provenant majoritairement de la Cour suprême du Canada et la possibilité, pour les juges, de faire avancer une norme d’autonomie pour les francophones hors Québec (FHQ). La thèse démontre que l’interprétation des droits linguistiques par les juges est contrainte par des éléments contextuels comme les traditions étatiques du compromis politique et du fédéralisme. Ces traditions étatiques conditionnent les représentations que se font les juges des droits linguistiques et créent des effets de « dépendance au sentier » dans le domaine de la jurisprudence, limitant la possibilité, pour les juges, de faire avancer une norme d’autonomie pour les FHQ. Les juges peuvent toutefois réviser ces éléments de dépendance au sentier afin de présenter de nouvelles représentations des droits linguistiques dans la jurisprudence, instigatrices de « points tournants », voire de nouveaux paradigmes d’interprétation, dans l’évolution des droits linguistiques. La thèse permet de voir que l’activisme judiciaire dans le domaine des droits linguistiques demeure soumis aux éléments structurants du régime linguistique canadien. En conséquence, les juges ont répondu, de façon graduelle, à certaines revendications des minorités francophones du Canada, sans toutefois combler toutes leurs aspirations d’autonomie. Afin de réaliser cette recherche, nous avons proposé une analyse herméneutique de la jurisprudence. Nous avons aussi mobilisé les outils théoriques de l’institutionnalisme historique et la notion de représentations afin de montrer les facteurs de continuité et de changement dans le domaine des droits linguistiques. Ces outils nous ont permis de compléter l’approche personnelle aux décisions des juges en arrimant l’analyse de la jurisprudence à son contexte institutionnel d’énonciation et d’observer la dépendance au sentier et les points tournants dans l’interprétation des droits linguistiques sur trois décennies. Cette recherche contribue à l’avancement des connaissances en participant au débat normatif et à l’analyse institutionnelle des droits des minorités linguistiques. D’abord, la thèse met en dialogue les disciplines du droit et de la science politique, grâce à une analyse institutionnelle de la jurisprudence canadienne dans le domaine des droits linguistiques. Elle contribue aussi au domaine d’étude de la judiciarisation de la politique canadienne et la mobilisation judiciaire des « citoyens de la Charte » - où les FHQ brillent par leur absence. Ensuite, sur le plan normatif, la thèse montre comment l’évolution de la jurisprudence pose de nouveaux jalons pour penser l’autonomie des FHQ. Cette discussion nourrit aussi le débat international sur les droits auxquels les minorités linguistiques peuvent aspirer, dans le sillon des travaux de Cardinal (2008), de Cardinal et González Hidalgo (2012), de Foucher (2012), de Léger (2015) de Kymlicka (2012), et de Poirier (2012). Finalement, au plan théorique, en tentant de démontrer l’existence d’éléments contextuels contraignant l’évolution de la jurisprudence de droit linguistique au Canada, notre thèse confirme l’utilité de l’approche néo-institutionnaliste historique pour l’étude de la question de la « judiciarisation de la politique » au Canada, un domaine dominé par les approches instrumentalistes.

Quand le droit linguistique parle de sciences sociales : l’intégration de la notion de complétude institutionnelle dans la jurisprudence canadienne - Chouinard, Stéphanie (Revue de droit linguistique, 2016)

Quel avenir pour le projet autonomiste des communautés francophones en situation minoritaire ? Réflexion sur les politiques publiques canadiennes en matière de langues officielles - Chouinard, Stéphanie (Minorités linguistiques et société, 2012)
Nous tentons de mettre au jour quelques possibilités d’application, en matière de politiques publiques, des revendications de reconnaissance politique des communautés francophones en situation minoritaire (CFSM) du Canada, que nous organisons selon deux optiques différentes, soit l’autonomie et l’intégration. Après quelques considérations d’ordre sociopolitique et juridique, nous plaiderons pour une asymétrie dans l’élaboration des politiques publiques relatives à ces communautés. Nous soulignerons aussi le poids des enjeux de pouvoir dans la relation entre l’État et les CFSM, notamment sur le plan de la gouvernance, dans l’élaboration de ces politiques. Mots-clés : autonomie, politiques publiques, communautés francophones en situation minoritaire, communautés de langue officielle au Canada, participation politique

The principle of minority protection and language rights in Canada: The secession reference’s legacy - Chouinard, Stéphanie (Journal of Parliamentary and Political Law, 2021)

Talk COVID to me: Language rights and canadian government responses to the pandemic - Chouinard, Stéphanie; Normand, Martin (Canadian Journal of Political Science, 2020)
Since the COVID-19 outbreak, a gradual loosening of linguistic obligations in public institutions and governments has been observed in various jurisdictions in Canada. This article argues that in addition to legal requirements to provide minority language services, it is not justifiable for governments to suspend or curtail such services in an emergency situation, for reasons pertaining to public safety and public health. After performing a survey and analysis of government actions against their constitutional, legislative, and policy language obligations to highlight best practices and deficiencies, we discuss the policy implications of these actions. In conclusion, the article considers how governments could better uphold their language obligations in times of emergency.

Une innovation réussie et durable au sein d’un réseau de santé, soit un hôpital et centre de santé communautaire en région rurale au Canada - Collin, Stéphanie; Michaud, Nancy; Ringuette, Claudie (Revue francophone sur la santé et les territoires, 2024)
Dans le monde, les décideurs publics tentent de trouver des arrangements structuraux pour améliorer la performance des systèmes de santé. La stratégie de régionalisation a été privilégiée depuis quelques décennies par une majorité des provinces canadiennes. Dans cet article, nous nous penchons sur les dynamiques relationnelles entre les acteurs associés à une régie régionale de la santé et leur influence sur la naissance et l’adoption d’une pratique innovante, soit un hôpital et centre de santé communautaire en région rurale. Une méthode de recherche qualitative a été retenue et la collecte de données a été effectuée par le biais d’entretiens semi-dirigés, de groupes de discussion, ainsi qu’une analyse documentaire. L’émergence et la pérennité d’une pratique innovante nécessitent une définition de la santé qui fait consensus, la présence d’entrepreneurs institutionnels et une redéfinition des rôles et responsabilités entre l’autorité centrale et les acteurs locaux. La mise en œuvre d’une gouvernance collaborative est également requise.

Pour un nouveau leadership en matière d'amélioration des services de santé en français. Rapport au ministre fédéral de la santé - Comité consultatif des communautés francophones en situation minoritaire (Santé Canada, 2007)

Rapport au ministre fédéral de la santé - Comité consultatif des communautés francophones en situation minoritaire (Santé Canada, 2001)

Évaluation de l’offre active des services de santé de première ligne - Comité santé en français de Fredericton (Groupe Progecom communication et stratégies d’entreprise, 2006)

L’offre active une culture de respect, une culture d’excellence : dépliant [infographie] - Commissariat aux langues officielles (2019)

L’offre active une culture de respect, une culture d’excellence : guide complet [infographie] - Commissariat aux langues officielles (2017)

Une question de respect et de sécurité : l’incidence des situations d’urgence sur les langues officielles - Commissariat aux langues officielles (Gouvernement du Canada, 2020)

Étude sur les besoins en formation clinique et en formation continue des professionnels de la santé des communautés francophones en situation minoritaire - Consortium national de formation en santé (2006)

La discordance linguistique. L'intervenant et le patient ne parlent pas la même langue ou ne peuvent pas communiquer adéquatement [infographie] - Consortium national de formation en santé (2022)

La formation à l’offre active de services de santé et de services sociaux en français — La valeur ajoutée du Consortium national de formation en santé (CNFS) - Consortium national de formation en santé (Reflets, 2014)

La mobilisation des connaissances en santé dans les CFSM [infographie] - Consortium national de formation en santé (2021)

La recherche, un levier pour améliorer la santé. 1er forum national de recherche sur la santé des communautés francophones en situation minoritaire - Consortium national de formation en santé; Société Santé en français (Santé Canada, 2005)

La santé des francophones en situation minoritaire : un urgent besoin de plus d’information pour offrir de meilleurs services - Consortium national de formation en santé; Société Santé en français (La santé des francophones en situation minoritaire : un urgent besoin de plus d’information pour offrir de meilleurs services, 2010)

The health of Francophones in minority communities: An urgent need for more information to provide better services - Consortium national de formation en santé; Société Santé en français (The health of Francophones in minority communities: An urgent need for more information to provide better services, 2010)

Towards a new leadership for the improvement of health services in French. Report to the federal minister of health - Consultative Committee for French-Speaking Minority Communities (Health Canada, 2007)

Les minorités prennent la parole : résultats de l'Enquête sur la vitalité des minorités de langue officielle - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistique Canada, 2007)

Minorities speak up: Results of the survey on the vitality ot the Official-Language Minorities - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistics Canada, 2007)

Portrait des minorités de langue officielle au Canada : les francophones de l'Ontario - Corbeil, Jean-Pierre; Lafrenière, Sylvie (Statistique Canada, 2010)

Portrait of Official-Language Minorities in Canada: Francophones in Ontario - Corbeil, Jean-Pierre; Lafrenière, Sylvie (Analytical Paper, 2010)

Les Canadiens partiellement français sont susceptibles à une augmentation des facteurs de risque cardiovasculaire : une étude de cohorte rétrospective basée sur la population - Daccache, J.; Savoury, M.; Yam, Y.; Chow, B. J. M. (Annales de Cardiologie et d'Angéiologie, 2020)
Introduction Grâce à diverses recherches menées dans le passé, il a été démontré que le Québec est la province avec les taux d’infarctus aigü du myocarde (IAM) et la prévalence des facteurs de risque cardiovasculaire les plus élevés au Canada. Cette étude proposée effectuera une analyse rétrospective sur les populations caucasiennes, afin d’analyser les facteurs de risque cardiovasculaire dans les populations partiellement francophones par rapport aux Canadiens-Français et non-Français. En outre, nous analyserons de près les deux sexes des populations susmentionnées. Méthode Cette étude de cohorte rétrospective, basée sur la population, a été réalisée en utilisant le registre de l’ACTC de l’Institut de cardiologie de l’Université d’Ottawa (ICUO). Les participants sont des patients de race blanche de tout âge, qui sont venus à l’ICUO pour une angiographie par tomodensitométrie, entre 2006 et 2018, et qui ont donné leur consentement éclairé. SPSS a été utilisé pour comparer les différentes populations (Canadiens-Français [CF], Canadiens partiellement Français [CPF], et Canadiens non-Français [CNF]) et les différents sexes. Résultats La population des CPF ressemble plus à celle des FC, ayant une incidence plus élevée de facteurs de risque cardiovasculaire tels que le tabagisme, la dyslipidémie et le diabète de type 2. Interprétation Nos résultats suggèrent que les CPF, comme les CF, pourraient bénéficier d’une éducation plus intensive et de techniques de modification du mode de vie.

Access to resources in the community through navigation: Protocol for a mixed-methods feasibility study - Dahrouge, Simone; Gauthier, Alain; Chiocchio, François; Presseau, Justin; Kendall, Claire; Lemonde, M.; Chomienne, Marie-Hélène; Perna, A.; Toal-Sullivan, Darene; Devlin, R. A.; Timony, Patrick; Prud'homme, Denis (JMIR Publications, 2019)
Background: Community-based health and social resources can help individuals with complex health and social needs achieve their health goals. However, there is often inadequate access to these resources due to a lack of physician and patient awareness of available resources and the presence of social barriers that limit an individual’s ability to reach these services. Navigation services, where a person is tasked with helping connect patients to community resources, embedded within primary care may facilitate access and strengthen the continuity of care for patients. Objective: This study aims to describe the protocol to assess whether the implementation of the Access to Resources in the Community (ARC) navigation model (an innovative approach to navigation services) is feasible, including its potential to achieve its intended outcomes, and to assess the viability of the evaluation approach. Methods: The study consists of a single-arm, prospective, explanatory, mixed-methods, pre-post design feasibility study focusing on primary care practice settings with vulnerable populations. Participants include primary care providers and patients. Results: Enrollment is closed with 82 patients. Navigation services have ended for 69 patients. Conclusions: The study of an innovative complex intervention requires an adequate assessment of the feasibility of the intended approach during which the potential challenges of the planned intervention and need for its adaptation may be uncovered. Undertaking a feasibility study of the ARC navigation model from a conceptually clear and methodologically solid protocol will inform on the practicality and acceptability of the approach, demand for the services, ease of implementation, quality of integration of the new services within primary care, and practicality and potential for efficacy prior to initiating a randomized controlled trial.

Accès aux services de santé et d’interprète accompagnateur : l’expérience des communautés minoritaires à faible densité de francophones au Canada. Rapport de recherche-Projet INTACC - de Moissac, Danielle (Société Santé en français, 2016)

Access to health and interpreter-companion services – the experience of sparsely populated Francophone minority communities in Canada - de Moissac, Danielle (Société Santé en français, 2016)

Agir ! Pour ma santé : une intervention harmonisant Services médicaux et diagnostiques et services communautaires pour les Franco-Manitobains souffrant de dépression - de Moissac, Danielle; Bohémier, Moniqu; Herdman, Chelsea; Roch-Gagné, Margaux; Paillé, Julie; Johnston, Christine; Arpin-Molinski, Michelle; Dupuis, Georgette; Saint-Hilaire, Mélanie; Prairie, Liliane (Reflets, 2012)

Impact of language barriers on access to healthcare for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Healthcare management forum, 2017)
While there is strong international evidence that language barriers present obstacles to healthcare access, quality and safety, little research has been conducted on the experience of official language minorities in Canada. This multiple method research used on-line and paper-based surveys, combined with semi-structured individual interviews to explore the experience with access to care of Francophone minorities living in four Canadian provinces. The majority of Francophones surveyed reported limited access to French language services and described an environment where low importance is given to addressing language barriers within the health system. Even when services are available, the lack of services in French sometimes results in avoidance of care. Results confirm that many Francophones face similar barriers to care as other language minorities in Canada. Strategies to improve access for official language minorities are discussed.

Impact of language barriers on quality of care and patient safety for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Journal of Patient Experience, 2019)
Introduction: The risks to patient safety and quality of care faced by members of linguistic minority groups have been well-documented. However, little research has focused on the experience of official language minorities in Canada. Methods: This multiple method study (online and paper-based surveys combined with semi-structured individual interviews with patients and interpreters-health navigators) explored the experience of minority Francophones living in 4 Canadian provinces. Results: Patients and interpreters-navigators described experiences where language barriers contributed to poorer patient assessment, misdiagnosis and/or delayed treatment, incomplete understanding of patient condition and prescribed treatment, and impaired confidence in services received. Reliance on Google Translate and ad hoc, untrained interpreters are commonly reported, in spite of evidence highlighting the risks associated with such practice. Conclusion: Increased awareness that the risks of language barriers apply to official language minorities is essential.

Défis associés à l’offre de services de santé et de services sociaux en français au Manitoba : perceptions des professionnels - de Moissac, Danielle; de Rocquigny, Janelle; Giasson, Florette; Tremblay, Cindy-Lynne; Aubin, Natalie; Charron, Marc; Allaire, Gratien (Reflets, 2012)
Les services de santé et les services sociaux en français ne sont accessibles qu’auprès d’un quart de la population francophone au Manitoba (de Moissac, 2011). Une pénurie de professionnels pouvant offrir des services en français est perçue comme un obstacle important pour les usagers qui recherchent ces services et pour les professionnels qui voudraient assurer un suivi en français pour leurs clients. Une hésitation à s’identifier comme francophone et un manque de connaissance des ressources disponibles en français contribuent-ils à cette perception de pénurie? Cet article traite des défis entourant l’offre de services de santé et de services sociaux en français au Manitoba et suggère des pistes de solutions. Mots-clés : disponibilité, accessibilité, minorité francophone, Manitoba, professionnels

Disponibilité et accessibilité des services de santé en français au Manitoba. Rapport final - de Moissac, Danielle; de Rocquigny, Janelle; Roch-Gagné, Margaux; Giasson, Florette (Université de Saint-Boniface et Institut franco-ontarien de l’Université Laurentienne, 2011)

Enjeux et défis dans l’offre de services dans la langue de la minorité : l’expérience des professionnels bilingues dans le réseau de la santé et des services sociaux - de Moissac, Danielle; Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette; Benoît, Josée; Arcand, Isabelle; Lagacé, Josée; Dubouloz, Claire-Jehanne (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Le présent chapitre dévoile l’expérience de professionnels bilingues quant à l’offre de services sociaux et de santé dans la langue officielle de la minorité en contexte canadien. Soixante-douze professionnels du Manitoba et de l’Est ontarien décrivent les principaux enjeux associés à la langue et les défis auxquels ils sont confrontés quotidiennement dans l’offre active de ces services. Ces défis concernent la pénurie de professionnels et de services bilingues, la difficulté à repérer le client désirant un service dans la langue officielle de la minorité et les professionnels bilingues, ainsi que l’absence d’appui organisationnel pour faire une offre active de services dans les établissements de santé. Pour mieux soutenir l’offre de services dans la langue de la minorité, des pistes de solution sont proposées. Mots-clés : offre active, santé et services sociaux, langue officielle, contexte minoritaire, professionnels.

Issues and challenges in providing services in the minority language: The experience of bilingual professionals in the health and social service network - de Moissac, Danielle; Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette; Benoît, Josée; Arcand, Isabelle; Lagacé, Josée; Dubouloz, Claire-Jehanne (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Accès aux services sociaux et de santé en français : l’expérience des Franco-Manitobains - de Moissac, Danielle; Giasson, Florette; Roch-Gagné, Margaux (Minorités linguistiques et société / Linguistic Minorities and Society, 2015)
Des progrès considérables sont constatés dans l’offre de services et la formation de professionnels dans le domaine des services sociaux et de santé en français au Manitoba depuis les 30 dernières années. L’objectif de cette recherche est de mieux connaître la perception des usagers quant aux services couramment disponibles et aux barrières réduisant l’accès à ces services. L’obtention de services en français est importante pour la population francophone, particulièrement pour les aînés et les immigrants. En moyenne, 50 % des répondants disent demander des services en français, mais seulement 25 % affirment les recevoir. La pénurie de professionnels pouvant offrir des services en français est considérée comme la barrière principale à l’accès. L’offre active est essentielle et facilite la prestation des services dans la langue de choix de la clientèle. Mots-clés : accessibilité, santé, services sociaux, Manitoba, minorité francophone

Besoins et services en français en matière de sexopérinatalité chez les couples parentaux franco-ontariens - de Pierrepont, Catherine; Polomeno, Viola; Bouchard, Louise; Reissing, Elke (Minorités linguistiques et société, 2017)
Cet article dévoile un portrait des besoins et des services en français en matière de sexopérinatalité perçus par 67 couples parentaux francophones en situation linguistique minoritaire d’Ottawa et de l’Est de l’Ontario. Les couples ont des besoins d’informations et de soutien ; pour eux, il est important d’aborder la sexualité pendant la période périnatale. Toutefois, le sujet est peu discuté avec les professionnels de la santé, et très peu de services sexopérinataux en français sont offerts, même s’ils sont souhaités par ces couples. Les discussions sur la sexualité qui se déroulent majoritairement en anglais constituent un obstacle supplémentaire pour une majorité des couples. Mots-clés : sexualité périnatale, couples parentaux, périnatalité, francophones en situation linguistique minoritaire, services de santé en français

Profil des ressources des communautés francophones en milieu minoritaire - Deroche, Francine; Simard, Anne; Di Ruggiero, Erica; Levesque, Johanne (Reflets, 2007)
Le Réseau canadien de la santé (RCS) est une initiative nationale financée par Santé Canada. Le Réseau favorise l’accès à une information fiable, crédible et continuellement mise à jour, sur la santé et vient renforcer les réseaux existants de promotion de la santé. Le RCS a mené une enquête pour identifier quelles sont les informations disponibles sur la santé dans les communautés francophones vivant en milieu minoritaire. Il s’agit là d’un point de départ pour permettre au RCS de planifier et de mettre en œuvre des services en français pertinents. Les objectifs de l’enquête étaient: • d’identifier et d’établir le profil des organismes qui traitent de la santé des Francophones; • d’identifier les types d’organismes recommandés comme sources d’information aux consommateurs et consommatrices et aux intermédiaires de la santé; • d’identifier les ressources existantes les plus souvent demandées par les consommateurs et consommatrices et les intermédiaires de la santé et, • d’identifier les lacunes en matière d’informations sur la santé des francophones

Utilisation des services gouvernementaux de langue française. Une étude auprès des Acadiens et francophones de la Nouvelle-Écosse sur les facteurs associés à l’utilisation des services gouvernementaux en français - Deveau, Kenneth; Landry, Rodrigue; Allard, Réal (Institut canadien de recherche sur les minorités linguistiques, 2009)

Utilisation des services gouvernementaux de langue française : une étude auprès des Acadiens et francophones de la Nouvelle-Écosse sur les facteurs associés à l’utilisation des services gouvernementaux en français : sommaire - Deveau, Kenneth; Landry, Rodrigue; Allard, Réal (Institut canadien de recherche sur les minorités liguistiques, 2010)

Accès aux services en santé dans la langue officielle de leur choix par les minorités francophones hors Québec. Analyse de données secondaires - Diaz Pinsent Mercier Research Inc (Consortium national de formation en santé, 2021)

Vers une amélioration de la prestation de services de santé pour les Franco-Ontariens - Doucet, Pascale-Anne. M.; Gorham, Robyn; Hunt, Elena (Journal de recherche interdisciplinaire, 2021)
Malgré le statut de dualité linguistique du Canada, la communauté francophone continue d’être laissée pour compte par les autorités du pays. Plus spécifiquement, l’étendue et l’accès restreints des services de santé offerts aux francophones en Ontario posent un grave danger pour cette population. Les établissements qui dispensent des services de santé continuent d’ignorer les politiques de soins existantes. Cette situation impose plusieurs actions au niveau fédéral, législatif et communautaire nécessaires afin d’assurer la garantie bilingue promise à la population canadienne. Parmi celles-ci, il faut augmenter la présence francophone dans les groupes décisionnels pour assurer la conception et l’établissement de programmes et services de santé axés sur les besoins uniques et distincts des franco-ontariens. Par ailleurs, l’engagement financier fédéral envers des organismes communautaires francophones est essentiel afin de fournir plus de services de santé en français, surtout dans les communautés nordiques et rurales de la province. Finalement, la subvention gouvernementale de futures recherches sur la santé des francophones est nécessaire puisque celles-ci vont servir de base solide pour déterminer comment mieux desservir cette population. Pour y arriver, il faudrait considérer le lobbying, l’encouragement des institutions qui dispensent des services de santé d’obtenir leur désignation bilingue, et la mise à jour de la Loi sur les services en français. Cependant, en continuant l’inaction, les Franco-Ontariens risquent de devenir assimilés au restant de la population, de dépérir et de voir leur santé se détériorer. Cet article cherche notamment à signaler la nécessité d’améliorer la prestation de services de santé en français en Ontario.

Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire - Drolet, Marie; Bouchard, Pier; Savard, Jacinthe (Presses de l'Université d'Ottawa, 2017)
Ce collectif multidisciplinaire examine les enjeux linguistiques de l’offre active des services sociaux et de santé en français aux communautés francophones en situation minoritaire. Dirigé vers l’action, il contribue à la formation de leaders capables d’intervenir efficacement. Pour les communautés francophones en situation minoritaire (CFSM), l’offre active des services de santé et des services sociaux en français est une question de qualité, de sécurité, d’humanisation des soins et services, de droit et d’équité, et d’éthique professionnelle. Les enjeux liés à la formation postsecondaire et aux ressources humaines, notamment au recrutement et à la rétention des professionnels, sont particulièrement importants, car il est essentiel de former les leaders de demain. Ainsi, cet ouvrage combine la théorie et les données empiriques pour se diriger vers l’action afin de permettre aux futurs professionnels de mieux saisir les enjeux de l’accessibilité et de l’offre active de services en français qui se posent en milieu de travail.

Accessibility and active offer: Health care and social services in linguistic minority communities - Drolet, Marie; Bouchard, Pier; Savard, Jacinthe (University of Ottawa Press, 2017)
This edited volume examines language issues within the active offer of health and social services in francophone and anglophone minority communities. Action based, it will help shape the leaders of tomorrow. It is imperative that we train leaders who are able to intervene efficiently with service users and to support a better organization of the workplace. It is especially important to look at the many issues related to postsecondary training and human resources, such as recruiting and keeping these leading professionals. Accessibility and Active Offer thus combines theory and empirical data to help future professionals understand the workplace issues of accessibility and active offer of minority-language services. This English-language adaptation of Accessibilité et offre active features an additional chapter by Richard Bourhis on issues specific to Anglophone communities in Québec.

Problématique générale : Enjeux de l’accessibilité et de l’offre active de sociaux et de santé au sein de la francophonie canadienne en situation minoritaire - Drolet, Marie; Bouchard, Pier; Savard, Jacinthe; Laforge, M.-J. (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Cette problématique générale vise tout d’abord à présenter un portrait global des communautés francophones en situation minoritaire (CFSM) au Canada. Nous présenterons aussi la problématique de l’accessibilité à des services sociaux et de santé en français en contexte linguistique minoritaire, l’importance de l’accès à des services dans la langue officielle de son choix et les principaux éléments qui justifient le fait d’offrir activement des services sociaux et de santé en français dans les CFSM. Nous établirons également les bases d’une définition de l’offre active et certains contours politiques et historiques qui façonnent les services sociaux et de santé en français en contexte francophone minoritaire. Cette problématique générale sera, par conséquent, une assise pour chacun des chapitres qui composeront cet ouvrage et en facilitera la compréhension.

Introduction: Social services and health services in minority-language communities: Towards an understanding of the actors, the system, and the levers of action - Drolet, Marie; Bouchard, Pier; Savard, Jacinthe; van Kemenade, Solange (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Introduction : Vers une compréhension des acteurs, du système et des leviers d’action - Drolet, Marie; Bouchard, Pier; Savard, Jacinthe; van Kemenade, Solange (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Cette introduction présente le fil conducteur du livre, ainsi qu'une introduction à chacun de ses chapitres

L’accès aux services sociaux et de santé en français et la formation des professionnelles et professionnels en situation francophone minoritaire canadienne - Drolet, Marie; Dubouloz, Claire-Jehanne; Benoît, Josée; Dubois, M. (Reflets, 2014)

Health services for linguistic minorities in a bilingual setting: Challenges for bilingual professionals - Drolet, Marie; Savard, Jacinthe; Benoît, Josée; Arcand, Isabelle; Savard, Sébastien; Lagacé, Josée; Lauzon, S.; Dubouloz, Claire-Jehanne (Qualitative Health Research, 2014)
We explore in this qualitative research the challenges faced by bilingual health and social services professionals in a Canadian bilingual setting, as well as the strategies used to overcome them. Eight focus groups were conducted with a total of 43 bilingual Francophone professionals who offered services in French in 21 health and social service organizations in eastern Ontario, Canada. We highlight linguistic issues affecting a minority Francophone clientele, the shortage of services in French, and organizational issues within these agencies. The solutions that the professionals adopt for better serving the clients and overcoming these challenges focus on adapting services from linguistic angles. In the long term, such an enhanced approach can affect staff well-being. Ensuring access to services for linguistic minority populations and the active offer of same should not rest solely on the shoulders of such professionals, but rather on organizational strategies.

From Policy to Practice: A Qualitative Study on Reforms and Frontline Retention in Healthcare - Dubé, Anik; Collin, Stéphanie; Hakim, Jennifer; Johnson, Claire; Laforest, Marie-Ève; Landry, Michel H.; Lauzier, Martin (INQUIRY: The Journal of Health Care Organization, Provision, and Financing, 2025)
In Canada, healthcare reforms typically aim to improve the quality of care and access while making healthcare systems more efficient. These reforms have led to a 2-level healthcare system consisting of provincial and regional health authorities (RHAs). RHAs are responsible for providing and administering health services within specific territories. One of the 2 language-based RHAs in New Brunswick (NB) operates in French-speaking rural minority communities. This study explored key factors affecting the retention of nurses and physicians within a RHA operating in a language minority context. This descriptive qualitative study explored how macro-level decisions are experienced on the frontlines. Data were collected through semi-structured interviews with 21 physicians and 37 registered nurses, as well as 2 focus groups involving 20 key informants in managerial roles. Thematic analysis was used to identify key themes. Three main factors emerged: organizational accountability and frustration, local autonomy and contextual responsiveness, and a culture of openness and perceived loss of control. These factors are associated with policy changes that affect operational settings and resource distribution within the RHA and influence the retention of nurses and physicians. Stakeholders in health system reforms, including governments and RHAs, must recognize that policy adjustments can have direct implications on everyday care. Participants expressed a growing disconnect from decision-making hierarchies and a perceived loss of control. Both are seen as barriers to delivering quality care. Ensuring adequate support and resources for implementing system-level changes is key to fostering professional engagement and enhancing job satisfaction.

Implantation d’un programme de formation à l’offre active de services en français auprès des futurs professionnels de la santé et des services sociaux dans une université canadienne - Dubouloz-Wilner, Claire-Jehanne; Benoît, Josée; Savard, Jacinthe (Éducation francophone en milieu minoritaire, 2019)

Lignes directrices pour la formation des futurs professionnels de la santé et du service social - Dubouloz, Claire-Jehanne; Benoît, Josée; Guitard, Paulette; Brosseau, Lucie; Savard, Jacinthe; Drolet, Marie; Kubina, Lucy-Ann; Casimiro, Lynn (Groupe de recherche sur la formation professionnelle en santé et service social en contexte francophone minoritaire, 2013)

Proposition de lignes directrices pour la formation à l’offre active des futurs professionnelles et professionnels en santé et en service social œuvrant en situation francophone minoritaire - Dubouloz, Claire-Jehanne; Benoît, Josée; Guitard, Paulette; Brosseau, Lucie; Savard, Jacinthe; Kubina, Lucy-Ann; Drolet, Marie (Reflets, 2014)
Cet article présente des lignes directrices qui guident la formation des futurs professionnelles et professionnels des services sociaux et de santé dans le but d’inclure l’apprentissage du concept d’offre active de services dans les programmes universitaires et collégiaux de formation. Ce concept de soins et de services permet de mieux répondre aux besoins des communautés francophones en situation minoritaire. Fondées sur une recension d’écrits et les résultats d’un sondage réalisé auprès du corps professoral des programmes francophones de santé et de service social au Canada, ces lignes directrices identifient les appuis nécessaires au niveau de l’institution, des facultés, des programmes d’études et du corps professoral pour cette intégration du concept d’offre active de services sociaux et de santé en français dans les programmes de formation. Mots-clés : Formation, service social et santé, offre active de services, lignes directrices

Enjeux de l’enseignement de l’offre active : proposition d’un cadre éducationnel pour les professeurs - Dubouloz, Claire-Jehanne; Benoît, Josée; Savard, Jacinthe; Guitard, Paulette; Bigney, Kate (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Dans la lignée des recherches portant sur la nécessité d’offrir aux futurs professionnels de la santé et des services sociaux une formation sur l’offre active de services sociaux et de santé dans la langue choisie par les patients, un besoin de formation pour les professeurs de ces disciplines s’est également fait ressentir : la plupart d’entre eux semblent ne pas avoir reçu de formation sur les stratégies d’enseignement favorisant la formation des professionnels appelés à travailler auprès de communautés de langue officielle en situation minoritaire. Cela nous a poussées à examiner en quoi consisterait une éventuelle formation sur l’offre active destinée aux professeurs. Ce chapitre discute des perspectives éducationnelles de l’andragogie et présente notre cadre conceptuel éducationnel incluant la situation pédagogique, ainsi que le savoir, le savoir-faire et le savoir-être menant à un savoir-agir au sujet de l’offre active. Enfin, nous proposons une réflexion sur les enjeux particuliers de l’enseignement de l’offre active, tels qu’ils ont été dégagés d’un projet pilote d’implantation d’une formation sur l’offre active. Mots-clés : enseignement de l’offre active, communautés de langue officielle en situation minoritaire, professionnels de la santé et des services sociaux, pédagogie.

Teaching active offer: Proposal for an educational framework for professors - Dubouloz, Claire-Jehanne; Benoît, Josée; Savard, Jacinthe; Guitard, Paulette; Bigney, Kate (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Élaboration, implantation et évaluation d’une formation à l’enseignement de l’offre active pour les professeurs et formateurs d’université - Duchesne, Claire; Sauvé-Schenk, Katrine; Benoît, Josée; Dubouloz, Claire-Jehanne (Minorités linguistiques et société, 2019)
Les professeurs et les formateurs des programmes de formation dans les domaines de la santé et des services sociaux ont la responsabilité d’enseigner le concept d’offre active, ses enjeux et les comportements qui y sont associés aux futurs professionnels de ces secteurs qui travailleront auprès des populations francophones vivant en contexte minoritaire. Cet article porte sur les résultats d’une recherche-développement visant l’élaboration, l’implantation et l’évaluation d’une formation à l’enseignement de l’offre active destinée aux professeurs et aux formateurs de ces domaines. Le programme de formation mis en place sera présenté et les pistes d’amélioration découlant de son évaluation seront proposées. Finalement, la discussion soulignera l’importance de facteurs tels que le temps, l’engagement et le soutien de l’administration, la souplesse, le partage des expériences, le soutien du formateur ainsi que les perspectives d’avenir lors de l’élaboration d’un tel programme. Mots-clés : offre active, contexte linguistique minoritaire, santé et services sociaux, programme de formation, professeurs et formateurs

Le projet « Préparer le terrain » : outil de planification des services de santé primaire et de mieux-être en français au Nouveau-Brunswick - Duguay, Lise (Gouvernance, santé et minorités francophones : stratégies et nouvelles pratiques de gestion au Canada, 2007)

Préparer le terrain pour la santé en français. Rapport final - Duguay, Lise; Fortin, Pierrette; Hendriks, Edouard; Losier, Barbara; Pinet, Léo-Paul; Schofield, Aurel; St-Pierre-Ellis, Lyne; Thébeau, Marcel; Thériault, Bernadette; Vienneau, Gilles (La Société Santé et Mieux-être en français du Nouveau-Brunswick, 2007)

Multimorbidity: Exploring determinants and differences between Francophones and Anglophones in Ontario - Duong, Patrick; Batista, Ricardo; Lizotte, Mathieu; Sauvé-Schenk, Katrine; Bouchard, Louise (2024)

La multimorbidité : prévalence et déterminants chez les francophones et les anglophones de l’Ontario [affiche] - Duong, Patrick; Lizotte, Mathieu; Batista, Ricardo; Sauvé-Schenk, Katrine; Bouchard, Louise (Colloque 103 – L’offre des services de santé dans les langues minoritaires, dans le cadre du 92e Congrès de l’Acfas, 2025)

La recherche au profit d’un meilleur accès aux services de santé en français [numéro thématique] - Dupuis-Blanchard, Suzanne; Vézina, Sylvain (Minorités linguistiques et société / LinguisticnMinorities and Society, 2015)

Leçons apprises sur la navigation des services de santé en français - Entité de planification des services de santé en français pour les régions de Waterloo, Wellington, Hamilton, Niagara, Haldimand, Brant (2019)

L'accessibilité des services sociaux et de santé chez les minorités de langue officielle du Canada et les facteurs influant sur leur accès : une étude de portée - Éthier, Alexandra; Carrier, Annie (Minorités linguistiques et société, 2022)
Les minorités de langue officielle (MLO) du Canada rencontrent des difficultés d’accès aux services sociaux et de santé (SSS). Or, il n’existe aucun portrait exhaustif des services concernés par ces difficultés et des facteurs (facilitateurs et barrières) qui modulent leur accès. Ainsi, le but de cette étude était de décrire l’accessibilité des SSS et d’identifier les facteurs influant sur l’accès aux SSS pour les MLO canadiennes. Une étude de portée dans neuf banques de données combinée à une stratégie élargie a permis d’inclure 74 documents. Les SSS sont généralement insuffisants pour les MLO. De plus, 15 facteurs (8 facilitateurs, 11 barrières) ont été identifiés. Enfin, 26 connexions (une parmi les facilitateurs, 25 parmi les barrières) ont été notées, complexifiant l’accès aux SSS pour les MLO. Intervenir pour favoriser l’accès aux SSS des MLO pourrait être bénéfique à l’ensemble des populations canadiennes, étant donné la présence de barrières communes entre ces groupes. Mots-clés : services sociaux et de santé, minorité anglophone, minorité francophone, facilitateurs, barrières

L'intervention du gouvernement fédéral canadien en matière de droits linguistiques dans le secteur de la santé - Farley, Roger; Guillemette, Roger; Rivest, François (2015)

Active offer of health services in French in Ontario: Analysis of reorganization and management strategies of health-care organizations - Farmanova, Elina; Bonneville, Luc; Bouchard, Louise (The International Journal of Health Planning and Management, 2018)
The availability of health services in French is not only weak but also inexistent in some regions in Canada. As a result, estimated 78% of more than a million of Francophones living in a minority situation in Canada experience difficulties accessing health care in French. To promote the delivery of health services in French, publicly funded organizations are encouraged to take measures to ensure that French-language services are clearly visible, available, easily accessible, and equivalent to the quality of services offered in English. Objective This study examines the reorganization and management strategies taken by health care organizations in Ontario that provide health services in French. Methods Review and analysis of designation plans of a sample of health care organizations. Results Few health care organizations providing services in French have concrete strategies to guarantee availability, visibility, and accessibility of French-language services. Conclusions Implementation of the active offer of French-language services is likely to be difficult and slow. The Ontario government must strengthen collaboration with health care organizations, Francophone communities, and other key actors participating in the designation process to help health care organizations build capacities for the effective offer of French-language services.

Success strategies for linguistically competent healthcare: The magic bullets and cautionary tales of active offer of French-language health services in Ontario - Farmanova, Elina; Bouchard, Louise; Bonneville, Luc (Healthcare Quaterly, 2018)
An active offer of French-language health services (FLHS) was introduced in several Canadian provinces to help create an environment that will anticipate the needs of Francophones in their community and will stimulate the demand for services in French. For the active offer to be implemented, changes in how health services are organized and managed at both organizational and system levels must be introduced. In this perspective paper, we identify several success strategies and potential pitfalls with regards to the implementation of the active offer of FLHS primarily at the level of healthcare organization. Our recommendations are based on a recent health services research study exploring reorganization and management strategies for the delivery of the active offer of FLHS in Ontario and insights from a focus group with healthcare administrators conducted as part of this research. We propose a "wrap-around strategy" called organizational health literacy to help reorient organizational culture and improve management and sustainability of the active offer of FLHS. These strategies have relevance for advocates and professionals working to promote an active offer of FLHS, including healthcare administrators, human resource professionals, quality-improvement specialists and others.

Pour un meilleur accès à des services de santé en français. Étude coordonnée par la Fédération des communautés francophones et acadienne (FCFA) du Canada pour le compte du Comité consultatif des communautés francophones en situation minoritaire (CCCFSM) - Fédération des communautés francophones et acadienne du Canada (2001)

Services de santé dans la langue officielle du patient : liens avec la proximité, la région et les facteurs sociodémographiques - Fernandes, Daphné (Regards sur la société canadienne, 2025)
À l’aide des données tirées de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 et de la Base de données ouverte sur les établissements de soins de santé, la présente étude examine l’incidence de la proximité des établissements de santé, et d’autres facteurs régionaux et sociodémographiques, sur l’accès à des soins dans la langue de choix de la population de langue officielle en situation minoritaire au Canada. Dans cet article, les soins en concordance linguistique se rapportent aux personnes qui reçoivent des services de santé dans la langue officielle de leur choix (français ou anglais). L’analyse porte sur les adultes de 18 ans et plus vivant dans différentes régions du Canada.

Health services in a patient’s own official language: Associations with proximity, region and sociodemographic factors - Fernandes, Daphné (Insights on Canadian Society, 2025)
Using data from the 2022 Survey on the Official Language Minority Population and the Open Database of Healthcare Facilities, this study examines how distance to health care facilities, alongside regional and sociodemographic factors, relates to access to language-concordant care for the official language minority population in Canada. In this article, language-concordant care refers to individuals receiving health care services in their preferred official language (English or French). The analysis focuses on adults aged 18 and older living across Canada.

Exploration of English language program undergraduate nursing students’ attitudes toward the risks of English-French language discordance and their implementation of the active offer of French language health services in Ontario [master's thesis, University of Ottawa] - Ford, Amy (University of Ottawa, 2018)
As has been reported in Canadian research on the experiences of Francophone patients and Francophone health professionals, active offer is not common or well performed in the Ontario healthcare system (Bernier, 2009; Boileau, 2016; Bouchard & Desmeules, 2013; Drolet et al., 2014; Hien & Lafontant, 2013). This descriptive quantitative research explored the self-reported awareness and implementation of the active offer concept during clinical placements by English language program 4th year undergraduate nursing students. A total of 69 participants were recruited in April 2017 to complete a paper or online-based survey. The survey consisted of questions on French language abilities, awareness of the patient safety risk of language discordance, communication experiences with Francophone patients and opinions of the role of the nurse, healthcare organizations and universities in the implementation of active offer. The participating nursing students reported little knowledge and training for implementing active offer during clinical settings. Despite the lack of preparation, the majority of them (92%) reported caring for a Francophone patient at least once with 25% doing that eight times or more during their clinical placements. More than 84% reported finding a way to communicate with Francophone patients in French, by speaking to them in French themselves or by asking Francophone colleagues, a professional interpreter or the patients’ family to interpret for them. Study recommendations include training nursing students during their undergraduate studies about the patient safety risks of language discordance, active offer and how to implement it. All English program nursing students should also be taught how to access and work with a professional interpreter. Those with French language skills should be encouraged to take healthcare specific language training. New research should be done to explore communication between English language program nursing students and Francophone patients to identify if it is safe and adequate from both the student and the patient’s point of view.

Analyse des retombées des fonds de recherche du CNFS - Volet université d'Ottawa, période 2013-2020 - Forest, Mariève (Consortium national de formation en santé - Volet Université d'Ottawa, 2020)

Évaluation des besoins des francophones et des Acadiens de la région de Saint-Jean pour un service de navigation - Forest, Mariève (Réseau santé en français de Terre-Neuve-et-Labrador, 2019)

mobilisation collective pour une santé en français en ontario. closm santé - Forest, Mariève; Gilbert, A.; Bouchard, Louise (Le moment Monfort dans la francophonie canadienne, 2024)

Autonomie, vitalité et identité des communautés en situation minoritaire : proposition d’un cadre conceptuel - Forgues, Éric (Revue internationale d’études canadiennes, 2010)
Quels facteurs contribuent à la vitalité linguistique d’une communauté en situation minoritaire et lui assurent les conditions propres à favoriser sa reproduction linguistique et culturelle? Nous nous proposons de présenter un modèle conceptuel susceptible de répondre à cette question. Selon ce modèle, trois facteurs sont au fondement de la reproduction linguistique d’une communauté en situation minoritaire : la gouvernance, l’identité et la vitalité, avec comme point pivot, la société civile et l’espace public. Cet article présente non seulement la fonction de ces facteurs au sein des communautés, mais les sous-fonctions qui découlent de leurs interrelations, tels que la lutte pour la reconnaissance, le droit, la complétude institutionnelle, l’engagement social et l’expression identitaire publique et privée. Ce modèle peut être utile pour saisir, d’un point de vue global, les composantes de la reproduction des communautés en situation minoritaire, pour déterminer celles qui la compromettent et, ainsi, envisager des pistes d’action.

La gouvernance des communautés francophones en situation minoritaire et le partenariat avec l’État - Forgues, Éric (Politique et Sociétés, 2010)
Nous abordons ici des enjeux que pose le partenariat entre les organismes communautaires francophones en situation minoritaire (CFSM) et l’État fédéral canadien. S’il semble répondre aux aspirations des communautés concernant la prise en charge de leur développement, en favorisant notamment une démarche fondée sur le principe de la gouvernance partagée, ce partenariat comporte malgré tout des exigences administratives qui paraissent tempérer l’autonomie et la libre gouvernance des CFSM. La participation des organismes francophones à l’élaboration et à la mise en oeuvre des politiques publiques s’accompagne d’une bureaucratisation de leurs activités communautaires et d’une réévaluation de leurs structures de représentation. Tenus de représenter plus formellement l’intérêt général de la communauté et de collaborer directement avec l’État pour lui permettre d’atteindre ses objectifs, ils sont poussés à une action qui se heurte, constate-t-on, à de nouveaux impératifs de légitimité. Ces derniers ont pour effet de remettre en question l’arrangement corporatiste qui s’est établi entre eux et l’État. C’est cet enjeu de légitimité qui pèse sur le nouveau mode de gouvernance des CFSM que nous avons voulu porter au jour dans notre recherche, dont nous présentons quelques éléments dans le présent article.

Offering health services in French: Between obstacles and favourable factors in Anglophone hospital settings - Forgues, Éric; Bahi, Boniface; Michaud, Jacques (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Offre de services de santé en français : entre obstacles et facteurs favorables en milieu hospitalier anglophone - Forgues, Éric; Bahi, Boniface; Michaud, Jacques (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé Notre chapitre vise à mettre en relief les facteurs sociaux et organisationnels qui favorisent l’offre de services de santé en français par des professionnels travaillant dans des établissements de santé majoritairement anglophones. Il présente une perspective sociologique qui invite les intervenants à tenir compte de la complexité de l’environnement socio-organisationnel dans lequel pratiquent les professionnels de la santé. Ainsi, leurs compétences linguistiques ne suffisent pas à assurer pareille offre. L’engagement de la haute direction et de ses gestionnaires, la gestion des services et des ressources humaines, les relations de travail, la disponibilité de la main-d’oeuvre bilingue, le contexte juridique et politique sont, entre autres facteurs, des éléments à considérer afin de comprendre dans tous ses aspects la prestation de services de santé en français. Plus largement, ils renvoient nécessairement aux rapports sociaux qu’entretiennent les anglophones et les francophones. Mots-clés : services de santé, environnement socio-organisationnel, droits linguistiques, professionnels de la santé.

L’offre de services de santé en français en contexte francophone minoritaire - Forgues, Éric; Bahi, Boniface; Michaud, Jacques; Deveau, Kenneth; Boudreau, Jonathan; St-Onge, Sylvain (Institut canadien de recherche sur les minorités linguistiques, 2011)

50 ans de législation en matière de langues officielles au Canada : bilan et perspectives - Forgues, Éric; Donovan, Patrick; Labelle Eastaugh, Érik; O’Donnell, Lorraine (Minorités linguistiques et société, 2021)

50 Years of Legislation Concerning Official Languages in Canada: Review and Prospects - Forgues, Éric; Donovan, Patrick; Labelle Eastaugh, Érik; O’Donnell, Lorraine (Minorités linguistiques et société, 2021)

Liminaire: Les enjeux reliés à la santé des communautés francophones en situation minoritaire - Forgues, Éric; Guignard Noël, Josée; Landry, Rodrigue (Francophonies d’Amérique, 2009)

De l’émergence à la consolidation. L’état de santé des francophones en situation minoritaire - Forgues, Éric; Guignard Noël, Josée; Nkolo, Christiane; Boudreau, Jonthan (Consortium national de formation en santé et Institut canadien de recherche sur les minorités linguistiques, 2009)

L’accès aux services de santé en français et leur utilisation en contexte francophone minoritaire. Rapport final - Forgues, Éric; Landry, Rodrigue (Institut canadien de recherche sur les minorités linguistiques et Société Santé en français, 2014)

Qui sont les francophones ? Analyse des définitions selon les variables du recensement de 2001 - Forgues, Éric; Landry, Rodrigue; Boudreau, Jonathan (Institut canadien de recherche sur les minorités linguistiques et Consortium national de formation en santé, 2009)

L'effectivité des lois linguistiques dans le secteur de la santé - Forgues, Éric; Maillet, Stéphanie (Minorités linguistiques et société, 2024)
Cet article découle d’une étude qui problématise le concept d’effectivité des lois linguistiques. Dans cette étude, nous cherchions à mieux comprendre les dimensions juridiques, sociales, organisationnelles et psychologiques qui peuvent agir sur l’effectivité des lois linguistiques dans le secteur de la santé dans les provinces du Canada qui disposent de telles lois. Sachant que les professionnels de la santé sont en première ligne pour offrir des services en français, nous avons analysé leurs perceptions en ce qui concerne divers aspects pouvant influencer l’offre de services en français. Les résultats montrent que des différences souvent significatives s’observent entre les répondantes et les répondants anglophones et francophones et ceux qui oeuvrent dans des hôpitaux anglophones et francophones. Les résultats révèlent également que des efforts doivent se poursuivre pour atteindre une effectivité accrue, tout en offrant des pistes pour mieux orienter ces efforts. Mots-clés : effectivité des lois linguistiques, santé en français, francophonie, langue de service, minorités linguistiques

L'effectivité des lois linguistiques dans le secteur de la santé. Rapport - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

L'effectivité des lois linguistiques dans le secteur de la santé. Sommaire - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

Prévalence de la dépression majeure chez les arthritiques des populations canadiennes : étude comparative entre anglophones majoritaires et francophones en situation linguistique minoritaire - Fotsing, Salomon; Nzokem, Aubain H.; Grenier, Jean; Imbeault, Pascal; Batal, Malek; Bouchard, Louise; Chomienne, Marie-Hélène (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectif La santé mentale et l’arthrite sont deux maladies reconnues comme étant des enjeux majeurs en santé publique. La situation minoritaire des francophones est reconnue comme un déterminant de la santé. L’objectif de cette étude est de déterminer la prévalence de la dépression majeure chez les arthritiques adultes des populations francophones minoritaires comparativement à la majorité anglophone. Méthode Analyse secondaire de l’ESCC (fusion de 2003 (cycle 2.1), 2005 (cycle 3.1), 2007 (cycle 4.1), 2008 et 2009) excluant le Québec. La variable langue a été construite selon un algorithme pré-existant réunissant la langue maternelle, de conversation, d’entrevue et de préférence. La dépression majeure était définie selon les critères du DSM IV. La présence ou non d’arthrite était une variable auto-rapportée. Les prévalences et rapports de cotes pour la dépression dans la population arthritique ont été calculés et ajustés en fonction de divers facteurs (socioéconomiques, isolement social, accès aux services de santé). Résultats L’étude identifiait 159 426 anglophones et 10 658 francophones. Parmi les sujets avec arthrite (27 %), la prévalence de la dépression était de 8,5 % et de 8,4 % chez les francophones et les anglophones, respectivement; chez les hommes, les anglophones étaient plus à risque de faire une dépression que les francophones: OR=2,36 (IC 95%: 2,07-2,70) c. OR=1,87 (IC 95%: 1,20-2,91). Cette tendance ne se retrouvait pas chez les femmes. Conclusion Notre échantillon démontre que dans une population arthritique, la dépression semble toucher plus particulièrement les hommes anglophones. Cependant il faut souligner la petite taille de l’échantillon.

French-language health services in Canada: The state of the law - Foucher, Pierre (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Services de santé en français au Canada : l’état du droit - Foucher, Pierre (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
L’analyse du cadre juridique de l’offre active de soins de santé en français au Canada abordera ses dimensions constitutionnelles et législatives. La première partie explore la dimension constitutionnelle de la question, dans son aspect fédéraliste autant que par rapport à la Charte canadienne des droits et libertés. Par la suite, il est fait mention des lois linguistiques applicables au gouvernement fédéral, dans les provinces et dans les territoires. L’étude démontre l’asymétrie de la situation juridique et les difficultés qu’elle engendre. Mots-clés : cadre juridique, droit, soins de santé, Charte canadienne des droits et libertés, Constitution canadienne.

Linguistic variables: A necessity for health services planning tailored to the needs of Francophones. Current Status - French Language Heatlh Services Network of Eastern Ontario (Current Status, 2012)

Un aperçu de la santé et de ses déterminants au Nouveau-Brunswick d’après les données des Enquêtes sur la santé des collectivités canadiennes (ESCC) 2001-2003-2005 - Gaboury, Isabelle; Bouchard, Louise (Université d'Ottawa, 2008)

Les données administratives et d’enquêtes sur l’état de santé et l’accès aux services des communautés francophones en situation minoritaire : potentiel d’analyse et état de situation. Rapport - Gaboury, Isabelle; Guignard Noël, Josée; Forgues, Éric; Bouchard, Louise (Consortium national de formation en santé, 2009)

Access to health care services and self-perceived health of canada's official-language minorities [master's thesis, University of Ottawa] - Gagnon-Arpin, Isabelle (University of Ottawa, 2011)

Les services de santé en français en Ontario: Offre - demande - utilisation - Gagnon-Arpin, Isabelle; Bouchard, Louise (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, 2011)

Accès et utilisation des services de santé en langue minoritaire - Gagnon-Arpin, Isabelle; Bouchard, Louise; Leis, Anne; Bélanger, Mathieu (La vie dans une langue officielle minoritaire au Canada, 2014)

Access and use of health care services in the minority language - Gagnon-Arpin, Isabelle; Bouchard, Louise; Leis, Anne; Bélanger, Mathieu (Life within an official language minority in Canada, 2014)

Un aperçu de la santé et de ses déterminants dans la région Champlain de l’Est de l’Ontario d’après les données des Enquêtes sur la santé dans les collectivités canadiennes (ESCC) 2001-2003-2005-2007 - Gagnon-Arpin, Isabelle; Gaboury, Isabelle; Bouchard, Louise (Université d'Ottawa, Réseau de recherche interdisciplinaire sur la santé des francophones en contexte minoritaire au Canada, Institut de recherche sur la santé des population, 2009)

Le surplus de poids chez les francophones et les anglophones - Gagnon-Arpin, Isabelle; Makvandi, Ewa; Imbeault, Pascal; Batal, Malek; Bouchard, Louise (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectifs Des études récentes rapportent une prévalence d’embonpoint et d’obésité plus élevée chez les francophones en situation linguistique minoritaire en comparaison à la majorité anglophone du Canada. L’objectif de l’étude est de vérifier si l’appartenance au groupe linguistique minoritaire s’ajoute aux déterminants sociaux du surplus de poids. Méthode Les statistiques descriptives (n=128 986), provenant de cinq cycles de l’Enquête sur la santé dans les collectivités canadiennes, ont été croisées en fonction de la langue et du sexe des individus. Deux modèles de régression logistique multivariée, pour les hommes et pour les femmes, ont permis de tester l’association entre le surplus de poids et la langue en contrôlant pour les déterminants socioéconomiques et comportementaux. Résultats La prévalence du surplus de poids est plus élevée chez les francophones que chez les anglophones de l’Ontario, bien que cette différence ne soit plus significative lorsque le modèle est ajusté pour les caractéristiques socioéconomiques et comportementales. Néanmoins, les francophones sont plus âgés, moins éduqués et vivent davantage en milieu rural que leurs homologues anglophones, un contexte qui les rend plus vulnérables. Conclusion L’étude vient réaffirmer le rôle des déterminants sociaux et comportementaux dans la prévalence du surplus de poids. Bien que la langue n’influence pas directement le surplus de poids, compte tenu de la réalité socioéconomique de la minorité francophone, représentée en plus grande proportion dans les strates de la population plus vulnérable au surplus de poids, l’appartenance à un groupe minoritaire devrait interpeller les planificateurs de la santé.

Portraits socio-sanitaires des communautés francophones de l'Ontario | Demographic and health profiles of Ontario's Francophone communities - Gagnon-Arpin, Isabelle; Sedigh, Golnaz; Bouchard, Louise (Alliance des réseaux ontariens de santé en français, 2011)

Une formation en service social à distance en français : le modèle de l’Université Laurentienne - Garceau, Marie-Luce; Marcoci, Gabriela (Reflets, 2015)

Examining the geographic distribution of French-speaking physicians in Ontario - Gauthier Alain P.; Timony Patrick E.; Wenghofer, Elizabeth. F. (Canadian Family Physician, 2012)
Abstract: Objective: To determine how many physicians in Ontario express a proficiency in providing services in the French language, and to assess the geographic distribution of such physicians. Design: Population-based analysis of the 2007 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey. Setting: Ontario. Participants: A total of 22688 GPs, FPs, and other specialists certified by the College of Family Physicians of Canada and the Royal College of Physicians and Surgeons of Canada who responded to the survey. Main outcome measures: First official language spoken and languages of competency to conduct practice. Results: The physician-to-patient ratio by first official language spoken is 1 physician per 138 Francophone patients in Ontario. There is 1 French-speaking GP or FP for every 297 Francophone patients, and most French-speaking physicians are located in southern Ontario (91.4%), at a ratio of 1 physician per 111 Francophone patients. The most promising French-speaking physician–to–Francophone patient ratios are found in southern Ontario (1:248 for GPs and FPs, and 1:202 for other specialists) and in urban Ontario (1:266 for GPs and FPs, and 1:209 for other specialists). Conclusion: Clearly, there is a promising number of physicians, relative to the amount of French-speaking residents in Ontario, who identified a competency in offering services in French. However, while the number of physicians who indicated a self-assessed competency to deliver health services in French is promising, it is the maldistribution of such services that is of concern. Thus, efforts must be made to attract French-speaking physicians to areas where there is the greatest demand, particularly in the northern part of the province. Résumé Objectif: Déterminer combien de médecins ontariens se disent compétents pour fournir, des services en français et vérifier la distribution géographique de ces médecins. Type d’étude: Analyse démographique du rapport de 2007 sur la réinscription annuelle à l’Ordre des médecins et chirurgiens de l’Ontario. Contexte: L’Ontario. Participants: Un total de 22 688 omnipraticiens (OP), MF et autres spécialistes diplômés du Collège des médecins de famille du Canada et du Collège royal des médecins et chirurgiens du Canada qui ont répondu à l’enquête. Principaux paramètres à l’étude: Première langue officielle parlée et langues de compétence pour la pratique. Résultats: En Ontario, le rapport médecin/patient dans le cas de la première langue officielle parlée est de 1 médecin pour 138 patients francophones. On compte un OP ou MF francophone pour 297 patients francophones et les médecins francophones sont localisés pour la plupart (91,4%) dans le sud de l’Ontario, où on observe 1 médecin pour 111 patients francophones. C’est dans le sud de l’Ontario que le rapport médecin francophone/patient francophone est le plus favorable (1/248 pour les OP et les MF, et 1/1202 pour les autres spécialistes) et dans les milieux urbains (1/266 pour les OP et les MF et 1/1209 pour les autres spécialistes). Conclusion: Il est certain qu’en Ontario, il y a un nombre encourageant de médecins qui, par rapport au nombre de résidents francophones, se sont dits compétents pour offrir des services en français. Malgré ce rapport favorable, c’est la mauvaise distribution de ces services qui est préoccupante. Il faudrait donc s’efforcer d’attirer des médecins francophones dans les régions où la demande est la plus forte, notamment dans le nord de la province.

Barriers and strategies to offering health services to French-speaking patients: Perspectives from family physicians in Northeastern Ontario - Gauthier, Alain P.; Timony, Patrick E. (Research in FOCUS on Research [Centre for rural and northern health research], 2015)

Les obstacles et les stratégies dans les services de santé offerts aux patients francophones : perspectives des médecins de famille dans le Nord-Est de l'Ontario - Gauthier, Alain P.; Timony, Patrick E. (FOCUS sur la recherche [Centre de recherche en santé dans les milieux ruraux et du nord], 2015)

Strategies for improved French-language health services: Perspectives of family physicians in northeastern Ontario - Gauthier, Alain P.; Timony, Patrick E.; Serresse, Suzanne; Goodale, Natalie; Prpic, Jason (Canadian Family Physician, 2015)

Compétences linguistiques et qualité de services. Argumentaire pour des services de soins de santé en français de qualité - Gauthier, Hubert; Reid, Marc-André (Conseil communauté en santé en français du Manitoba, 2012)

Les services de santé en français pour les communautés francophones et acadiennes en situation minoritaire du Canada : bonification du schéma du CCCFSM (2001) - Giguère, Louis (Nouvelles perspectives en sciences sociales, 2013)
Nous bonifions le schéma du CCCFSM (2001) sur le développement des services de santé en français pour les communautés francophones et acadiennes en situation minoritaire (CFASM) du Canada à l’aide de données probantes recueillies lors du recensement national de 2006. Notre approche consiste à choisir, à partir d’une procédure statistique, une mesure de masse critique de francophones qui met en évidence un schème cohérent d’offre et de demande de services de santé sur une base géographique juridictionnelle. L’offre et la demande sont plus grandes là où la vitalité linguistique des CFASM est plus grande. Dans l’ensemble, l’offre tombe en deçà de la demande; ceci suggère une demande latente de services en français et est consistant avec les études d’offre active des services en français dans les CFASM. Nos résultats sont aussi consistants avec les trois phases évolutives de sensibilisation, de structuration et de consolidation proposées par le CCCFSM (2001). Nous discutons des limitations méthodologiques et en tirons des leçons pour les réseaux de santé francophones des CFASM. Mots-clés : CFASM, CLOSM, communauté francophone, minoritaire, vitalité linguistique, langues officielles, réseaux de santé, services en français, offre et demande

Validation d’un schème national sur le développement des services de santé pour les communautés francophones et acadiennes en situation minoritaire au Canada : arrimage à des assises théoriques et modélisation - Giguère, Louis (Nouvelles perspectives en sciences sociales, 2014)
Nous avons présenté (Giguère, 2013), pour les communautés francophones hors Québec (CFASM), un schème juridictionnel national qui illustre l’offre et la demande de services de santé en français en fonction d’une masse critique de francophones qui reflète la vitalité linguistique de ces communautés. Nous corroborons ce schème à l’aide de procédures statistiques dont l’une identifie une forte association entre le rapport offre/demande (un ratio) et des facteurs qui reflètent la cohérence linguistique et culturelle des deux communautés de langue officielle. Ce résultat est cohérent avec le cadre de vitalité linguistique déjà proposé (Giguère, 2013), et il fait écho au travail de terrain de Forgues, Bahi et Michaud (2011) et aux modèles psycho-langagiers et d’autonomie culturelle de Deveau, Landry et Allard (2009), de Landry, Allard et Deveau (2007, 2008) et de Landry (2012). Nous modélisons le développement des services de santé en français pour les CFASM dans un cadre national structurant qui est cohérent avec ces assises empiriques et théoriques. Cette modélisation suggère deux approches stratégiques distinctes mais complémentaires pour favoriser le développement des services de santé en français. Mots-clés : CFASM, communauté francophone, minoritaire, développement communautaire, vitalité langagière, réseautage, schéma CCCFSM, assises théoriques, modélisation en diagramme de phase

Le potentiel d'offre et de demande de Services médicaux et diagnostiques dans la langue de communautés minoritaires : où se situe le français en Colombie-Britannique? - Giguère, Louis; Conway, Brian (Reflets, 2014)
Une étude comparative du potentiel de services médicaux dans les langues minoritaires de Colombie-Britannique révèle que des médecins non-francophones parlant français génèrent une retombée linguistique qui amplifie l’offre potentielle de services de santé et de services sociaux en français de façon dramatique. Ce mécanisme structurant s’appliquerait aux autres professions de la santé et des services sociaux, partout au Canada et il serait plus prononcé plus le contexte est minoritaire. Les communautés francophones doivent faire plus pour identifier, engager et outiller les professionnels et professionnelles « francophiles » et elles doivent élaborer une logique d’équité innovatrice pour dégager le potentiel d’offre de services de santé et de services sociaux en français dans un contexte multilingue. Mots-clés : CFASM, CLOSM, médecins parlant français, minorités linguistiques, équité, services d’interprétation, offre et demande

L'environnement et la vitalité communautaire des minorités francophones : vers un modèle conceptuel - Gilbert, A.; Langlois, A.; Landry, R.; Aunger, A. E. (Territoires francophones : études géographiques sur la vitalité des communautés francophones du Canada, 2010)

Les discours sur la santé des organismes franco-ontariens : du rapport Dubois à la cause Montfort - Gilbert, Anne; Kérisit, Michèlle; Dallaire, Christine; Coderre, Cécile; Harvey, Jean (Reflets, 2005)

L’environnement et la vitalité communautaire des minorités francophones : vers un modèle conceptuel - Gilbert, Anne; Langlois, André; Landry, Rodrigue; Aunger, Edmund (Francophonies d'Amérique, 2005)

L’ambition territoriale dans le dossier de la santé en français - Gilbert, Anne; Lefebvre, Marie; Bouchard, Louise (Francophonies d’Amérique, 2010)
Dix ans se sont écoulés depuis le jugement Montfort, qui consacrait l’Hôpital comme une composante essentielle de la vitalité des communautés francophones en situation minoritaire. Jusqu’à quel point cette reconnaissance du droit à un service en français, accessible dans des établissements localisés dans les milieux dans lesquels la minorité évolue, a-t-elle mené à une ambition plus territoriale chez les intervenants francophones ? L’analyse des propos tenus par 38 participants à un exercice de cartographie conceptuelle sur l’avenir des services de santé en français en Ontario révèle qu’ils ne s’aventurent pas très loin sur le terrain des modalités de l’édification d’un véritable territoire francophone en santé. L’institution est évoquée, mais davantage comme un projet appartenant à un horizon lointain que comme un enjeu actuel. En guise de conclusion, les auteures se sont interrogées sur les effets d’une telle vision sur l’avenir des services de santé en français.

La pratique de la physiothérapie en milieu minoritaire : mon expérience en tant que francophone à l’Hôpital de Hamilton - Goulet, Anik (Reflets, 2002)

Investir dans notre avenir 2018-2023. Plan d'action pour les langues officielles - Gouvernement du Canada (Plan d'action pour les langues officielles, 2018)

Investing in our future 2018-2023. Action plan for official languages - Government of Canada (Action plan for official languages, 2018)

Comorbidités entre maladies chroniques et problèmes de santé mentale fréquents : différences entre francophones et anglophones - Grenier, Jean; Gosselin, Dominique; Greenman, Paul. Samuel; Chomienne, Marie-Hélène; Imbeault, Pascal; Batal, Malek; Bouchard, Louise (Psy-Cause, 2016)

L’usage de technologies de santé pour accéder à des soins virtuels : une enquête exploratoire pour mieux comprendre les besoins et attentes des francophones de l’Ontario - Grosjean, Sylvie; Giguère, Lauriane; Lessard, Lysanne; Dionne, Émilie (Minorités linguistiques et société, 2024)
Dans cet article, nous présentons les résultats d’une étude visant à répondre à la question suivante : quels usages des technologies numériques de santé sont jugés accessibles et acceptables par les francophones de l’Ontario? Les résultats de cette enquête exploratoire montrent que l’accessibilité et l’acceptabilité des technologies de santé pour soutenir l’offre de soins virtuels chez les francophones de l’Ontario dépendent de plusieurs facteurs liés : a) à leur utilité perçue, b) à leur valeur sociale et leur intégration dans des usages existants, et c) à l’offre des technologies accessibles en français – de leur conception au support offert pour en accompagner les usages. Les résultats de l’étude nous invitent à considérer les questions à la fois communicationnelles (concordance linguistique patient/technologie), organisationnelles (intégration dans des pratiques et structures existantes) et éthiques qu’implique l’usage des technologies de santé visant à soutenir l’offre de soins virtuels pour les francophones de l’Ontario. Mots-clés : soins virtuels, technologies numériques de santé, acceptabilité, francophones, Ontario

Services de santé pour la communauté franco-ontarienne : feuille de route pour une meilleure accessibilité et une plus grande responsabilisation - Groupe de travail sur les services de santé en français (Ministère de la Santé et des Soins de longue durée de l'Ontario, 2005)

Populations de langue officielle en situation minoritaire selon différentes méthodes de dénombrement. Rapport - Guignard Noël, Josée; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2020)

Qui sont les francophones ? Analyse des définitions selon les variables du recensement. Mise à jour : recensement de 2011 - Guignard-Noël, Josée; Forgues, Éric; Landry, Rodrigue (Institut canadien de recherche sur les minorités linguistiques, 2014)

Portrait des services bilingues offerts au sein des hôpitaux canadiens. Rapport - Guignard Noël, Josée; LeBlanc, J.; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2016)

Étude de référence sur les services bilingues au sein des établissements de santé canadiens - Guignard Noël, Josée; LeBlanc, Joannie; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2016)

La contribution des centres scolaires communautaires à la santé des francophones vivant en milieu minoritaire - Harrison, Suzanne (Francophonies d'Amérique, 2009)
La santé des francophones vivant en milieu minoritaire est un sujet d’actualité. Récemment, les centres scolaires communautaires (CSC) ont commencé à explorer leur contribution en cette matière, puisque traditionnellement, leurs activités portaient sur les besoins culturels, éducatifs et sociaux des francophones. Cet article présente les résultats d’une étude qui examinait la capacité des CSC à augmenter le contact avec la langue française dans huit domaines de vie. Les centres ne semblent pas encore contribuer à l’augmentation des contacts avec la langue française dans le domaine de la santé. Toutefois, des exemples révèlent qu’ils peuvent influencer, entre autres, la santé physique (cours d’aérobie, sports collectifs) et psychologique (cours sur la gestion du stress).

Access to Health and Social Services in Official Languages (Reaffirmation) - Health Standards Organization (2022)
The standard CAN/HSO 11012:2018 (R2022) is a reaffirmation of CAN/HSO 11012:2018 Access to Health and Social Services in Official Languages. The standard provides guidelines of excellence to help organizations aim to improve access to health and social services across the continuum of care in Canada’s two official languages – French and English. The standard content is grouped into five sections: - Establishing the Active Offer of Services - Clinical Research - Governance and Leadership - Workforce - Quality Assurance

Client and family information sheet: Access to health and social services in Official Languages Standard - Health Standards Organization (2018)
The CAN/HSO 11012:2018 Access to Health and Social Services in Official Languages Standard provides guidelines of excellence to help organizations aim to improve access to health and social services across the continuum of care in Canada’s two official languages – French and English. This information sheet explains what should be expected from health and social service organizations applying this standard.

Accès aux services de santé et aux services sociaux dans les langues officielles - Health Standards Organization / Organisation de normes en santé (2018)
La norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais.

Accès aux services de santé et aux services sociaux dans les langues officielles (confirmation) - Health Standards Organization / Organisation de normes en santé (2022)
La norme CAN/HSO 11012:2018 (R2022) est une confirmation de la norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles. Elle fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais. Le contenu de la norme comprend cinq sections : - Établissement de l’offre active de services - Recherche clinique - Gouvernance et leadership - Main-d’oeuvre - Assurance de la qualité

Feuillet d'information pour les usagers et les familles : norme sur l'Accès aux services de santé et aux services sociaux dans les langues officielles - Health Standards Organization / Organisation de normes en santé (2018)
La norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais. Ce feuillet d'information explique ce à quoi les usagers peuvent s'attendre des organismes de santé et de services sociaux qui appliquent cette norme.

Perceived importance of native language use in service encounters - Holmqvist, Jonas; Van Vaerenbergh, Yves (The Service Industries Journal, 2013)
Despite the importance of interactions in services, the role language plays in services is an under-researched field. This paper outlines for which services language is especially important. Consistent across studies in three countries (Belgium, Canada and Finland), the findings suggest that bilingual consumers find it particularly important to be served in their native language in high-involvement services. Moreover, for high-involvement services, all consumers find it important to be served in their native language. For low-involvement services, elderly consumers are less willing to switch language than young consumers. The importance of native language use did not differ between males and females.

Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada : état des lieux - Hsu, Amy. T.; Ménard, Alixe; Scott, Mary (Université d'Ottawa et Institut de recherche Bruyère, 2022)

Understanding the long-term care experience of official language minorities in Canada: An environmental scan - Hsu, Amy; Ménard, Alixe; Scott, Mary (Bruyère Research Institut, 2022)

Practice #28: Access to Resources in the Community (ARC): A social prescribing and navigation model (Ontario) - Ibrahim, Nour; Benoît, Josée; Savard, Jacinthe (2025)

Physical inactivity among Francophones and Anglophones in Canada - Imbeault, Pascal; Makvandi, Ewa; Batal, Malek; Gagnon-Arpin, Isabelle; Grenier, Jean; Chomienne, Marie-Hélène; Bouchard, Louise (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objective Leisure-time physical activity participation is influenced by various socio-demographic factors. Recent evidence suggests that being part of a minority negatively impacts an individual’s health status. The objective of this study was to compare inactive leisure-time physical activity between the Francophone minority and the Anglophone majority in Canada. Methods Data from the fusion of cycles 2.1, 3.1, 4.1, 2008 and 2009 of the Canadian Community Health Survey (CCHS) were used. The linguistic variable was determined by languages spoken at home, first language learned and still understood, language of interview, and language of preference. Leisure-time physical activity was based on a questionnaire provided during the interview. Factors associated with inactive leisure time were examined using logistic regression models. Results Francophones were more likely than Anglophones to be physically inactive in their leisure time (49.1% vs. 47.2%). A greater percentage of Francophones had poor self-perceived health, were older, were single, had lower education, had higher rate of unemployment and lived in rural areas compared to Anglophones. When these socio-demographic factors were taken into account, there were no further differences in the likelihood of being inactive between Francophones and Anglophones. Conclusion The Francophone minority in Canada is characterized by socio-demographic factors that have a negative impact on leisure-time physical activity participation.

Le rôle de l’hôpital communautaire Montfort comme pilier francophone de formation - Joanisse, Dr. John (Reflets, 2002)

La mobilisation des connaissances en santé dans les petites communautés francophones en situation minoritaire. Ses défis, ses conditions de succès - Johnson, Marc. L.; Cimon, Virginie; Dancause, Luc; Forest, Mariève (SOCIUS recherche et conseils, 2021)

Concordance et discordance linguistique : comprendre l’expérience des patients francophones chez leur médecin de famille dans le Nord de l’Ontario - Jutras, Chloé. F. (Focus sur la recherche [Centre de recherche en santé dans les milieux ruraux et du nord], 2017)

Linguistic concordance and discordance: Understanding the Francophone patient experience during a visit to their family physicians' Office in Northern Ontario - Jutras, Chloé F. (Focus on Research [Centre for rural and northern health research], 2017)

Expérience de francophones en Ontario chez leur médecin de famille : concordance et discordance linguistique - Jutras, Chloé; Gauthier, Alain P.; Timony, Patrick E.; Côté, Daniel; Kpazaï, Georges (La Revue de la Diversité de la Recherche en Santé, 2020)
Abstract : Improving health and health care can be achieved efficiently by improving the patient experience. This study’s main objective was to capture and understand the Francophone patient experience during a visit to their family physician’s office and examining the impact of linguistic concordance or discordance on this experience. Data collection method was inspired by the first two steps of the Experience Based Design approach (EBD), six focus groups were conducted in strong French communities of Northern Ontario in which a total of twenty-nine Francophones described their experience of a visit to their family physicians’ office. The Francophone patient experience is characterized by many emotions, several of which result from the presence of linguistic concordance or discordance with the physician. Linguistic discordance in a primary care setting elicits a less favorable patient experience in terms of emotions associated with comfort, accessibility, security and personal aptitude. Actively offering French language services, being mindful of patient language preferences regardless of apparent bilingualism and providing a bilingual environment in the family physician’s office (e.g. signage, forms) would favor a positive patient experience for Francophones in Ontario.

La littérat'ie en santé et les communautés francophones, minoritaires et ethnoculturelles - Kaszap, M.; Zanchetta, M. S. (Lire le monde : les littératies multiples et l'éducation dans les communautés francophones, 2009)

Recueil des outils proposés dans le guide pratique Plaidoyer pour la santé - Knaidil, Ibtissam; Chaput, Sarah (Réseau francophone international pour la promotion de la santé, 2022)

Actes du colloque : l'offre active des services sociaux et de santé en français - La Cité universitaire francophone, Université de Régina; Consortium national de formation en santé (Colloque offre active symposium, 2019)

L’application de la Loi sur les services en français (LSF) de l’Ontario aux services de santé : la problématique des Réseaux locaux d’intégration des soins de santé (RLISS) - Labelle Eastaugh, Érik (Revue générale de droit, 2019)
Depuis quelques années, le Commissaire aux services en français attire l’attention du public sur le fait que le gouvernement provincial semble être d’avis que la Loi sur les services en français (LSF) de l’Ontario ne s’applique pas à la grande majorité des services de soins de santé financés par l’État, au motif qu’ils sont principalement offerts par des entités non gouvernementales. Plus précisément, le gouvernement a apparemment conclu que la LSF ne s’applique pas aux prestataires de soins médicaux financés par les Réseaux locaux d’intégration des soins de santé (RLISS). Puisque ces derniers ne prodiguent pas eux-mêmes de tels services, les entités qu’ils financent n’opèrent donc pas « pour leur compte », au sens de cette Loi. Or, puisque la majorité du financement du système de santé public est octroyé par l’entremise des RLISS, il s’agirait là d’une lacune très importante dans l’armature des droits linguistiques du public ontarien. Et, bien que la province ait déclenché un important processus de réforme en 2019 qui cherche à modifier, voire même éliminer les RLISS, on doit donc s’attendre à ce que le gouvernement adopte la même position en ce qui concerne l’application de la LSF qu’auparavant. Le présent article a pour but d’étudier le bien-fondé de cette hypothèse. Au final, l’auteur conclut qu’elle doit être rejetée. La LSF, à titre de loi quasi constitutionnelle ayant pour objet de protéger des droits fondamentaux, s’applique à toute entité non gouvernementale qui prodigue un service public dans le cadre d’un programme ou d’une politique gouvernementale déterminée, ce qui inclut les fournisseurs de soins de santé financés par les RLISS ou par la nouvelle entité qui les remplacera. L’analyse de cette question que propose l’auteur est pertinente non seulement quant à la LSF, mais également à toute loi relative aux droits linguistiques, dont la Loi sur les langues officielles du Canada. Elle intéressera aussi les chercheurs en droits de la personne et en droit administratif. Mots-clés : Droits linguistiques, droit de la santé, droits fondamentaux, droit public et administratif, services publics, secteur privé

Minoration et santé : les formations discursives des communautés et institutions francophones à Toronto - Labrie, Normand; Chambon, Adrienne; Heller, Monica; Kanouté, Fasal; Madibbo, Amal; Maury, John (Bulletin suisse de linguistique appliquée, 2001)

Les services de santé au Canada : une perspective linguistique - Lacroix, Frédéric (L'Action nationale, 2006)

Statistics Canada data sources on official-language minorities (n°91-549-X-n°001) - Lafrenière, Sylvie (Statistics Canada, 2009)

Statistics Canada data sources on official-language minorities (n°91-549-X-n°2) - Lafrenière, Sylvie (Statistics Canada, 2013)

Autodétermination du comportement langagier en milieu minoritaire : un modèle conceptuel - Lagacé, Josée; Lefebvre, Pascal (Francophonies d’Amérique, 2005)

Improving the recruitment and retention of doctors by training medical students locally - Landry, Michel; Schofield, Aurel; Bordage, Rachel; Bélanger, Mathieu (Medical Education, 2011)
Context The global shortage of doctors is of concern. This is particularly true in French‐speaking regions of New Brunswick, Canada, where there is no medical school. Since 1981, francophone medical students from New Brunswick have been able to undertake part of their training in their province through an agreement with medical schools in another province. We studied the effects of frequency and length of exposure to the province of origin during medical training on the likelihood that a doctor will ever or currently practise medicine in that province. Methods A questionnaire was sent to 390 francophone doctors from New Brunswick to collect information on history of medical training and practice. Multivariate logistic regressions were used to identify whether exposure to New Brunswick during medical training at the undergraduate and postgraduate levels affects the likelihood of ever or currently practising in the province. Results A total of 263 doctors participated. Among family doctors, those with exposure to their province of origin in 1, 2, 3 or 4 years of undergraduate training were 2.5 (95% confidence interval [CI] 0.8–7.4), 2.5 (95% CI 0.7–8.6), 9.3 (95% CI 1.5–56.9) and 9.3 (95% CI 1.4–60.1) times more likely, respectively, to currently practise in New Brunswick than doctors who had experienced no exposure to the province during undergraduate training. Among specialty doctors, exposure to New Brunswick during undergraduate training had no effect on location of practice. Family and specialty doctors who had been exposed to New Brunswick during postgraduate residency were 5.9 (95% CI 2.3–14.9) and 3.2 (95% CI 0.9–11.6) times more likely, respectively, to practise in the province than doctors without postgraduate exposure. Conclusions Greater exposure to New Brunswick during medical training is associated with significantly better odds that doctors will be recruited to and retained in the province. Some effects are perceived for exposure during both undergraduate (most importantly in the final years) and postgraduate programmes.

Tensions linguistiques au Nouveau-Brunswick : attitudes à l’égard du bilinguisme dans le système de santé. - Landry, Michelle; Legault-Leclair, Jacob; McLaughlin, Gilbert (Minorités linguistiques et société, 2024)
Dans cet article, nous examinons les opinions des anglophones à l’égard du bilinguisme dans le système de santé. Les données proviennent d’un sondage mené par la firme Léger du 16 au 24 février 2021. Nous avons mesuré l’effet d’une série de variables sociodémographiques, de l’orientation politique et de l’accord avec un énoncé selon lequel les francophones constitueraient un groupe privilégié sur le fait d’être d’avis que les services bilingues sont suffisamment développés dans le secteur de la santé. En conclusion, les résultats indiquent que les électeurs des partis politiques conservateurs et du People’s Alliance ont en majorité tendance à estimer que le bilinguisme en santé est suffisamment développé. Les variables sociodémographiques et le fait d’affirmer que les francophones représentent un groupe privilégié ne sont pas des variables discriminantes dans notre analyse. Mots-clés : Bilinguisme, Nouveau-Brunswick, système de santé, Acadie, services en français

Autonomie culturelle, cultures sociétales et vitalité des communautés de langue officielle en situation minoritaire au Canada - Landry, Rodrigue (Minorités linguistiques et société, 2012)
Partant d’un modèle macroscopique des facteurs associés à la vitalité d’une minorité linguistique en situation intergroupe, cet article présente cinq principes expliquant comment les structures sociales s’imposent sur les vécus langagiers des membres de la minorité. Ce même modèle montre comment tant les individus que la collectivité peuvent exercer leur autonomie langagière pour contrer ce déterminisme social. Le modèle de l’autonomie culturelle est explicité et appliqué aux communautés de langue officielle en situation minoritaire (CLOSM) dans le but de faire valoir leur besoin d’autonomie institutionnelle pour assurer leur vitalité au Canada. La reconnaissance du droit à l’autonomie culturelle pourrait être un mode de légitimation des droits propres à ces communautés. Les CLOSM sont décrites comme des prolongements des deux cultures sociétales qui constituent le fondement de la dualité linguistique canadienne. Mots-clés : autonomie culturelle, culture sociétale, vitalité linguistique, droits linguistiques, minorités linguistiques

Loi sur les langues officielles et vitalité des minorités : mission impossible ou oeuvre inachevée ? - Landry, Rodrigue (Minorités linguistiques et société, 2021)
Notre article vise à déterminer les conditions nécessaires pour qu’une loi et des politiques linguistiques puissent avoir un effet réel sur la vitalité d’une minorité. L’article comprend trois parties. Premièrement, nous concluons que la Loi sur les langues officielles (LLO) a eu peu d’effet sur la vitalité des minorités de langue officielle. En deuxième partie, nous distinguons trois acteurs essentiels qui agissent sur la vitalité linguistique : la communauté d’intimité, la société civile de la minorité et l’État. De ces analyses, nous dégageons deux principes sociolinguistiques que toute législation linguistique devrait respecter si son objet est de favoriser la vitalité/revitalisation d’une minorité. Enfin, nous focalisons sur la partie VII de la LLO, la plus susceptible de favoriser la mise en oeuvre d’un aménagement linguistique planifié et global capable de respecter les deux principes sociolinguistiques, de coordonner une synergie d’action des acteurs essentiels et d’avoir un effet réel sur la vitalité des minorités. Mots-clés : Loi sur les langues officielles, vitalité ethnolinguistique, autonomie culturelle, aménagement linguistique, politiques linguistiques, droits linguistiques

Is Francophone language status associated with diffences in the health services use of rural Nova Scotians? - Langille, Donald; Rainham, Daniel; Kisely, Steve (Canadian Journal of Public Health, 2012)
L’étude a pour objet de vérifier empiriquement la validité d’un modèle théorique qui propose un système de relations liant la construction de l’identité ethnolinguistique à la satisfaction de vie, un aspect du mieux-être psychologique, et à l’autoévaluation de sa santé. Un échantillon de 8 124 élèves du secondaire, provenant de 30 conseils scolaires francophones situés à l’extérieur du Québec, a participé à l’étude. Les résultats sont conformes au modèle fondé sur la théorie de l’autodétermination, qui stipule que lorsque la construction identitaire se fait dans un contexte d’appui à des besoins psychologiques de base, elle est reliée au mieux-être psychologique de la personne. Abstract

Ma santé, en français s'il vous plaît ! Une proposition qui traite des besoins des franco-ontariens et des franco-ontariennes de Thunder Bay en ce qui a trait aux soins de santé primaires - Larouche, Jérémie (Association des Francophones du Nord-Ouest de l'Ontario, L'Accueil francophone de Thunder Bay, Réseau francophone de santé du Nord de l'Ontario, 2007)

La parole aux communautés : nous sommes là! La vitalité des communautés de langues officielles en situation minoritaire. Rapport du Comité permanent des langues officielles - Lauzon, Guy (Gouvernement du Canada, Chambre des communes 39e Législature, 1er session, 2007)

Énoncé de position commune sur l’offre active des services de santé en français en Ontario - Le Regroupement des Entités de planification des services; de santé en français de l’Ontario; et; L’Alliance des Réseaux ontariens de santé en français (Regroupement des Entités de planification des services de santé en français de l’Ontario et Alliance des Réseaux Ontariens de santé en français, 2015)

Peut-on parler d'une déshospitalisation des services ? Les soins en santé mentale de la minorité de langue officielle dans le Nord-Est ontarien - LeBel, Marie (La fin de l'asile ? Histoire de la déshospitalisation psychiatrique dans l'espace francophone au xxe siècle, 2018)

Pour un système de santé en français amélioré au Nouveau-Brunswick - Leblanc, Gino (Gouvernement du Nouveau-Brunswick, 2010)

Toward an improved health system in french in New Brunswick - Leblanc, Gino (New-Brunswick Government, 2010)

Rapport de l’évaluation sommative du Projet de formation et de recherche du Consortium national de formation en santé - LeBlanc, Pierre (Conseillers en gestion PRAXIS, 2008)

La gouvernance communautaire dans la fourniture de services de santé en milieu minoritaire francophone en Ontario : le cas du Centre de santé communautaire de Kapuskasing et région - Leblanc, Stéphanie (Université d’Ottawa, 2015)
L’offre des services de santé dans la langue d'une population est un élément essentiel à l'amélioration des conditions de santé de cette population. C’est pourquoi le manque de services de santé francophones de qualité en Ontario crée des désavantages important pour la population francophone en situation minoritaire. Cependant, une nouvelle initiative est apparue depuis quelques années afin de combler ce manque de services de santé francophone en Ontario, tout en donnant aux communautés le pouvoir de gestion de leurs services. Cette initiative est celle des centres de santé communautaires francophones. Regroupant sous un même toit des services de soins primaires et toute une gamme de services de promotion de la santé et de développement communautaire, les centres de santé communautaires francophones offrent un modèle de soins de santé complet et unique à chaque région. L’étude de cas qui suit permet d’explorer le rôle de la gouvernance communautaire comme facteur important au succès des centres de santé communautaires francophones en Ontario.

Perceptions des communautés de langue officielle en situation minoritaire : accès aux services de santé dans la langue officielle de son choix. Rapport final - Léger (Santé Canada, 2020)

La santé des populations de langue officielle en situation minoritaire [numéro thématique] - Leis, Anne; Bouchard, Louise (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Cette page éditoriale présente un numéro spécial de la Revue canadienne de santé publique qui comporte 16 articles compilant certains résultats de recherches obtenus par des chercheurs affiliés au RISF, au RRASFO et à l’Institut de recherche de l’Hôpital Montfort (IRHM), ainsi qu'un commentaire exposant les enjeux d'accès aux services de santé linguistiquement concordant au Pays de Galles.

English, French and official language minorities in Canada: Census of population, 2016 (n°98-200-X2016011) - Lepage, Jean-François (Statistics Canada, 2017)

Le français, l’anglais et les minorités de langue officielle au Canada : recensement de la population, 2016 (n°98-200-X2016011) - Lepage, Jean-François (Statistique Canada, 2017)

Portrait des minorités de langue officielle au Canada : les francophones du Manitoba - Lepage, Jean-François; Bouchard-Coulombe, Camille; Chavez, Brigitte (Statistique Canada, 2012)
Réalisé grâce au soutien financier du Secrétariat des langues officielles de Patrimoine canadien, de Ressources Humaines et Développement des Compétences Canada (RHDCC) ainsi que du ministère de la Justice Canada, ce portrait de la population de langue française du Manitoba est le huitième d’une série de portraits démolinguistiques des minorités de langue officielle au Canada rédigés par la Section des statistiques linguistiques de Statistique Canada. Cette étude brosse un portrait statistique général de la minorité de langue officielle du Manitoba en s’appuyant sur des données de recensements de la population ainsi que sur celles de l’Enquête sur la vitalité des minorités de langue officielle au Canada menée en 2006. Le but d’un tel portrait est de présenter un ensemble de caractéristiques, de comportements et de perceptions de la population de langue officielle minoritaire en mettant en évidence les possibilités d’analyse que recèlent les données. Le présent document ne se veut ni un simple assemblage de tableaux ni une étude approfondie de la dynamique démolinguistique de la population de langue française au Manitoba. Il présente une information diversifiée sur un ensemble de thèmes et de problématiques qui revêtent un intérêt pour les minorités de langue officielle et pour quiconque s’intéresse à la situation passée, actuelle et future des populations de langue officielle en situation minoritaire au Canada. La première section de ce portrait démolinguistique porte sur le choix des critères de définition de la population de langue française au Manitoba qui seront utilisés aux fins de ce document ainsi que sur une brève description des sources de données utilisées. La seconde section présente différentes informations qui rendent compte de l’évolution de la population de langue française ainsi que sur la répartition et la concentration de cette population sur le territoire manitobain. Cette information est accompagnée d’une série de cartes géographiques présentée en annexe et d’un tableau détaillé sur l’effectif, le poids relatif et la répartition de la population de langue française au Manitoba. La troisième partie de ce portrait porte sur les principaux facteurs qui influent sur l’évolution de la population de langue française dans cette province ou qui en résultent, soit la fécondité, la transmission de la langue maternelle et l’effet de l’exogamie, la structure par âge, la mobilité linguistique intragénérationnelle, la migration interprovinciale et internationale. De plus, on y présente de l’information sur l’usage du français dans la sphère publique et sur l’évolution de la capacité de soutenir une conversation selon le groupe de langue maternelle. La quatrième partie porte sur quelques secteurs clés pour la vitalité des communautés de langue officielle en situation minoritaire tels qu’identifiés dans la Feuille de route pour la dualité linguistique canadienne 2008-2013 : agir pour l’avenir1, soit la santé, la justice, l’éducation et les médias, les arts et la culture. Nous y présentons également des statistiques sur la participation communautaire, les caractéristiques de l’emploi et du revenu ainsi que sur l’utilisation du français au travail. Finalement, la dernière partie de ce portrait présente des statistiques sur l’appartenance identitaire des francophones et leurs perceptions à l’égard de la présence du français dans leur communauté, de l’offre de services en français de la part du gouvernement fédéral, du respect des droits linguistiques ainsi qu’à l’égard du fait que des gens travaillent au développement de la communauté francophone.

Portrait of Official-Language Minorities in Canada: Francophones in Manitoba - Lepage, Jean-François; Bouchard-Coulombe, Camille; Chavez, Brigitte (Statistics Canada, 2012)
This demolinguistic portrait of the French-speaking population in Manitoba was undertaken with the financial support of Canadian Heritage’s Official Languages Secretariat, Human Resources and Skills Development Canada (HRSDC) and Justice Canada. It is the eighth in a series of demolinguistic portraits of official-language minorities in Canada, prepared by Statistics Canada’s Language Statistics Section. This study paints a general statistical portrait of the official-language minority in Manitoba based on data from the Census of Population and the Survey on the Vitality of Official-Language Minorities in Canada, conducted in 2006. The purpose of such a portrait is to present a set of characteristics, behaviours and perceptions of the official-language minority population, exploiting the analytical opportunities contained in the data. This document is intended to be neither a mere collection of tables nor an in-depth study of the demolinguistic dynamics of the French-speaking population in Manitoba. It presents a range of information on themes and issues that will interest official-language minorities and anyone concerned with the past, present and future situation of official-language minority populations in Canada. Section 1 of this demolinguistic portrait concerns the criteria used in this study to define the French-speaking population in Manitoba. It also provides a brief description of the data sources used. Section 2 presents varied information on the evolution of the French-speaking population and its geographic distribution and concentration in Manitoba. This information includes a series of appended maps and a detailed table on the size, relative weight and distribution of the French-speaking population in Manitoba. Section 3 concerns the main factors that affect or are affected by changes over time in this province’s French-speaking population: fertility; transmission of mother tongue and effect of exogamy; age structure; intragenerational linguistic mobility; and interprovincial and international migration. It also discusses the use of French in the public sphere and how the ability to conduct a conversation in that language has evolved according to mother-tongue group. Section 4 looks at a few sectors essential to the vitality of official-language minority communities, as identified in the Roadmap for Canada’s Linguistic Duality 2008–2013: Acting for the Future1: health; justice; education; and the media, arts and culture. It also provides statistics on community participation, employment and income characteristics, and the use of French at work. The last section of this portrait presents statistics on the identity of Francophones and their perceptions regarding the presence of French in their community, the provision of federal government services in French, the respect for linguistic rights, and the fact that people are working to develop the Francophone community.

Health care professionals and official-language minorities in Canada, 2001 and 2011 (n°89-657-X 2017002) - Lepage, Jean-François; Lavoie, Émilie (Statistics Canada, 2017)

Professionnels de la santé et minorités de langue officielle au Canada, 2001 et 2011 (n°89-657-X 2017002) - Lepage, Jean-François; Lavoie, Émilie (Statistique Canada, 2017)

Identité, culture et représentations de la santé et des maladies - Lévesque, Annabel (Cahiers franco-canadiens de l’Ouest, 2015)
La santé et les maladies représentent des concepts subjectifs qui varient en fonction de nombreux facteurs, notamment la culture d’appartenance. Étant donné le contexte multiculturel canadien, il importe de considérer le contact interculturel lorsqu’on s’interroge au sujet des représentations de la santé et des maladies chez les groupes minoritaires puisque ces derniers sont soumis à l’influence d’autres cultures, dont la culture du groupe dominant. Ainsi, le degré d’identification à la culture d’origine et à la culture dominante détermine les représentations auxquelles souscrivent les individus issus d’un groupe minoritaire. Chez ceux qui s’identifient à leur culture d’origine, on note un lien entre leur état de santé et la vitalité culturelle et linguistique de leur communauté. Les efforts visant à promouvoir la santé et le bien-être de ces individus devraient donc être axés sur le maintien de leur héritage culturel et linguistique. Les professionnels de la santé, pour leur part, devraient engager le dialogue avec leurs patients au sujet de leurs représentations culturelles de la santé et des maladies, et ce, dans un climat empreint de respect. Cette pratique pourrait contribuer à la satisfaction des patients avec les soins reçus et, par le fait même, à l’adoption de comportements sains.

L’influence de l’identité linguistique et de l’âge sur la représentation sociale des services de santé mentale chez les personnes dites dépressives - Lévesque, Maude; Negura, Lilian; Moreau, Nicolas; Laflamme-Lagoke, M. (Minorités linguistiques et société, 2018)
Cet article étudie la représentation sociale des services de santé mentale chez les personnes dites dépressives en contexte francophone minoritaire au Canada. Des entrevues semi-dirigées ont été réalisées auprès de 44 personnes s’identifiant comme francophones et anglophones. Ces dernières proviennent de Moncton, Ottawa, Sudbury et Winnipeg et ont fait l’expérience d’un épisode dépressif. L’analyse lexicographique complétée par l’analyse intégrée de contenu a fait ressortir trois grands schèmes sociocognitifs de la représentation sociale des services, qui agissent sur l’acceptabilité sociale des services de santé mentale chez les personnes francophones vivant en situation minoritaire : 1) la nature impersonnelle des compétences expertes des professionnels de la santé, 2) la facette médicale de l’identité dépressive et 3) la perte perçue du contrôle dans le contexte de soins. L’acceptabilité sociale des services de santé mentale est discutée également en fonction de la configuration de la représentation sociale des services selon l’âge. Mots-clés : minorité linguistique, francophones, santé mentale, services, dépression, représentation sociale

Participation citoyenne, francophonie minoritaire et gouvernance des services de santé : les conceptions des acteurs - Lévesque, Maurice; Burlone, Nathalie; Boyer, Émilie (Université d'Ottawa, 2010)

Reference framework: Training for active offer of French-language health services - Lortie, L.ise; Lalonde, André. J. (Consortium national de formation en santé, 2012)

Cadre de référence pour la formation à l’offre active des services de santé en français (n°978-0-9879240-1-8) - Lortie, Lise; Lalonde, André. J. (Consortium national de formation en santé, 2012)

Les répercussions des problèmes de communication sur la prestation de soins de santé de qualité aux communautés et patients de langue minoritaire - MacLean, Patsy; Robinson, Constance; Lewis, Kay; HRA, firme d’experts-conseils (Réseau des services de santé en français de l’Île-du-Prince-Édouard et Société Santé en français, 2007)

Methodological issues in analysing small populations using CCHS cycles based on the official language minority studies - Makvandi, Ewa; Bouchard, Louise; Bergeron, Pierre-Jerôme; Sedigh, Golnaz (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Statistical analyses for small populations or small domains of interest can be challenging. To obtain reliable estimates, only very large surveys such as the Canadian Community Health Survey can be considered. However, despite its good geographical and temporal coverage, the analysis of small populations in smaller regions (e.g., health regions) and in regards to specific health issues remains challenging. We will look at the methodological issues in analysis of small populations in relation to sampling and non-sampling survey errors that affect the precision and accuracy of the estimates. Francophone minorities in Canada will be used to illustrate the issues throughout the paper.

Operationalising linguistic unease for the evaluation of language policies in healthcare - Marinaro, Nicole (Revista de Llengua i Dret, 2025)
This contribution presents an original methodological tool for the systematic evaluation of the relevance and comprehensiveness of healthcare language policy design. In particular, the focus of the analysis are public policies that address communication barriers experienced by patients who speak autochthonous or allochthonous languages other than the majority language in their interaction with the healthcare system. Such communication barriers are here conceptualised as “linguistic unease”. Within the epistemological framework of public policy analysis, the tool presented in the article hinges on the operationalisation of the concept of linguistic unease and is hence built on the centrality of the consideration of speakers’ needs. After outlining instances of linguistic unease in healthcare, the article presents the tool in detail and illustrates its employment through a brief practical example. , Aquest article presenta una eina metodològica original per a l’avaluació sistemàtica de la rellevància i l’exhaustivitat del disseny de polítiques lingüístiques en l’atenció sanitària. En concret, l’anàlisi se centra en les polítiques públiques que aborden les barreres de comunicació que experimenten els pacients que parlen llengües autòctones o al·lòctones diferents de la llengua majoritària a l’hora d’interactuar amb el sistema de salut. Aquestes barreres comunicatives es conceptualitzen com a “incomoditat lingüística”. Dins del marc epistemològic de l’anàlisi de les polítiques públiques, l’eina presentada a l’article es basa en l’operacionalització del concepte d’incomoditat lingüística i, com a tal, s’articula al voltant de la centralitat de les necessitats dels parlants. Després d’exposar diversos casos d’incomoditat lingüística en l’atenció sanitària, l’article descriu l’eina en detall i n’il·lustra l’ús a través d’un breu exemple pràctic. , Este artículo presenta una herramienta metodológica original para la evaluación sistemática de la relevancia y la exhaustividad del diseño de políticas lingüísticas en la atención sanitaria. En concreto, el análisis se centra en las políticas públicas que abordan las barreras de comunicación que experimentan los pacientes que hablan lenguas autóctonas o alóctonas diferentes de la lengua mayoritaria en sus interacciones con el sistema de salud. Estas barreras comunicativas se conceptualizan como “incomodidad lingüística”. Dentro del marco epistemológico del análisis de las políticas públicas, la herramienta presentada en el artículo se basa en la operacionalización del concepto de “incomodidad lingüística” y, como tal, se articula en torno a la centralidad de las necesidades de los hablantes. Después de exponer varios casos de incomodidad lingüística en la atención sanitaria, el artículo describe la herramienta en detalle e ilustra su uso a través de un breve ejemplo práctico.

Les soins de santé en français à l'extérieur du Québec - Marmen, L.ouise; Delisle, Sylvain (2003)

Validation culturelle d’un outil numérique francophone pour l’histoire médicale en soins de santé primaires - McGraw, Monica; Dionne Merlin, Marjolaine; Dion, Cynthia; Renaud, Julie; Légère, Danika; Poirier, Marie-Dominique (Minorités linguistiques et société / Linguistic Minorities and Society, 2025)
La technologie de santé numérique s’intègre dans les soins de santé améliorant l’engagement des patients dans les décisions partagées, favorisant ainsi leur prise en charge et la qualité des soins. FirstHx développe des outils innovants dans cette optique, mais leur mise en oeuvre est complexe pour la population francophone dans un contexte majoritairement anglophone. Cette étude vise à valider culturellement cet outil et à évaluer la satisfaction des utilisateurs. Une méthodologie mixte séquentielle explicative est employée en trois phases : un sondage quantitatif pour tester la clarté des questions, des entretiens semi-dirigés pour explorer la traduction culturelle et la convivialité, et une validation par des experts via la méthode Delphi. L’outil validé optimisera les pratiques cliniques, normalisera la saisie des données d’anamnèse et ouvrira de nouvelles perspectives de recherche. Cette validation offrira à la population francophone un accès équitable à des outils numériques innovants, renforçant leur engagement dans leurs soins. Digital health technology is being integrated into healthcare, improving patient engagement in shared decision-making, thereby promoting their care and the quality of care. FirstHx develops innovative tools with this goal in mind, but their implementation is complex for the Francophone population in a predominantly English-speaking context. This study aims to culturally validate this tool and assess user satisfaction. A sequential explanatory mixed-method approach is used in three phases: a quantitative survey to test question clarity, semi-structured interviews to explore cultural translation and user-friendliness, and validation by experts using the Delphi method. The validated tool will optimize clinical practices, standardize the collection of medical history data, and open new research opportunities. This validation will provide the Francophone population with equitable access to innovative digital tools, strengthening their engagement in their healthcare.

Comprendre l'expérience des soins de longue durée des minorités de langue officielle au Canada : une analyse de l'environnement | Understanding the long-term care experience of official language minorities in Canada: An environmental scan - Ménard, Alixe; Scott, Mary; Hsu, Amy T. (2022)

Santé et accès aux soins de santé des communautés francophones en situation minoritaire au Canada (CFSM) [numéro thématique] - Mercure, Dominique (Reflets, 2018)

Stages et réalité des professionnelles et professionnels en santé et services sociaux dans un contexte francophone minoritaire à Iqaluit, au Nunavut - Mercure, Dominique; Rivard, Sylvie; Bélanger, Roxanne; Charrier, Marie-Josée (Reflets, 2018)
Cet article présente la démarche d’analyse et les résultats d’une recherche sur les stages et la réalité des professionnelles et professionnels en santé et services sociaux dans un contexte francophone minoritaire en région arctique. Une démarche méthodologique d’étude de cas à multiples niveaux a été choisie pour permettre de comprendre le vécu des différents acteurs et actrices de la communauté francophone vivant à Iqaluit, au Nunavut. Douze entretiens ont été effectués auprès de stagiaires et de professionnelles et professionnels oeuvrant dans les services de santé et les services sociaux pour mieux saisir leur contexte de pratique, les défis rencontrés, les compétences développées dans ce milieu et les obstacles quant à l’organisation des stages. Les résultats illustrent les perceptions de participantes et participants non autochtones sur une réalité complexe composée de nombreux défis. Mots-clés : stages en région éloignée, Iqaluit (Nunavut, Canada), communauté francophone en situation minoritaire (CFSM), défis professionnels et personnels en milieu de stage, pratique professionnelle en contexte interculturel

Santé mentale - Michel, Isabelle; Lévesque, Johanne (Programme de recherche, d'éducation et de développement en santé publique, Institut franco-ontarien et Université Laurentienne, 2005)

L’émergence graduelle du droit à l’obtention de services publics provinciaux en français au Nouveau-Brunswick - Migneault, Gaètan (Revue juridique Thémis de l'Université de Montréal, 2016)

Guide des exigences et obligations concernant les services de santé en français - Ministère de la santé et des soins de longue durée (2017)

L’état de la recherche en travail social dans les communautés francophones minoritaires au Canada : une topographie thématique - Molgat, Marc; Trahan-Perreault, Julienne (Reflets, 2015)
Cet article présente un inventaire thématique des écrits scientifiques sur le travail social en contexte francophone minoritaire depuis les années 1990 et cherche à stimuler une réflexion sur les rapports entre la recherche et les communautés francophones minoritaires au Canada. La description des thèmes de recherche montre un dynamisme certain de la recherche, une grande diversité d’intérêts, une prédilection pour certaines thématiques dont celles de la santé et de l’intervention auprès des femmes et des personnes immigrantes. Mais il y aussi une absence d’écrits sur certains groupes dont les autochtones, et sur les milieux institutionnels d’intervention. Ces résultats s’expliquent notamment par la structuration des communautés et les conditions de la recherche en milieu francophone minoritaire, et permettent de tracer des voies pour la recherche à l’avenir. Mots-clés : travail social, recherche, recension, francophones, communautés francophones minoritaires, sociologie des connaissances

Expérience de conciliation travail-famille de parents francophones de la région d’Ottawa : étude pilote - Moreau, Denise; Polomeno, Viola; Ranger, Marie-Christine (Reflets, 2018)
Plusieurs études soutiennent que l’expérience de la conciliation travail-famille (CTF) a un impact majeur sur la santé et la qualité de vie des familles (Winter, et collab., 2006). Les objectifs de cette étude pilote étaient les suivants : 1) documenter l’expérience de la CTF chez un groupe de parents francophones de la région d’Ottawa, 2) élaborer, pré-tester et administrer le questionnaire sur l’expérience de conciliation travail-famille (ECTF), et 3) exécuter les premières étapes de validation de cet instrument. Cet article présente les données recueillies auprès de 46 participantes et participants concernant leurs expériences et leurs stratégies de CTF ainsi que leurs suggestions pour favoriser la CTF. Mots-clés : conciliation travail-famille, parents, francophones, étude pilote, Ottawa

Official Language Minority Communities in Ontario: Understanding the Lived Experiences of Francophone Patients and their Nursing Care Providers - Muray, Mwali (2022)
Although Canada is a bilingual country, official language minority community patients struggle to access quality care in their language. This reality has been of concern for Francophone minority communities in Ontario, but has seldom been examined in a nursing context. This research sought to examine the lived experiences of registered nurses and nursing students providing care to French-speaking patients in Ontario, as well as the realities of Francophone patients seeking French language health care services in Ontario. The conceptual frameworks guiding the study were the “Four Levels of Change for Improving Quality” model and the “Four-Level Model of the Health Care System.” Using qualitative phenomenological inquiry, as influenced by Martin Heidegger and Max van Manen, 31 semi-structured interviews were conducted with three subsets (n=10 Francophone patients; n=10 nursing students; n=11 registered nurses) throughout Ontario who had experience with the phenomenon being investigated. Data collection took place over a year (2018-2019) and was analysed thematically. Significant findings were identified across the three groups. Participants revealed the patchwork of individual actions taking place to remedy the existing gaps regarding care for Francophone minority populations. This included navigating a health care system where good enough care was the unfortunate standard for Francophone patients, and discussing how Francophone patients and nursing care providers implement strategies individually to manage the lack of resources for Francophone patient populations in Ontario. This thesis asserts that official language minority communities and their nursing care providers remain faced with difficulties providing and receiving care in Ontario. While numerous structures and resources exist to remediate the problems, these interventions and resources are not always implemented systemically, leading to a disproportionate burden on individuals, significant risks for safety for patient populations, and ethical dilemmas for nursing care providers. Recommendations are provided to bridge the gaps and ensure considerations of the needs of linguistic minorities throughout the health care system. Keywords: Francophonie, Linguistic Minorities, Nursing, Phenomenology, Qualitative Research

L'accès aux soins de santé des communautés de langue officielle en situation minoritaire (CLOSM) au Canada : une recension des écrits - Muray, Mwali; Peguero-Rodriguez, G.; Scarlett, Emilie; Perron, Amélie; Chartrand, Julie (Minorités linguistiques et société, 2022)
Cette étude présente une recension des écrits sur les expériences des patients et des prestataires de soins en ce qui concerne les services de santé au Canada offerts aux communautés de langue officielle en situation minoritaire (CLOSM). Mandatée par le Bureau d’appui aux communautés de langue officielle (BACLO), cette recension fait constat des défis et des obstacles qui entravent l’offre de services de santé et l’accès aux soins pour les CLOSM dans la langue officielle de leur choix, et propose des recommandations à l’intention des patients, des professionnels de la santé, des établissements de santé, des différents ordres de gouvernement au Canada et des chercheurs. Cette recension des écrits met en lumière le manque d’exécution systémique des stratégies, afin de faciliter l’accès aux services de santé dans leur langue pour les CLOSM fondées sur des données probantes. Elle s’interroge également sur le fait que peu de stratégies fondées sur des données probantes ont été mises en oeuvre à l’échelle du système malgré des décennies de recherche sur le sujet. Mots-clés : accès aux soins de santé, communautés de langue officielle en situation minoritaire (CLOSM), patients, professionnels de la santé, recension des écrits

The linguistic continuity of Ontario's minority Francophone population: Examining the relationship between culture and linguistic practices - Nault, Jean-François (Canadian Review of Sociology, 2019)
Despite decades of policy aimed at the maintenance of Francophone communities in Ontario, the proportion of individuals with French as a mother tongue or who speak French most often at home has steadily declined. Research on language retention has highlighted the importance of sociodemographic and structural factors in understanding minority language practices. However, given the relationship between culture and action, this paper examines how cultural factors contribute to Franco-Ontarians’ linguistic practices. Results indicate that beyond couple composition and the concentration of minority-language speakers, cultural factors including identity, cultural consumption, and values play an instrumental role in Franco-Ontarians’ linguistic continuity. The importance of considering linguistic continuity as part of a “package” of cultural practices is discussed.

The revised patient perception of patient-centeredness questionnaire: Exploring the factor structure in French-speaking patients with multimorbidity - Nguyen, Tu Ngoc; Ngangue, Patrice Alain; Ryan, Bridget. L.; Stewart, Moira; Brown, Judith. B.; Bouhali, Tarek; Fortin, Martin (Health Expectations, 2020)
Background The Patient Perception of Patient-Centeredness (PPPC) questionnaire was revised, and there is a need for the questionnaire to be tested in diverse primary care populations. Objectives This study aimed to examine the factor structure of the Revised PPPC questionnaire (PPPC-R) in French-speaking patients with multimorbidity. Design Secondary analysis from baseline data of the French arm of Patient-Centered Innovations for Persons with Multimorbidity Study (PACEinMM Study). Setting and participants Participants were adult patients with multimorbidity attending primary health-care settings. Outcome measures Exploratory factor analyses were applied to examine the factor structure of the PPPC-R. Cronbach's alpha values were calculated to assess the internal consistency of the whole questionnaire and of each factor explored. Results There were 301 participants, mean age 61.0, 53.2% female. The PPPC-R showed very good internal consistency, with three factors: Patient-Centered Clinical Method (PCCM) Component 1-Exploring the health, disease and illness experience + PCCM Component 4-Enhancing the patient–clinician relationship (Factor 1); PCCM Component 2-Understanding the whole person (Factor 2); and PCCM Component 3-Finding common ground (Factor 3). There was a good internal consistency within each factor (Cronbach's α = 0.87 for 8 items in Factor 1, 0.77 for 5 items in Factor 2 and 0.87 for 5 items in Factor 3). Discussion and conclusions The French PPPC-R factor structure was in accordance with the underpinning conceptual model and presented with three factors. Further assessment of its validity and reproducibility are needed to allow its use as a measure of patient's perception of patient-centeredness.

Language barriers: Use of regular medical doctors by Canada's official language minorities - Ngwakongnwi, Emmanuel; Hemmelgarn, Brenda, R.; Musto, Richard; King-Shier, Kathryn M.; Quan, Hude (Canadian Family Physician, 2012)

Experiences of French speaking immigrants and non-immigrants accessing health care services in a large Canadian city - Ngwakongnwi, Emmanuel; Hemmelgarn, Brenda. R.; Musto, Richard; Quan, Hude; King-Shier, Kathryn. M. (International Journal of Environmental Research and Public Health, 2012)
French speakers residing in predominantly English-speaking communities have been linked to difficulties accessing health care. This study examined health care access experiences of immigrants and non-immigrants who self-identify as Francophone or French speakers in a mainly English speaking province of Canada. We used semi-structured interviews to gather opinions of recent users of physician and hospital services (N = 26). Language barriers and difficulties finding family doctors were experienced by both French speaking immigrants and non-immigrants alike. This was exacerbated by a general preference for health services in French and less interest in using language interpreters during a medical consultation. Some participants experienced emotional distress, were discontent with care received, often delayed seeking care due to language barriers. Recent immigrants identified lack of insurance coverage for drugs, transportation difficulties and limited knowledge of the healthcare system as major detractors to achieving health. This study provided the groundwork for future research on health issues of official language minorities in Canada. Keywords: immigrants; French language; health care access; family doctor; qualitative descriptive; official language minorities

Comparison of sampling methods for hard-to-reach Francophone populations: Yield and adequacy of advertisement and respondent-driven sampling - Ngwakongnwi, Emmanuel; King-Shier, athryn. M.; Hemmelgarn, Brenda. R.; Musto, Richard; Quan, Hude (Open medicine, 2014)
Francophones who live outside the primarily French-speaking province of Quebec, Canada, risk being excluded from research by lack of a sampling frame. We examined the adequacy of random sampling, advertising, and respondent-driven sampling for recruitment of francophones for survey research. Methods: We recruited francophones residing in the city of Calgary, Alberta, through advertising and respondentdriven sampling. These 2 samples were then compared with a random subsample of Calgary francophones derived from the 2006 Canadian Community Health Survey (CCHS). We assessed the effectiveness of advertising and respondent-driven sampling in relation to the CCHS sample by comparing demographic characteristics and selected items from the CCHS (specifically self-reported general health status, perceived weight, and having a family doctor). Results: We recruited 120 francophones through advertising and 145 through respondent-driven sampling; the random sample from the CCHS consisted of 259 records. The samples derived from advertising and respondentdriven sampling differed from the CCHS in terms of age (mean ages 41.0, 37.6, and 42.5 years, respectively), sex (proportion of males 26.1%, 40.6%, and 56.6%, respectively), education (college or higher 86.7% , 77.9% , and 59.1%, respectively), place of birth (immigrants accounting for 45.8%, 55.2%, and 3.7%, respectively), and not having a regular medical doctor (16.7%, 34.5%, and 16.6%, respectively). Differences were not tested statistically because of limitations on the analysis of CCHS data imposed by Statistics Canada. Interpretation: The samples generated exclusively through advertising and respondent-driven sampling were not representative of the gold standard sample from the CCHS. Use of such biased samples for research studies could generate misleading results.

L’offre active de services en français : généalogie d’un outil de politique publique - Normand, Martin (Francophonies d'Amérique, 2019)
L’offre active de services en français est un principe qui s’est rapidement imposé dans le discours des principaux intervenants dans le domaine de la promotion et de la protection des langues officielles et de la dualité linguistique au Canada. Elle a été intégrée à des politiques, à des règlements et à des lois au palier fédéral et dans plusieurs provinces canadiennes. Plusieurs travaux ont été consacrés aux aspects liés à la mise en oeuvre du principe. Cet article va au-delà de ces contributions pour retracer l’histoire de l’offre active. Il répond à deux questions : 1) quelle est l’origine de l’offre active ? et 2) quels sont les principaux jalons dans son évolution et sa diffusion ? L’hypothèse est que les représentations initiales de l’offre active n’étaient pas que techniques ou formalistes et qu’elles se sont effritées avec le temps. La recherche repose essentiellement sur des sources primaires et secondaires, qui nous ont permis de reculer jusqu’au moment où le principe semble avoir émergé. Le texte s’organise autour de trois périodes : la conceptualisation, l’institutionnalisation et la diffusion de l’offre active.

The new Inclusive definition of Francophone (IDF) - Office of Francophone Affairs (2020)

Contribution Program to improve access to health services for Official Language Minority Communities. Formative evaluation. - Official Language Community Development Bureau (Health Canada, 2007)

Problèmes d’accès aux services en français ? Contactez-nous. Nous pouvons vous aider [infographie] - Ombudsman de l'Ontario (2022)

Active offer of mental health and addiction services: How to serve Francophones at their most vulnerable times [oral communication] - Ontario mental health & addictions virtual care collaborative (Centre for Addiction and Mental Health (CAMH), 2021)

Problems accessing services in French? Contact us. We can help [infographie] - Ontario Ombudsman (2022)

Connaissance et utilisation de la langue officielle minoritaire au travail par les travailleurs de la santé, 2001 à 2016 - Paez Silva, Alejandro. A.; Cornelissen, Louis (Statistique Canada, 2021)

Knowledge and use of the Official Minority Language at work by healthcare workers, 2001 to 2016 - Paez Silva, Alejandro. A.; Cornelissen, Louis (Statistics Canada, 2021)

Enjeux relatifs à la formation en français dans le domaine des sciences infirmières. Rapport du Comité permanent des langues officielles - Paradis, Denis (Gouvernement du Canada, Chambre des communes 42e Législature, 1re session, 2018)

Le laboratoire d’idées ad hoc et le développement de partenariats communautaires dans les services de santé - Parent, Roger (Minorités linguistiques et société, 2015)
Cet article fait état d’une recension des écrits effectuée pour le Consortium national de formation en santé (CNFS) autour du phénomène des laboratoires d’idées ou think tanks. Cette recension visait à identifier la forme de laboratoire d’idées en mesure de favoriser la prestation de soins de santé linguistiquement et culturellement appropriés dans les communautés d’expression française du Canada. Les écrits recensés font état de l’évolution du think tank classique vers des communautés de recherche axées sur un virage pragmatique qui redéfinit le savoir universitaire en fonction des besoins des usagers. Les pratiques transformatrices liées à cette démocratisation du savoir innovent en raison de leurs approches systémiques et organisationnelles envers la résolution de problèmes culturels. Mots-clés : laboratoire d’idées, communauté, santé, culture, système

Francophone patients - Patrie, Mélanie; Barbeau-Rodrigue, Danielle; Morris, Vanessa (Canadian Medical Association Journal, 2024)

Patientèle francophone - Patrie, Mélanie; Barbeau-Rodrigue, Danielle; Morris, Vanessa (Canadian Medical Association Journal, 2024)

Situation des populations de langue anglaise au Québec et de langue française au Canada hors Québec : résultats de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 - Pépin‑Filion, Dominique; Cornelissen, Louis; Lemyre, Étienne (Statistique Canada, 2024)
Le présent rapport et l’Enquête sur la population de langue officielle en situation minoritaire de 2022 ont bénéficié du soutien financier et de la collaboration soutenue du ministère du Patrimoine canadien. Cette étude a pu être réalisée grâce au travail de longue haleine de plusieurs équipes et personnes qui se sont relayées au fil des ans pour planifier, concevoir, préparer, tester, réaliser, assurer la qualité des données, documenter, analyser et diffuser cette enquête d’envergure. Les auteurs tiennent à remercier toutes les personnes qui ont participé à ce processus, en particulier, Marie Desnoyers, Éric Caron Malenfant, Daniel Pereira, Claude Girard, Marie‑ Hélène Toupin, Danielle Léger et Catherine Dufour. Plusieurs autres membres du personnel actuel ou passé de Statistique Canada ont contribué de manière importante à cette enquête au fil du temps, dont Siramane Coulibaly, Catherine Frigon, Julien Acaffou, Paul Brisson, Sara Tello, Jean‑Pierre Corbeil, Émilie Lavoie, Deniz Do, Jean‑François Nault, Guylaine Dubreuil, Isabelle Lévesque, Daphné Allard Gervais, Geneviève Caron, Geanina Popescu et Dominique Pérusse, de même que les équipes internes des activités de collecte et de traitement des données. Pour leur soutien, leurs conseils et leur aide à la production du rapport, merci à Laurent Martel, Daphne Fernandes, Juliane Oliveira Pisani Martini et Pierre‑France Bondesen‑David. Soulignons également l’expertise et l’orientation fournies par les réviseurs ainsi que les membres du comité de direction et les membres du comité scientifique de l’enquête.

Situation of English-speaking populations in Quebec and French-speaking populations in Canada outside Quebec: Results of the 2022 Survey on the Official Language Minority Population - Pépin‑Filion, Dominique; Cornelissen, Louis; Lemyre, Étienne (Statistique Canada, 2024)
This report and the 2022 Survey on the Official Language Minority Population received funding and ongoing support from the Department of Canadian Heritage. This study was made possible thanks to the tireless efforts of many different teams and individuals who, over the years, contributed to planning, designing, preparing, testing, conducting, ensuring data quality, documenting, analyzing and publishing this major survey. The authors would like to thank each and every one of them, especially, Marie Desnoyers, Éric Caron Malenfant, Daniel Pereira, Claude Girard, Marie‑Hélène Toupin, Danielle Léger and Catherine Dufour. Many other current or former Statistics Canada staff members have made, over the years, important contributions to this survey including Siramane Coulibaly, Catherine Frigon, Julien Acaffou, Paul Brisson, Sara Tello, Jean Pierre Corbeil, Émilie Lavoie, Deniz Do, Jean‑François Nault, Guylaine Dubreuil, Isabelle Lévesque, Daphné Allard Gervais, Geneviève Caron, Geanina Popescu and Dominique Pérusse, as well as the in‑house data collection and processing teams. For their support, advice and help in producing the report, thanks to Laurent Martel, Daphne Fernandes, Juliane Oliveira Pisani Martini and Pierre‑France Bondesen‑David. We would also like to acknowledge the expertise and guidance of the editors, as well as the members of the Interdepartmental Steering Committee and the survey Scientific Committee.

Hôpital Montfort : reflets de la francophonie en évolution - Perron Roach, Daniel (Reflets, 2015)

Étude de besoins sur les services de santé mentale en français. Rapport final - PGF Consultants (Société Santé en français et Santé Canada, 2019)

Deuxième rapport sur la santé des francophones de l’Ontario - Picard, Louise; Allaire, Gratien (Programme de recherche, d'éducation et de développement en santé publique, Institut franco-ontarien et Université Laurentienne, 2005)

Rapport sur la santé des francophones de l'Ontario, Sudbury - Picard, Louise; Sanderson, Ruth; Michel, Isabelle; Palangio, Alissa; Fraser, C.; Hébert, D.; Charland, J. (Programme de recherche, d’éducation et de développement en santé publique, Institut franco-ontarien et Université Laurentienne, 2000)

Substance Use, Addiction and Support Services: Increased Risk and Service Inequity for Official Language Minority Communities in Canada - Prada, Kevin; de Moissac, Danielle (The Canadian Journal of Addiction, 2024)
Abstract Objectives: The increase in substance use and addictions within the Canadian population, illustrated by the current opioid crisis and exacerbated by the COVID-19 pandemic, urges the investigation of populations who may be particularly vulnerable to developing problematic substance use. Official language minority communities in Canada, both understudied and underserved, may be one such population. Methods: Through its tripartite design using scoping literature review, interview, and environmental scan methodologies, this study offers a snapshot of the current reality surrounding substance use, addictions, and related treatment services available to this linguistic minority population. Results: Results reveal significant gaps in knowledge and service provision for this population. Service provision and knowledge on this issue constitute a nationwide patchwork, leaving official language minority communities underserved. While enough is known to assert that their needs are different than those of their majority peers, much remains to be investigated, and efforts to ameliorate their social determinants of health, including cultural and linguistic competence on behalf of service providers, are urgently needed. Conclusions: Recommendations include networking, collaboration, financial support and active offer of services in both official languages to improve mental health and addictions services through a continuum of care. Systems navigators may facilitate promotion and referral to such services for official language minorities. Résumé Objectifs: La prévalence croissante de la consommation des substances et des dépendances au Canada, tel qu’illustrée par la crise actuelle des opioïdes et exacerbée par la pandémie de la COVID-19, exhorte à l’investigation de populations qui pourraient être particulièrement vulnérables à la consommation problématique de substances. Au Canada, les communautés de langue officielle en situation de minorité (CLOSM), une population à la fois peu étudiée et peu desservie, pourrait bien représenter une telle population. Méthodes: Au moyen de sa stratégie tripartite, employant les méthodologies d’étude de la portée, d’entrevues, et de scan environnemental, cette étude brosse un premier portrait de la réalité actuelle quant à la consommation de substances, aux dépendances et aux services qui y sont voués, parmi les CLOSM au Canada. Résultats: Les résultats révèlent une lacune importante aux niveaux des connaissances et des services desservant les CLOSM dans la majorité des provinces et territoires. Bien que l’état des lieux soit parcellaire en raison du manque d’études scientifiques sur la question, le portrait actuel suffit pour constater que les besoins des CLOSM différent de ceux de leurs pairs de langue majoritaire. Une amélioration des déterminants sociaux de la santé, tel la compétence culturelle et linguistique de la part des pourvoyeurs des services, représente un besoin pressant. Conclusions: Les recommandations, qui comprennent le réseautage, la collaboration, l’appui financier et l’offre active des services dans les deux langues officielles, visent à améliorer les services voués à la santé mentale et aux dépendances auprès des CLOSM au sein d’un continuum de soins. Les navigateurs.rices de systèmes pourraient faciliter l’aiguillage de membres des CLOSM vers ces services.

An evaluation of FrancoForme: A case-managed home-based primary and secondary cardiovascular disease prevention program for French-speaking Canadians - Prince, Stephanie. A.; Laflamme, Marc; Harris, Jennifer; Tulloch, Heather E.; de Margerie, Michele (Journal of cardiopulmonary rehabilitation and prevention, 2017)
Purpose: Cardiovascular disease (CVD) is the leading cause of mortality globally. Telephone-delivered interventions targeting cardiovascular risk factors are gaining popularity. This study is an evaluation of FrancoForme, a cardiovascular risk factor reduction program for the primary and secondary prevention of CVD among French-speaking patients of Eastern Ontario. Methods: This study reports on changes in cardiovascular risk factors, weekly exercise levels, and psychosocial characteristics including anxiety, depression, and quality of life upon program completion (3 months) and at 1 year after the start of the program. Repeated-measures analysis of variance was used to compare changes in outcomes between primary prevention risk groups (low, moderate, and high risk for CVD) and the secondary prevention group (ie, cardiac rehabilitation) at baseline, 3 months and 12 months. Results: A total of 762 patients enrolled in FrancoForme between 2008 and 2015. At 3 months, all program completers (n = 507) experienced significant reductions for all cardiovascular risk factors except diastolic blood pressure. Minutes of self-reported exercise increased significantly by an average 90 minutes per week and all psychosocial variables improved. Significant group effects were observed across several risk factors. Among 12-month responders (n = 240), exercise, high-density lipoproteins, triglycerides, cholesterol, and all psychosocial variables were improved over baseline results. Conclusions: FrancoForme is unique in targeting both the primary and secondary prevention of CVD and removes several of the barriers to participating in a conventional CVD prevention program for French-speaking patients. FrancoForme is successful, receiving high satisfaction rates and resulting in significant improvements in cardiovascular risk factors, exercise, anxiety, and depression, as well as quality of life.

Ciel éclairci ! Vers un meilleur accès aux services de santé mentale et de lutte contre les dépendances en français en Ontario - Programme de soutien au système provincial (Centre de toxicomanie et de santé mentale, 2018)

Official language minority communities in Canada: Is linguistic minority status a determinant of mental health? - Puchala, Chassidy; Leis, Anne; Lim, Hyun; Tempier, Raymond (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)

The impact of language on emergency department visits, hospitalizations, and lenght of stay among home care recipients - Reaume, M.; Batista, Ricardo; Rhodes, Emily; Knight, Braden; Imsirovic, Haris; Seale, Emily; Riad, Karine; Prud'homme, Denis; Tanuseputro, Peter (Medical care, 2021)
Background: Research considering the impact of language on health care utilization is limited. We conducted a population-based study to: (1) investigate the association between residents’ preferred language and hospital-based health care utilization; and (2) determine whether this association is modified by dementia, a condition which can exacerbate communication barriers. Methods: We used administrative databases to establish a retrospective cohort study of home care recipients (2015–2017) in Ontario, Canada, where the predominant language is English. Residents’ preferred language (obtained from in-person home care assessments) was coded as English (Anglophones), French (Francophones), or other (Allophones). Diagnoses of dementia were ascertained with a previously validated algorithm. We identified all emergency department (ED) visits and hospitalizations within 1 year. Results: Compared with Anglophones, Allophones had lower annual rates of ED visits (1.3 vs. 1.8; P<0.01) and hospitalizations (0.6 vs. 0.7; P<0.01), while Francophones had longer hospital stays (9.1 vs. 7.6 d per admission; P<0.01). After adjusting for potential confounders, Francophones and Allophones were less likely to visit the ED or be hospitalized than Anglophones. We found evidence of synergism between language and dementia; the average length of stay for Francophones with dementia was 25% (95% confidence interval: 1.10–1.39) longer when compared with Anglophones without dementia. Conclusions: Residents whose preferred language was not English were less frequent users of hospital-based health care services, a finding that is likely attributable to cultural factors. Francophones with dementia experienced the longest stays in hospital. This may be related to the geographic distribution of Francophones (predominantly in rural areas) or to suboptimal patient-provider communication.

Qualité et sécurité des services de santé offerts en situation linguistique minoritaire en Ontario : investigations des données administratives de santé. - Reaume, Michael; Batista, Ricardo; Prud’homme, Denis; Tanuseputro, Peter (Minorités linguistiques et société, 2024)
Dans cet article, nous présentons une synthèse de plusieurs analyses récentes réalisées par notre groupe de recherche à partir de données administratives de santé pour mesurer la qualité et la sécurité des services de santé offerts aux francophones et allophones en Ontario, Canada. Les résultats de nos analyses démontrent que les Ontariennes et les Ontariens qui reçoivent des soins dans leur principale langue d’usage ont généralement de meilleurs résultats cliniques comparés à ceux qui reçoivent des soins dans une langue autre que leur principale langue d’usage. Ceci suggère que la qualité et la sécurité des soins offerts aux patients et aux patientes en situation de discordance linguistique pourraient être améliorées par le pairage de professionnel-patient parlant la même langue, par exemple, en référant un patient à un médecin qui parle la langue du patient, ou en s’assurant que les francophones ont accès aux services en français en milieux désignés en Ontario en vertu de la Loi sur les services en français et que les allophones puissent bénéficier de davantage de services d’interprétariat. Mots-clés : allophones, données administratives de santé, francophones, minorités de langue officielle, minorités linguistiques, qualité et sécurité des soins de santé

In-hospital patient harm across linguistic groups: A retrospective cohort study of home care recipients - Reaume, Michael; Batista, Ricardo; Talarico, Robert; Guerin, Eva; Rhodes, Emily; Carson, Sarah; Prud'homme, Denis; Tanuseputro, Peter (Journal of patient safety, 2022)
Objective Research examining the impact of language barriers on patient safety is limited. We conducted a population-based study to determine whether patients whose primary language is not English are more likely to experience harm when admitted to hospitals in Ontario, Canada. Methods We used linked administrative health records to establish a retrospective cohort of home care recipients (from 2010 to 2015) who were subsequently admitted to hospital. Patient language (obtained from home care assessments) was coded as English, French, or other. Harmful events were identified using the Hospital Harm Indicator developed by the Canadian Institute for Health Information. Results We included 190,724 patients (156,186 Anglophones, 5,110 Francophones, and 29,428 Allophones). There was no significant difference in the unadjusted risk of harm for Francophones compared with Anglophones (relative risk [RR], 0.94; 95% confidence interval [CI], 0.87–1.02). However, Allophones were more likely to experience harm when compared with Anglophones (RR, 1.14; 95% CI, 1.10–1.18). The risk of harm was even greater for Allophones with low English proficiency (RR, 1.18; 95% CI, 1.13–1.24). After adjusting for potential confounders, Anglophones and Allophones were equally likely to experience harm of any type, but Allophones more likely to experience harm from infections and procedures. Conclusions Patients whose primary language was not English or French were more likely to experience harm after admission to hospital, especially if they had low English proficiency. For these patients, the risk of harm from infections and procedures persisted in the adjusted analysis, but the overall risk of harm did not.

Patient-Physician Language Concordance and Cardiovascular Outcomes Among Patients With Hypertension. - Reaume, Michael; Labossière, Mathieu N.; Batista, Ricardo; Van Haute, Stephanie; Tangri, Navdeep; Rigatto, Claudio; Bohm, Clara; Prud’homme, Denis; Tanuseputro, Peter; Lix, L. M. (JAMA Network Open, 2025)
Importance Patients who live in minority language communities often receive health care services of lower quality and safety compared with patients who speak the majority language. Yet the outcomes associated with care provided by physicians who speak a patient’s primary language remain unknown. Objective To examine patient-physician language concordance and the risk of major adverse cardiovascular events (MACEs) among patients with hypertension. Design, Setting, and Participants This retrospective cohort study identified adults with self-reported hypertension in the Canadian Community Health Survey, a national survey that collects data from a representative sample of Canadians, from January 1, 2003, to December 31, 2014. Respondents (excluding those living in Quebec) had their hospitalization and mortality records linked to their survey responses. Data were analyzed from October 2023 to May 2024. Exposures Respondents’ primary home language was defined using language spoken most often at home. Language spoken with a regular physician was used to measure patient-physician language concordance. Respondents who spoke to their regular physician in their primary home language were classified as having received language-concordant care, while all other respondents were classified as having received language-discordant care.

Énoncé de position commune sur la variable linguistique - Regroupement des Entités de planification des services de santé en français de l’Ontario (Réseau des services de santé en français de l’Est de l’Ontario, 2013)

Des services de santé en français dans un Nord en mutation. Un défi intercommunautaire - Réseau de santé en français au Nunavut (Association des Francophones du Nunavut, Santé en français au Nunavut, 2006)

Affichage de postes bilingues dans la région de Kingston. Un guide utile pour les employeurs des secteurs de la santé et des services sociaux et communautaires | Job posting resource for bilingual positions in the Kingston area. A useful guide for employers in the healthcare and social community services sectors - Réseau des services de santé en français de l'Est de l'Ontario (A useful guide for employers in the healthcare and social community services sectors, 2019)

Better data for better planning: The challenge of evidence-based data for sound planning of French-Language health services in Ontario - Réseau des services de santé en français de l’Est de l’Ontario (The challenge of evidence-based data for sound planning of French-Language health services in Ontario, 2013)

Des données pour mieux planifier: Le défi des données pertinentes pour une planification judicieuse des services de santé offerts en français en Ontario - Réseau des services de santé en français de l’Est de l’Ontario (Le défi des données pertinentes pour une planification judicieuse des services de santé offerts en français en Ontario, 2013)

La population francophone au sein de votre équipe Santé Ontario : proposition d’indicateurs clés - Réseau des services de santé en français de l'Est de l'Ontario (2022)

Le Réseau à l’écoute. Rapport à la communauté 2022-2023. - Réseau des services de santé en français de l’Est de l’Ontario (2024)

Le Réseau à l’écoute. Rapport à la communauté 2023-2024. - Réseau des services de santé en français de l’Est de l’Ontario (2024)

Les variables linguistiques : un impératif pour une planification de services de santé adaptée aux besoins des francophones. État des lieux - Réseau des services de santé en français de l’Est de l’Ontario (État des lieux, 2012)

Mémoire sur la santé numérique en français en Ontario. Examen des documents d'orientation stratégique - Réseau des services de santé en français de l'Est de l'Ontario (2021)

Recommandation du Réseau. Application pratique de la Définition inclusive de francophone (DIF) - Réseau des services de santé en français de l’Est de l’Ontario (Application pratique de la Définition inclusive de francophone (DIF), 2013)

Recommandation du Réseau. Collecte des données linguistiques - Réseau des services de santé en français de l’Est de l’Ontario (2016)

Réseau recommendation. Application of the Inclusive definition of Francophone (IDF) - Réseau des services de santé en français de l’Est de l’Ontario (Application of the Inclusive definition of Francophone (IDF), 2013)

Services en français dans les CLOSM : produire des données probantes pour améliorer l’accès et la qualité. Mémoire du Réseau des services de santé en français de l’Est de l’Ontario dans le cadre de la consultation sur le renouvellement du PCLOS 2013-2018 - Réseau des services de santé en français de l’Est de l’Ontario (2016)

Les réseaux : architectes de la santé en français - Réseau des services de santé en français de l’Est de l’Ontario; Réseau de santé en français du Moyen-Nord de l’Ontario; Réseau francophone de santé du Nord de l’Ontario; Réseau franco-santé du Sud de l’Ontario (Les réseaux : architectes de la santé en français, 2007)

Je suis insatisfait(e) des services de santé reçus. Que faire ? Comment procéder ? [infographie] - Réseau des services de santé en français de l'Est de l'Ontario; Santé Canada; Société Santé en français (2022)

Final Report – Improving the Francophone Experience in Healthcare - Réseau du mieux-être francophone du Nord de l'Ontario (2021)

Rapport final – Amélioration de l’expérience des francophones dans les soins de santé - Réseau du mieux-être francophone du Nord de l'Ontario (2021)

Préparer le terrain. Soins de santé primaires en français dans le Sud de l'Ontario. Rapport régional - Réseau franco-santé du Sud de l'Ontario (2006)

Préparer le terrain : soins de santé primaires en français en Ontario. Rapport provincial - Réseau francophone de santé du Nord de l’Ontario; Réseau de santé en français du Moyen-Nord de l’Ontario; Réseau franco-santé du Sud de l’Ontario; Réseau des services de santé en français de l’Est de l’Ontario (2006)

À la rencontre des communautés acadiennes et francophones et de leurs enjeux en santé - Réseau Santé (Réseau santé en français de Nouvelle-Écosse, 2021)

Argumentaire pour la promotion d’une offre de service santé de qualité dans la langue maternelle des clients au Nunavut - Réseau Santé en français au Nunavut (2021)

Améliorer l’état de santé des francophones de Terre Neuve-et-Labrador - Réseau Santé en français de Terre-Neuve-et-Labrador (2021)

Santé mentale en français. Comprendre les enjeux et l’urgence de collaborer aux TNO - Réseau TNO Santé (Comprendre les enjeux et l’urgence de collaborer aux TNO, 2018)

Consultation publique sur l'accès aux services de santé en français - RésoSanté Colombie-Britannique (2016)

Consultation publique sur l'accès aux services de santé en français (infographie) - RésoSanté Colombie-Britannique (2016)

Enquête sommaire sur la santé des francophones de Colombie-Britannique - RésoSanté Colombie-Britannique (2016)

Santé des francophones en milieu minoritaire. Quelle est la situation en Colombie-Britannique ? | The health of Francophone minorities. What does it mean for British Colombia? - RésoSanté Colombie-Britannique (What does it mean for British Colombia, 2021)

Report on the 2020–2023 Café de Paris Manitoba Pilot Project - Roberge, Jérémie (Santé en français Manitoba, 2023)

La francophonie boréale : la vitalité des communautés francophones dans les territoires. - Robineau, Anne; Traisnel, Christophe; Forgues, Éric; Guignard Noël, Josée; Landry, Rodrigue; Ministère du Patrimoine canadien; Commissariat aux langues officielles (Institut canadien de recherche sur les minorités linguistiques, 2010)

Le Centre de santé de Clare : un modèle pour l'accès à des services de santé en français - Sangaré, Yalla (Reflets, 2014)

5 enjeux prioritaires en santé des communautés acadienne et francophones - Santé Nouvelle-Écosse; Réseau Santé Nouvelle-Écosse (2022)

Données sur les soins de longue durée en français-Équipe Santé Ontario du Grand Fleuve - Santé Ontario; Réseau des services de santé en français de l'Est de l'Ontario; Santé Canada (2022)

La recherche en santé et en services sociaux auprès des populations francophones en situation minoritaire au Canada. Revue de littérature et analyse des thèmes de recherche (2014-2016) - Sauvageau, Marie-Michèle (Association des collèges et universités de la francophonie canadienne, 2018)

Challenges faced by bilingual stroke survivors in the healthcare system: Unique considerations - Sauvé-Schenk, Katrine; Dubouloz-Wilner, Claire-Jehanne; Egan, Mary; Kristjansson, Elizabeth (Linguistic Minorities and Society, 2020)
The experiences of multilingual patients communicating with unilingual healthcare providers have been largely unexplored. The aim of this study was to investigate the experiences of bilingual stroke patients within the Canadian healthcare context. A secondary analysis was completed with data from a multiple case study of the experiences of seven, low-income bilingual Francophone stroke survivors living in a predominately English area. Data included semi-structured interviews, chart reviews and language proficiency assessments. Results demonstrated that bilingual survivors experience unique challenges, including limited French health vocabulary, use of non-standard French, and generally low health literacy levels in both languages. Participants with aphasia often used English and French interchangeably, leading to the potential for miscommunication when providers were not bilingual. The study highlights the importance of having bilingual healthcare providers when bilingual stroke survivors have communication or cognitive limitations. Keywords: Stroke, language, bilingualism, healthcare, literacy

L’expérience des francophones des soins et des services en contexte linguistique minoritaire : bilan et perspectives. - Sauvé-Schenk, Katrine; Savard, Jacinthe; Miljours, Jean-Christophe; Bouchard, Louise (Minorités linguistiques et société, 2024)
L’objectif de cet article est de présenter un état des lieux de la recherche qui porte sur l’expérience des bénéficiaires de services sociaux et de santé en contexte francophone minoritaire. On y traite des perceptions envers les services sociaux et de santé, de la demande de services en français ainsi que des expériences d’accès à des services en français, des barrières linguistiques et de la navigation dans le système de santé. On y traite aussi les perspectives qu’apportent les recherches en cours pour 1) mieux saisir les perceptions des francophones à l’égard de l’utilisation des technologies en santé afin d’améliorer leur accès aux services en français et 2) intégrer la mesure de la perception des usagers à l’évaluation continue des services en français. Mots-clés : expérience patient, minorité linguistique, francophone, système de santé, Canada

Conditions gagnantes pour une offre active de services en français efficace dans un milieu à faible densité de francophones : résultats d’une étude pilote. Rapport sommaire présenté à la Société Santé en français - Sauvé-Schenk, Katrine; Savard, Jacinthe; Prud’homme, Denis; Durand (Chiocchio), F.; Delluc, C. (Institut du savoir Montfort et Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2021)

Pratique # 16 : Des stages en français pour préparer à servir la clientèle francophone en milieu francophone minoritaire (Ontario) - Savard, Jacinthe; Benoît, Josée (2019)

Des stages en français pour se préparer à travailler auprès communautés francophones en situation minoritaire - Savard, Jacinthe; Benoît, Josée; Dubouloz, Claire-Jehanne; Breau-Godwin, Stéphanie (Reflets, 2018)
Dans l’objectif d’augmenter le nombre de professionnelles et professionnels pouvant offrir des services sociaux et de santé en français dans les communautés francophones en situation minoritaire (CFSM), des stages en français ont été offerts à des étudiantes et étudiants bilingues de programmes de formation professionnelle offerts en anglais au sein d’universités canadiennes. L’expérience a été positive pour l’ensemble des parties prenantes : stagiaires, éducatrices-cliniciennes et responsables de la formation clinique. Après cette expérience, les stagiaires ont mentionné avoir une meilleure connaissance des défis d’accès aux services rencontrés par les CFSM et se sentir plus en mesure d’offrir des services en français à ces communautés. Mots-clés : stage en français, formation clinique, communautés francophones en situation minoritaire, offre active, réadaptation

Évaluation métrologique de la Mesure de l’offre active de services sociaux et de santé en français en contexte minoritaire - Savard, Jacinthe; Casimiro, Lynn; Benoît, Josée; Bouchard, Pier (Reflets, 2014)
Comment peut-on mesurer l’impact des actions entreprises pour améliorer l’offre active de services sociaux et de santé en français dans les communautés francophones en situation minoritaire? Un questionnaire mesurant premièrement les comportements individuels de l’offre active et deuxièmement la perception du soutien organisationnel à faire de l’offre active a été créé. La validité de contenu de la Mesure de l’offre active de services en françaisen contexte minoritaire a été établie à l’aide d’une recension d’écrits, de consultations menées auprès d’expertes et d’experts et d’un sondage Delphi pancanadien. Sa fidélité a été examinée à partir de données recueillies auprès de récents diplômés en santé et en service social. L’outil démontre une bonne consistance interne et des études auprès d’un plus large échantillon sont nécessaires pour augmenter la confiance envers sa stabilité temporelle. Il s’agit des premiers pas d’une démarche visant à mesurer l’évolution des comportements d’offre active à la suite d’activités de formation ou de changements organisationnels en faveur de services en français. Une telle mesure est aussi susceptible d’être utile dans les recherches visant à saisir les déterminants de ces comportements d’offre active. Mots-clés : Offre active de services en français, formation des professionnelles ou professionnels en santé et services sociaux, soutien organisationnel, évaluation, minorité, langue et services, qualité des soins et services, sécurité des clientes ou clients/patientes ou patients

Behaviours demonstrating active offer: Identification, measurement, and determinants - Savard, Jacinthe; Casimiro, Lynn; Bouchard, Pier; Benoît, Josée (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Les comportements favorables à l’offre active, leur mesure et leurs déterminants - Savard, Jacinthe; Casimiro, Lynn; Bouchard, Pier; Benoît, Josée (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Dans ce chapitre, nous présenterons comment nous avons répertorié des comportements favorables à une offre active (OA) de services sociaux et de santé en français en contexte minoritaire, comment nous les avons mesurés et comment nous avons utilisé ces mesures pour déceler des déterminants de l’OA. Nous présentons en détail l’élaboration des outils qui ont servi à mesurer les comportements d’OA, le soutien organisationnel perçu envers l’OA et les caractéristiques personnelles qui peuvent influer sur les comportements d’OA (déterminants). Diverses méthodes quantitatives ont été utilisées pour atteindre ces objectifs. Les résultats obtenus démontrent la présence d’un fort lien entre le soutien organisationnel perçu et les comportements individuels d’OA. À soutien organisationnel égal, les caractéristiques individuelles associées à une plus grande propension à démontrer des comportements d’OA incluent une formation sur l’OA, l’affirmation identitaire et la compétence en français. Le sentiment de compétence en anglais est quant à lui associé négativement aux comportements individuels d’OA de services en français. Une meilleure connaissance de ces déterminants permet de raffiner les stratégies de sensibilisation et d’éducation des futurs professionnels de la santé et des services sociaux envers l’OA. Mots-clés : comportements d’offre active, mesure, déterminants, soutien organisationnel, comportements individuels, recherche quantitative.

Conception d’outils de mesure de l’offre active de services sociaux et de santé en français en contexte minoritaire - Savard, Jacinthe; Casimiro, Lynn; Bouchard, Pier; Benoît, Josée; Drolet, Marie; Dubouloz Claire-Jehanne (Minorités linguistiques et société, 2015)
Dans les communautés francophones en situation minoritaire, le besoin d’une offre active des services en français, plutôt que d’un service qui suit la demande, est de plus en plus reconnu. Les professionnels en santé et en service social doivent être formés à cette approche et les résultats devront être évalués. Cet article décrit le processus de création et de validation de contenu (recension d’écrits, consultations d’experts, sondage Delphi pancanadien) de deux questionnaires portant sur les comportements caractéristiques de l’offre active de services sociaux et de santé en français : le premier mesurant les comportements individuels d’offre active des intervenants et le deuxième mesurant la perception de ces derniers du soutien organisationnel à l’offre active. Mots-clés : offre active, formation des professionnels de la santé et des services sociaux, évaluation, minorités, langue et services, soutien organisationnel

Cadre d’analyse des leviers d’action pour l’accès et l’intégration des services sociaux et de santé pour les communautés de langue officielle en situation minoritaire - Savard, Jacinthe; Savard, Sébastien; Drolet, Marie; De Moissac, Danielle; Kubina, Lucy-Ann; van Kemenade, Solange; Benoit, Josée; Couturier, Yves (2017)

Framework for the Analysis of Health and Social Services Access and Integration for Official Language Minority Communities - Savard, Jacinthe; Savard, Sébastien; Drolet, Marie; De Moissac, Danielle; Kubina, Lucy-Ann; van Kemenade, Solange; Benoit, Josée; Couturier, Yves (2018)

Pratique # 4 : L’intégration de la variable linguistique dans la collecte de données (Île-du-PrinceÉdouard) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)

Pratique # 5 : Le Cadre de référence pour le recrutement et la rétention des ressources humaines bilingues en santé et la Stratégie Ressources humaines en santé (Pan-canadien). - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)

Pratique # 6 : Café de Paris (Nouveau-Brunswick) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 7 : La tournée des établissements désignés bilingues (Manitoba). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)

Les professionnels de la santé et des services sociaux intervenant auprès des francophones minoritaires : l’enjeu du capital social - Savard, Sébastien; Arcand, Isabelle; Drolet, Marie; Benoît, Josée; Savard, Jacinthe; Lagacé, Josée (Francophonies d’Amérique, 2013)
Cet article présente les résultats d’une recherche qualitative sur la collaboration et le partenariat entre les professionnels des services sociaux et de la santé qui interviennent auprès de francophones vivant en situation minoritaire en Ontario. L’étude met en lumière, à partir de l’information recueillie auprès de 43 professionnels rencontrés dans huit groupes de discussion, le contexte qui caractérise leur pratique, les défis qu’ils rencontrent dans leur tentative de créer des liens de collaboration avec d’autres professionnels qui oeuvrent auprès des communautés francophones minoritaires ainsi que les facteurs qui facilitent l’établissement de partenariats entre les différents intervenants qui répondent aux besoins de cette population. Les résultats font ressortir que le sentiment d’appartenance, la confiance et l’engagement des professionnels envers la communauté francophone, de même que les valeurs de réciprocité et de solidarité qui les habitent sont des éléments qui favorisent le développement du capital social de la communauté des intervenants. Cependant, le manque de mécanismes permettant la consolidation et la pérennisation des relations de collaboration constitue un facteur qui limite la capacité de bonifier le capital social des professionnels de la santé et des services sociaux francophones et bilingues.

L’accès aux services en français, de la connaissance des défis à l’accompagnement des organisations vers le changement. - Savard, Sébastien; Savard, Jacinthe; Sauvé-Schenk, Katrine; van Kemenade, Solange; Benoît, Josée (Minorités linguistiques et société, 2024)
Depuis 2011, le Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (GReFoPS) cherche à mieux comprendre les facilitateurs et les obstacles à l’offre de services en français dans un contexte linguistique minoritaire au Canada. Dans cet article, les auteurs présentent un bilan de près de 12 ans de recherche sur le sujet, en décrivant les facteurs individuels et organisationnels qui influencent l’offre de services en français. Les résultats de ces études ont mis en lumière quelques mécanismes organisationnels ou interorganisationnels qui ont permis l’émergence de pratiques novatrices pour améliorer l’offre de services en français dans les services communautaires et institutionnels. On y décrit également des outils créés pour aider les gestionnaires de ces services à identifier des mesures et des mécanismes pouvant répondre aux besoins des usagers francophones en situation minoritaire. Mots-clés : accès, services sociaux et de santé, francophones, contexte minoritaire, Canada

A self-assessment tool for healthcare and social service provision in French: What use for managers? - Savard, Sébastien; Savard, Jacinthe; van Kemenade, Solange; Benoît, Josée; Tabor, Michelle (Healthcare Management Forum, 2020)
Language is an important determinant of health, and lack of access to quality, linguistically adapted healthcare and social services negatively impacts users. Besides the lack of bilingual resources, our previous research on Francophone minority community seniors’ trajectories through these services shed light on important and nonobvious challenges currently faced by organizations offering healthcare and social services to this population. Current service provision appeared limited due to organizations working in silos with suboptimally used resources for integrating active offer of French language services throughout the continuum of care. This situation led our team to create the Organizational and Community Resources Self-Assessment Tool for Active Offer and Continuity of French Language Healthcare and Social Services, which is intended to help managers and service providers promote and facilitate the integration of active offer throughout the continuum of service provision. This article describes the Tool’s creation, content validation, and pilot-testing.

Vers de nouvelles approches en santé mentale : possibilités et limites pour les francophones en situation minoritaire à Terre-Neuve-et-Labrador et aux Territoires du Nord-Ouest - Savard, Sébastien; van Kemenade, Solange; Bouchard, Louise; Savard, Jacinthe; Oukouami D, Ghisleine; Michel, Jean Nephetaly (Canadian Social Work Review / Revue canadienne de service social, 2024)
De nouvelles approches axées sur la cybersanté mentale l’aide à la navigation du système, les cliniques sans rendez-vous, ainsi que les approches plus traditionnelles comme les lignes d’aide et de crise cohabitent afin de promouvoir ou d’intervenir précocement en santé mentale. Comment ces interventions répondent-elles aux besoins des francophones en contexte linguistique minoritaire alors que la communication est au coeur d’une consultation réussie? Objectif : Documenter six initiatives à Terre-Neuve-et-Labrador et dans les Territoires du Nord-Ouest. Méthode : Études de cas, incluant trente-six entrevues semi-dirigées auprès des autorités sanitaires, des fournisseurs de soins et des usagers. Résultats : La gratuité, l’anonymat, la rapidité, la présence des pairs travailleurs, l’absence de jugement et des démarches simples facilitent l’accès aux programmes. Parmi les limites, l’insuffisance de services en français et l’accent sur les thérapies brèves peuvent affecter la continuité des services, notamment pour les usagers francophones. Conclusion : Malgré les efforts pour améliorer l’offre de services en santé mentale aux francophones, des lacunes subsistent. L’article présente certaines stratégies qui permettraient d’améliorer l’offre de ces services. Mots-clés : Santé mentale, cybersanté mentale, initiatives novatrices, Terre-Neuve-et-Labrador, Territoires du Nord-Ouest, soins par paliers, francophones en situation minoritaire

La Société Santé en français : un modèle canadien de partenariat qui a fait ses preuves - Schofield, Aurel; Gauthier, Hubert (Education for Health, 2007)
Les francophones du Canada vivant en milieu linguistique minoritaire ont peu accès à des services de santé dans leur langue. Pour palier à cette problématique, le gouvernement du Canada a adopté un modèle de réseautage basé sur la stratégie Vers l’Unité pour la santé (VUPS) proposée par l’Organisation mondiale de la santé (OMS). Ce modèle, adopté depuis 2001, a donné naissance à une multitude de réseaux et partenariats qui couvrent l’ensemble des régions où vivent les francophones vivant en milieu minoritaire. Selon ce modèle, les réseaux sont constitués des cinq partenaires clés dans le secteur de la santé: les professionnels de la santé, la communauté, les gestionnaires d’établissements de soins, les institutions de formation et les gouvernements. Le gouvernement fédéral canadien, en collaboration avec la communauté, a pris en main le dossier de la santé en français grâce à la mise en place de deux agences à but non lucratif ayant une vision commune. Ces deux agences, la Société Santé en français (SSF) et le Consortium national de formation en santé (CNFS) collaborent en action concertée pour améliorer l’accès aux services de santé et ainsi améliorer l’état de santé de la population francophone vivant en milieu minoritaire. Le fonctionnement en réseau selon le modèle VUPS apporte de nombreuses opportunités mais également des défis à relever.

Patient-physician language concordance and quality and safety outcomes among frail home care recipients admitted to hospital in Ontario, Canada - Seale, Emily; Reaume, Michael; Batista, Ricardo; Eddeen, Anan. Bader; Roberts, Rihannon; Rhodes, Emily; McIsaac, Daniel. I.; Kendall, Claire. E.; Sood, Manish. M.; Prud'homme, Denis; Tanuseputro, Peter (Canadian Medical Association Journal, 2022)
Background: When patients and physicians speak the same language, it may improve the quality and safety of care delivered. We sought to determine whether patient–physician language concordance is associated with in-hospital and postdischarge outcomes among home care recipients who were admitted to hospital. Methods: We conducted a population-based study of a retrospective cohort of 189 690 home care recipients who were admitted to hospital in Ontario, Canada, between 2010 and 2018. We defined patient language (obtained from home care assessments) as English (Anglophone), French (Francophone) or other (allophone). We obtained physician language from the College of Physicians and Surgeons of Ontario. We defined hospital admissions as language concordant when patients received more than 50% of their care from physicians who spoke the patients’ primary language. We identified in-hospital (adverse events, length of stay, death) and post-discharge outcomes (emergency department visits, readmissions, death within 30 days of discharge). We used regression analyses to estimate the adjusted rate of mean and the adjusted odds ratio (OR) of each outcome, stratified by patient language, to assess the impact of language-concordant care within each linguistic group. Results: Allophone patients who received language-concordant care had lower risk of adverse events (adjusted OR 0.25, 95% confidence interval [CI] 0.15–0.43) and in-hospital death (adjusted OR 0.44, 95% CI 0.29–0.66), as well as shorter stays in hospital (adjusted rate of mean 0.74, 95% CI 0.66–0.83) than allophone patients who received language-discordant care. Results were similar for Francophone patients, although the magnitude of the effect was smaller than for allophone patients. Language concordance or discordance of the hospital admission was not associated with significant differences in postdischarge outcomes.

Manuel des directives sur la mise en œuvre des services en français d’après la politique du gouvernement du Manitoba | Guidelines manual for the implementation of French language services based on government of Manitoba policy - Secrétariat aux affaires francophones (2017)

Exploring the determinants of language barriers in health care (LBHC): Toward a research agenda for the language sciences - Segalowitz, Norman; Kehayia, Eva (The Canadian Modern Language Review, 2011)
There is growing interest in language barriers in health care (LBHC) – interest, that is, in how the quality of health care service delivery might be compromised when patients and health care providers do not share the same first language. This article discusses LBHC as an emerging research area that provides valuable opportunities for researchers in various branches of the language sciences – including, among others, applied linguistics, theoretical linguistics, psycholinguistics, second language acquisition – to conduct basic research and to make contributions to the socially important area of medical communication. This article also proposes a research agenda aimed at attracting general language researchers to the study of LBHC, an agenda that is theory driven, programmatic, problem-solving oriented, and interdisciplinary in scope. In proposing this agenda, selected examples have been reviewed from the current literature that can serve as illustrative models for how future research into LBHC can proceed.

Culture de sécurité des professionnels de santé en soins primaires : adapatation en langue française du questionnaire MOSPSC (« Medical Office Survey on Patient Safety Culture ») - Shih, C.; Buchet-Poyau, K.; Keriel-Gascou, M.; Quenon, J.-L.; Michel, P.; Touzet, S.; Chanalière, Marc (Revue d'Épidémiologie et de Santé Publique, 2022)
Contexte La culture de sécurité (CDS) rend compte de déterminants individuels et organisationnels. Son évaluation auprès des professionnels de santé en soins primaires (SP) peut être réalisée par des questionnaires auto-administrés, tel le « Medical Office Survey on Patient Safety Culture » (MOSPSC). Objectif Adapter en français le questionnaire MOSPSC et en étudier les propriétés psychométriques. Méthode Le questionnaire MOSPSC a fait l'objet d'une traduction avec analyse linguistique en langue française ; une rétrotraduction vers l'anglais a été réalisée, conformément aux recommandations de l'ISPOR. La version française du questionnaire a été diffusée à 415 professionnels de santé de 36 structures pluriprofessionnelles ambulatoires. L’étude des propriétés psychométriques (test-retest, α de Cronbach et analyse factorielle) a été conduite à partir des réponses des professionnels. Résultats Après analyse linguistique, la notion d’équipe a été traduite par celle de structure dans le questionnaire final. Le taux de participation des professionnels à l'enquête était de 64,1 % (266/415) ; 51,9 % (138/415) étaient des paramédicaux (principalement IDE ou kinésithérapeutes). Le coefficient α de Cronbach est de 0,94 pour l'ensemble des dimensions. Après analyse psychométrique, la dimension « signalement des évènements indésirables » a été ajoutée, et celle de « formation du personnel » intégrée à celle de « formation et standardisation des pratiques », portant à 13 le nombre de dimensions identifiées après analyse factorielle. Conclusion Le questionnaire MOSPSC adapté et validé en français peut être utilisé pour mesurer la CDS des professionnels en soins primaires en France. Son usage permettrait d'envisager à terme des comparaisons à l’échelle de chaque structure, pour y suivre l’évolution de la CDS, et dans le cadre de recherches nationales et internationales sur la gestion des risques en soins primaires.

Santé des francophones et utilisation des services de santé dans les Réseaux locaux d’intégration des services de santé d’Érié St.Clair et du Sud-Ouest - Smith, Michaela (Entité de planification des services de santé en français Érié St.Clair/Sud-Ouest, 2013)

Pour une réforme de la santé respectueuse des deux communautés linguistiques officielles. Mémoire présenté à l’honorable Dorothy Shephard, ministre de la Santé, dans le cadre de la consultation publique sur l’avenir des soins de santé dans la province du Nouveau-Brunswick - Société de l'Acadie du Nouveau-Brunswick (2021)

Des soins de santé et des services sociaux sécuritaires dans sa langue. Réponse au projet de Cadre canadien sur la qualité des soins et la sécurité des patients - Société Santé en français (2019)

Favoriser le rétablissement dans sa langue. Orientation en santé mentale en français. Version révisée - Société Santé en français (Version révisée, 2014)

Sensibilisation, structuration et consolidation en santé en français : 10 ans d’action - Société Santé en français (Reflets, 2014)

Pour la promotion de la santé en français au Canada - Société Santé en français et les Réseaux de santé en français (2016)

Mémoire sur l’accès aux soins de santé primaires au Nouveau-Brunswick - Société Santé et Mieux-être en français du Nouveau-Brunswick; Mouvement Acadien des Communautés en Santé du Nouveau-Brunswick Inc (2011)

L’offre de services dans les deux langues officielles dans le domaine de la santé : à nous d’y voir ! - Société Santé et Mieux-être en français du Nouveau-Brunswick; Réseau-action formation et recherche (2009)

Quand la langue fait une différence. Ce que des « bénéficiaires » pensent du système de santé mentale - St-Amand, Nérée; Vuong, Dung (Sociologie et sociétés, 2002)
Résumé En partant d'une recherche effectuée en 1993 auprès d'une soixantaine d'ex-psychiatrisés néo-brunswickois qui fréquentent maintenant des réseaux d'entraide de cette province, cet article met en évidence certains des enjeux auxquels sont confrontées les personnes " trans-institutionnalisées ". Il en ressort plusieurs différences au niveau de l'utilisation des services et du degré de satisfaction, selon l'appartenance sexuelle et la langue en particulier. De plus, cette recherche démontre que le réseau sur lequel s'appuient les ex-psychiatrisés francophones interrogés est davantage social (familles, groupe d'entraide), alors que pour la population anglophone, l'appareil institutionnel (psychiatres, institutions et cliniques) joue un rôle déterminant. Ceci soulève plusieurs questions, tant au niveau des politiques sociales que des pratiques d'intervention, en contexte minoritaire en particulier. Abstract On the basis of research carried out in 1993 on sixty or so ex-psychiatric patients who now frequent mutual aid networks in New Brunswick, this paper points out some of the issues with which these 'trans-institutionalized' persons are confronted. Differences at the level of service use and degree of satisfaction stand out, particularly in relation to gender and language. Moreover, this research shows that the network on which Francophone ex-psychiatric patients depend is more social in nature (families, mutual aid groups), whereas for the Anglophone population the institutional apparatus (psychiatrists, institutions and clinics) play a determining role. This brings up several questions, in regards to social policies as well of intervention practices, particularly in the minority context. Resumen Partiendo de una investigación efectuada en 1993 sobre unos sesenta ex-pacientes psiquiátricos de Nueva Brunswick que frecuentan actualmente la red de ayuda mutua de esta provincia, este articulo pone en evidencia algunas de las disyuntivas a las cuales se ven confrontadas las personas " trans-institucionalizadas ". Resaltan varias diferencias a nivel de la utilización de servicios y del grado de satisfacción, particularmente según la pertenencia sexual y el idioma. Además, esta investigación demuestra que la red sobre la cual se apoyan los ex-pacientes psiquiátricos francófonos interrogados, es mucho más social ( familia, grupo de ayuda mutua) mientras que para la población anglófona, el aparato institucional (psiquiatras, instituciones y clínicas) juega un rol determinante. Esto sugiere varias preguntas, tanto a nivel de las políticas sociales como de las prácticas de intervención, particularmente en un contexto minoritario.

French among Health Care Workers in Canada Outside Quebec, 2021 (Infographic) - Statistics Canada (2025)

French among healthcare workers in Canada outside Quebec, 2001 to 2016 [infographic] - Statistics Canada (2021)

Table : 15-10-0041-01 Frequency of health care or services obtained in the minority official language, by age group and gender, for adults in the official language minority population - Statistics Canada (Gouvernement du Canada, 2025)
Health services or care in the minority official language by age group and gender, Canada, among adults in the minority official language population who considered it important to obtain health services or care in the minority official language, 2022. Possibility to conduct more specific searches for Quebec, Canada outside Quebec, certain provinces, or certain regions.

Le français chez les travailleurs de la santé au Canada hors Québec, 2001 à 2016 [infographie] - Statistique Canada (2021)

Le français chez les travailleurs et travailleuses de la santé au Canada hors Québec, 2021 (infographie) - Statistique Canada (2025)

Mortality in Francophone minority in Canada - A 16-year follow-up study. Mortality by socioeconomic status among canadian Francophones and Anglophones living outside Québec - Sucha, E.; SIlva, E.; Batista, Ricardo; Bouchard, Louise (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, University of Ottawa, 2014)

Mortalité dans la minorité francophone au Canada - Une étude de suivi sur 16 ans. La mortalité selon la situation socioéconomique chez les francophones et les anglophones du Canada vivant à l'extérieur du Québec - Sucha, Ewa; Silva, Erika; Batista, Ricardo; Bouchard, Louise (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, Université d'Ottawa, 2014)

La satisfaction des patients francophones de l’Est de l’Ontario traités en réadaptation à domicile - Tardif, Charles; Dallaire, Christine (Francophonies d’Amérique, 2010)
L’accès à des services de santé en français est aujourd’hui une des revendications importantes des porte-drapeaux francophones non seulement pour assurer la santé individuelle des francophones mais aussi pour favoriser la vitalité des communautés. Cependant, certains des francophones qui font appel aux soins ou à l’appui des professionnels de la santé demandent des services en français, alors que d’autres sont satisfaits de recevoir des services en anglais. Cette étude s’inspire de l’analyse des discours développée par Michel Foucault pour examiner les discours que reproduisent les francophones qui reçoivent des soins de réadaptation à domicile, en français et/ou en anglais. Des entrevues semi-dirigées ont été effectuées avec 12 patients francophones dans l’Est de l’Ontario. Les participants de l’étude sont de façon générale satisfaits des soins reçus, mais la langue des services ne répond pas nécessairement à leurs attentes. Ce sont évidemment ceux qui ne peuvent s’exprimer en anglais, d’une part, et ceux qui s’affichent fièrement comme francophones, d’autre part, qui préfèrent recevoir des soins en français. Toutefois, ce ne sont pas que les caractéristiques linguistiques et identitaires des patients qui influencent les critères qu’ils jugent prioritaires pour évaluer les soins reçus. En effet, leur façon de concevoir leur rapport vis-à-vis le professionnel de la santé joue aussi sur l’importance qu’ils accordent à la langue des soins.

Comparing mental health of Francophone populations in Canada, France, and Belgium: 12-month prevalence rates of common mental disorders (part 1) - Tempier, Raymond; Vasiliadis, Helen-Maria; Gilbert, Fabien; Demyttenaere, Koen; Bruffaerts, Ronny; Bonnewyn, Anke; Lépine, Jean-Pierre; Gasquet, Isabelle; Mosier, Karen; Lesage, Alain; Puchala, Chassidy; Lepnurm, Marje; et al. (The Canadian Journal of Psychiatry, 2010)
Objective: To compare the 12-month prevalence of common mental disorders among francophones in Canada, France, and Belgium. This is the first article in a 2-part series comparing mental disorders and service use prevalence of French-speaking populations. Methods: This is a secondary analysis of data from the Canadian Community Health Survey: Mental Health and Well-Being (CCHS 1.2) in 2002 and the European Study of Epidemiology of Mental Disorders-Mental Health Disability (ESEMeD) from 2001 to 2003, where comparable questionnaires were administered to representative samples of adults in Canada, France, and Belgium. In Canada, francophone respondents living in Quebec (n = 7571) and outside Quebec (n = 500) completed the French version of the CCHS 1.2 questionnaire. Francophone respondents in Belgium (n = 389) and in France (n = 1436) completed the French version of the ESEMeD population survey questionnaire. Major depressive episodes (MDEs), specific anxiety disorders (ADs), and alcohol abuse and (or) dependence disorders' rates were assessed. Results: The overall prevalence rate for the presence of any MDE, AD, or alcohol abuse and (or) dependence was similar in all francophone populations studied in Canada and Europe and averaged 8.5%. Conclusions: Mental disorders were equally distributed in all francophone populations studied. Cross-national comparisons continue to be instrumental in providing information useful for the creation of appropriate policies and programs for specific subsets of populations.

Comparing mental health of Francophones in Canada, France, and Belgium: 12-month and lifetime rates of mental health service use (part 2) - Tempier, Raymond; Vasiliadis, Helen-Maria; Gilbert, Fabien; Demyttenaere, Koen; Bruffaerts, Ronny; Lépine, Jean-Pierre; Gasquet, Isabelle; Lepnurm, Marje; Lesage, Alain; Puchala, Chassidy; Mosier, Karen; Kovess-Masféty, Viviane (The Canadian Journal of Psychiatry, 2010)
Objectives: To compare 12-month and lifetime service use for common mental disorders in 4 francophone subsamples using data from national mental health surveys in Canada, Quebec, France, and Belgium. This is the second article in a 2-part series comparing mental disorders and service use prevalence of French-speaking populations. Methods: Comparable World Mental Health-Composite International Diagnostic Interviews (WMH-CIDI) were administered to representative samples of adults (aged 18 years and older) in Canada during 2002 and in France and Belgium from 2001 to 2003. Two groups of francophone adults in Canada, in Quebec (n = 7571) and outside Quebec (n = 500), and respondents in Belgium (n = 389) and France (n = 1436) completed the French version of the population survey. Prevalence rates of common mental health service use were examined for major depressive episodes and specific anxiety disorders (that is, agoraphobia, social phobia, and panic disorder). Results: Overall, most francophones with mental disorders do not seek treatment. Canadians consulted more mental health professionals than their European counterparts, with the exception of psychiatrists. Conclusions: Patterns of service use are similar among francophone populations. Variations that exist may be accounted for by differences in health care resources, health care systems, and health insurance coverage.

Access to psychiatrists by French-speaking patients in Ontario hospitals: 2005 to 2013 - Tempier, TempierRaymond; Bouattane, El Mostafa; Hirdes, John P. (Healthcare Management Forum, 2015)
There has been a limited amount of research suggesting that cultural and linguistic variables may affect access to health services, but no study has examined the access of French-speaking Canadians to psychiatrists. The present study used data from the Ontario Mental Health Reporting System to examine patterns of daily contact with psychiatrists in the first 3 days of admission to mental health facilities in Ontario. The results showed that after controlling for a broad range of covariates, French-speaking Ontarians were about one-third as likely to have daily contact with psychiatrists in that time period compared to English-speaking patients. These results were not explained by regional differences. Instead, they point to the possibility that language poses an important barrier to specific and highly specialized mental health services in this province.

Joint Position Statement on the Active Offer of French Language Health Services in Ontario - The Regroupement des Entités de planification des services; de santé en français de l’Ontario; and; the Alliance des Réseaux ontariens de santé en français (2015)

Des services de santé dans ma langue, un “horizon d’attente” : Programme de santé mentale de Montfort et parcours psychiatriques. - Thifault, Marie-Claude (Le moment Monfort dans la francophonie canadienne, 2024)

Dérives : une histoire sensible des parcours psychiatriques en Ontario français - Thifault, Marie-Claude; LeBel, Marie (Les Presses de l'Université d'Ottawa, 2021)

Rethinking the way we measure access to language-concordant health services for minority language populations: a secondary analysis of publicly available physician and population data in Ontario, Canada - Timony, Patrick E.; Belanger, Christopher; Bélizaire, Arlynn; Desilets, Antoine; Gauthier, Alain; Karunananthan, Sathya; Muray, Mwali-Nachishali; Peixoto, Cayden; Fitzsimon, Jonathan Peter; Godfrey, Leanda; Bjerre, Lise M. (BMJ Open, 2025)
Abstract Objective Providing care in a patient’s preferred language improves health outcomes and patient satisfaction. In Ontario, access to French-speaking physicians (FSPs) is estimated using FSP-to-Francophone population ratios and compared with total physician-to-total population ratios. This approach fails to consider the fact that FSPs also serve non-Francophone patients and that Francophones must compete with the entire population to access FSPs. As a result, this approach inaccurately suggests that Francophones have better access to language-concordant care than Anglophones/Allophones. We propose a novel approach to address this issue, enabling unbiased comparisons of access to language-concordant care across linguistic groups. Design This secondary analysis of publicly available data containing linguistic variables for the Ontario population (Statistics Canada, 2021 Census) and for family physicians (FPs) (College of Physicians and Surgeons of Ontario, January 2024) calculated competition-adjusted ratios and probabilities of accessing language-concordant care. Setting Ontario, Canada. Participants Census and publicly available data on FPs (ie, those providing comprehensive family medicine care to the community) and the Ontario population were obtained. Results Province-wide, the crude ratio of FSPs per 1000 Francophones was 3.46. After adjusting for competition, the ratio of FSP per 1000 population was 0.12, compared with a general physicians-per-1000 population ratio of 1.05. Anglophones/Allophones attached to a FP have a 100% probability of receiving care in English compared with an 11.4% probability for Francophones to receive care from a FSP. Expressed otherwise, Anglophones/Allophones are 8.8 times more likely to receive language-concordant care (ie, care in English) than Francophones. Conclusions Although crude physician-to-population ratios overestimate Francophones’ access to FSPs, competition-adjusted ratios and probabilities demonstrate that they are much less likely to access language-concordant care than Anglophones/Allophones. This novel approach has equity implications for health human resources planning and can be applied to other linguistic minority groups and healthcare providers.

Workload of French-speaking family physicians in Francophone rural and Northern communities in Ontario - Timony, Patrick E.; Gauthier, Alain P.; Sanou, Boroma; Wenghofer, Elizabeth. F. (Canadian Journal of Rural Medicine, 2018)
Introduction: Previous studies have shown that French-speaking family physicians (FSPs) in Ontario are less numerous in areas with high proportions of francophones. The purpose of the current study was to assess whether the degree of concordance between physicians' language of competence and the linguistic profile of the community in which they practise is associated with workload and to explore variations in this relation in rural and northern regions of the province. Methods: This was a secondary analysis of the 2013 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey. We analyzed the primary practice location and language of competence of family physicians/general practitioners. We compared the practice characteristics of FSPs and non-French-speaking physicians (NFSPs) by the proportion of the francophone population, geographic location (north vs. south) and community size (urban vs. rural). Results: Data for 10 548 family physician/general practitioners were analyzed. In areas densely populated by francophones, FSPs worked more hours per week on average and had a greater mean number of patient visits than NFSPs. Non-French-speaking physicians working in areas densely populated by francophones had fewer patient visits per hour on average than FSPs. In most cases, the results were particularly accentuated in rural and northern communities. Conclusion: Our findings suggest that, compared to NFSPs, the demands placed on FSPs are disproportionately greater in communities where the need for French-language health care services is greatest and the supply of FSPs is the smallest. Our results underline the importance of properly preparing family physicians to work in areas densely populated by francophones.

Barriers to offering French language physician services in rural and Northern Ontario - Timony, Patrick E.; Gauthier, Alain P.; Serresse, Suzanne; Goodale, Natalie; Prpic, Jason (Rural and Remote Health, 2016)
Introduction: Rural and Northern Ontario francophones face many health-related challenges including poor health status, a poor supply of French-speaking physicians, and the potential for an inability or reduced ability to effectively communicate with anglophone healthcare providers. As such, it can reasonably be expected that rural and Northern Ontario francophones experience barriers when receiving care. However, the experience of physicians working in areas densely populated by francophones is largely unexplored. This paper identifies barriers experienced by French-speaking and Non-French-speaking rural and Northern Ontario physicians when serving francophone patients. Methods: A series of key informant interviews were conducted with 18 family physicians practicing in rural and urban francophone communities of Northeastern Ontario. Interviews were analyzed using a thematic analysis process. Results: Five categories of barrier were identified: (1) language discordance, (2) characteristics of francophone patients, (3) dominance of English in the medical profession, (4) lack of French-speaking medical personnel, and (5) physicians’ linguistic (in)sensitivity. Some barriers identified were unique to Non-French-speaking physicians (eg language discordance, use of interpreters, feelings of inadequacy), some were unique to French-speaking physicians (eg limited French education and resources), and some were common to both groups (eg lack of French-speaking colleagues/staff, added time commitments, and the particularities of Franco-Ontarian preferences and culture). Conclusions: Healthcare providers and decision makers may take interest in these results. Although physicians were the focus of the present article, the barriers expressed are likely experienced by other healthcare providers, and thus the lessons learned from this article extend beyond the physician workforce. Efforts must be made to offer educational opportunities for physicians and other healthcare providers working in areas densely populated by francophones; these include linguistic and cultural sensitivity training, in addition to teaching strategies for the practice of ‘active offer’ of French-language services. In sum, the present study outlines the importance of linguistic concordant communication in healthcare delivery, and describes some of the challenges faced when providing French-language services in rural and Northern Ontario. Key words: Canada, doctor–patient communication, French-language services, key informant interviews, language concordance, language discordance, Northern Ontario, Ontario francophones, physicians.

The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services

Promising quantities, disappointing distribution. Investigating the presence of French-speaking physicians in Ontario’s rural francophone communities - Timony, Patrick; Gauthier, Alain; Hogenbirk, John. C.; Wenghofer, Elizabeth (Rural and Remote Health, 2013)
Introduction: Previous studies have suggested that there may be a lack of French language healthcare services in the province of Ontario. The purpose of this study was to determine if physicians in Ontario who expressed a proficiency in providing services in the French language are located in 'Francophone communities'. Method: Responses from 10 968 Ontario-based family physicians (FPs) certified by the College of Family Physicians of Canada and uncertified general practitioners (GPs) who responded to the 2007 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey were analysed and compared to the 2006 census of the population of Ontario. Main outcome measures were the number of FP/GPs categorized by their language of competency to conduct medical practice and the number of people categorized by their first official language spoken. The physician-to-population ratio was then compared for different groups of communities in Ontario categorized by the degree of francophonie of the community: strong French communities, with a Francophone population ≥25%; moderate French communities, with a Francophone population of 10-24%; and weak/no French communities, with a Francophone population <10%. Results: There are 5.6 French speaking FP/GPs for every 1000 Francophones in communities with a French population less than 10%. This ratio is considerably greater than what was found in moderate French communities (3.4 FP/GPs) and strong French (1.3 FP/GPs). Overall the lowest ratios were found in rural strong French communities both in southern and northern Ontario (0.8 FP/GPs and 0.9 FP/GPs respectively). The ratio for all of Ontario was 0.7-1.3. Conclusions: As the number of Francophones increases in a community, the availability of French-speaking FP/GPs actually decreases, particularly in rural northern Ontario. Furthermore, there is a paradoxical relationship between the potentially high number of FP/GPs in the province with French-language capabilities and the perceived deficiencies in the availability of French language medical services. Key words: family physician, Francophone community, general practitioners, health and human resources, language, physician-patient ratios, urban. Introduction

The impact of linguistic concordance and the active offer of French language services on patient satisfaction - Timony, Patrick; Gauthier, Alain; Wenghofer, Elizabeth; Hien, Amelie (Diversity of Research in Health Journal, 2022)
Communication is essential to providing quality primary care. Linguistic concordance between patients and physicians has been linked to improved health outcomes and greater patient satisfaction. Although Canadian Francophones often struggle to access linguistics concordant health services, the concept of the active offer of French Language Services (FLS) has emerged as a means of ensuring the availability of such services and improving the francophone patient experience. However, the impact of language concordance and the active offer of FLS on patient satisfaction among Ontario Francophones remain largely unknown. Patient satisfaction surveys were collected as part of a continuing education program targeted at family physicians in Northeastern Ontario. Participating physicians distributed patient surveys consisting of select patient satisfaction questions from the Physicians Achievement Review (PAR) and select questions from the Active Offer of French Language Services in Minority Context Measure. Valid surveys were received from 235 patients. Just under half of these (44%) identified as Francophones, 62.6% had a French-speaking family physician; however, only 17.2% reported regularly speaking in French with their family physician. As hypothesized, there was a consistent tendency for Francophones who experience stronger linguistic concordance with their family physician to report higher satisfaction scores. Francophones who regularly speak French with their family physicians were more satisfied ( = 4.63) than those who rarely/never speak French ( = 4.29, F(1; 83) = 4.852; p < 0.05). There was also a statistically significant interaction between the patients' language of preference and the service language. Francophones who prefer French and regularly speak it with their family physician (linguistic concordance; adj= 4.82) were significantly more satisfied than those who prefer French yet rarely/never speak it (linguistic discordance; adj= 4.06, F(1; 75) = 11.950; p < 0.001). Furthermore, a positive correlation between patient satisfaction and the active offer was observed in Francophones (r = 0.49, p<0.001). The present findings provide evidence of the impact of linguistically adapted health care services on the satisfaction of Ontario Francophones and suggest that patient satisfaction may be improved through the active offer of FLS. A larger and more diverse sample is required to confirm these findings.

Adopting a lay navigator training programme in primary care - Toal-Sullivan, Darene; Lemonde, Manon; Gauthier, Alain P.; Dahrouge, Simone (Health Education Journal, 2021)
Introduction: There is growing interest in the role and use of patient navigators within the health care system. Currently, qualifications and training expectations documented in the literature vary tremendously depending on context and patient population. This paper details the theoretical and pedagogical principles used to develop, implement and evaluate a training programme for lay patient navigators working in a primary care setting. Methods: The planning process involved (a) conducting an educational needs assessment, (b) identifying the theory underpinning the curriculum, (c) developing learning objectives and teaching strategies, (d) formulating evaluation methods, (e) implementing the programme and (f) refining the curriculum based on evaluation feedback and lessons learned. The training programme was first implemented in May 2017 and has evolved over the past 3 years based on our observations and feedback from the programme participants. Results: The training programme involves a total of 25 hours of online and face-to-face education sessions, and ongoing community mentorship from experienced navigators. All training components are rooted in theoretical principles and proven pedagogical approaches. The knowledge, skills and abilities acquired are also tied to core competencies of the role of lay patient navigator. Conclusion: The development of this lay navigator training programme was carefully designed with evidence-based competencies and practical realities to ensure rigour in preparing and supporting navigators’ work in primary care settings.

La santé et les minorités linguistiques : l’approche canadienne au regard de cas internationaux - Traisnel, Christophe; Forgues, Éric (Francophonies d'Amérique, 2009)
Dans notre article, nous présentons une analyse comparative de l’approche canadienne de l’enjeu de la santé pour les communautés francophones en situation minoritaire (CFSM). Nous montrons que l’État canadien a favorisé une démarche de concertation avec les acteurs communautaires. Notre analyse comparative nous a permis de dégager une typologie des politiques linguistiques en matière de santé destinées aux CFSM. Cette typologie permet de situer l’expérience canadienne par rapport à d’autres expériences, parfois proches, mais présentant des perspectives différentes, comme le montrent les cas finlandais, belge et états-unien. La « voie » canadienne paraît originale dans la mesure où elle semble se situer entre un modèle communautaire, à l’instar des pays européens, et un modèle individualisé, à l’instar de ce qui se fait aux États-Unis.

La réadaptation : son visage français en Ontario [numéro thématique] - Tremblay, Louis E. (Reflets, 2002)

Improving access to health services in French: The power of networking and knowledge mobilization, a proven Canadian Model - Tremblay, Michel; Leis, Anne (Linguistic Minorities and Society, 2021)
Language barriers have a detrimental impact on access to health services and compromise patients’ safety. The purpose of this article is to describe and evaluate how the Société Santé en français (SSF) and the 16 French Language Health (FLH) networks used networking and knowledge mobilization for improving access to health services in French for Francophone and Acadian minority communities (FAMC). Method: Data was extracted from the 2013-2018 program’s reports and evaluation. Results confirmed that networking effectively mobilized key partners for better access to health services in French regardless of location. This access increased incrementally as a function of the customized level of support provided to the system by the SSF and the FLH networks and, to a lesser extent, when FAMC represented over 3.5% of the total population in the region, province or territory. Networking and knowledge mobilization contribute to augmenting access to safe, quality health services in French for FAMC. Keywords: access, partnership and networking, active offer, language barriers, knowledge mobilization

Étude sur les services de santé linguistiquement et culturellement adaptés : portrait pancanadien - Tremblay, Suzanne (Société Santé et Mieux-être en français du Nouveau-Brunswick, Société Santé en français et Santé Canada, 2012)

Pour des services de santé culturellement et linguistiquement adaptés - Tremblay, Suzanne (Société Santé en français et Société Santé et Mieux-être en français du Nouveau-Brunswick, 2011)
Ce document fait rapport des études : Les normes de compétences culturelles et linguistiques en santé : étude exploratoire sur les normes américaines et Étude sur les services de santé linguistiquement et culturellement adaptés : portrait pancanadien.

Study on linguistically and culturally adapted healths services: A pan-Canadian portrait - Tremblay, Suzanne (Société Santé et Mieux-être en français du Nouveau-Brunswick, Société Santé en français & Health Canada, 2012)

L’infirmière psychiatrique, leader de l’équipe multidisciplinaire : étude de cas, Hôpital Montfort, 1976-2002 - Valentina Moya, Silvia. Maria (L’infirmière psychiatrique, leader de l’équipe multidisciplinaire : étude de cas, Hôpital Montfort, 2018)
Cet article a pour but de présenter l’espace relationnel de l’infirmière psychiatrique, dans un contexte de prestation de soins en français à Ottawa, pendant la période de désinstitutionnalisation psychiatrique. L’étude de cas d’une patiente francophone suivie pendant 26 ans à la clinique externe de l’Hôpital Montfort a été choisie comme échantillon. Durant son parcours de vie psychiatrique, 63 % des contacts de cette patiente ont été avec l’infirmière, 27 % avec les psychiatres, 5 % avec les ergothérapeutes, 4 % avec les travailleurs sociaux et 1 % avec les psychologues. Parmi les différentes tâches documentées par les infirmières, on retrouve six différents types d’intervention. Le dossier étudié révèle donc que l’infirmière occupe un espace relationnel plus important que les autres professionnels de l’équipe multidisciplinaire. Mots-clés : infirmière, santé mentale, désinstitutionnalisation psychiatrique, équipe multidisciplinaire, parcours de vie

Pratique # 25 : Accès éQUITÉ : Simplifier l’accès aux services de santé en français (Société Santé en français) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)

Pratiques novatrices en santé mentale pour les populations de langue officielle minoritaire à Terre-Neuve-et-Labrador et dans les Territoires du Nord-Ouest - van Kemenade, Solange; Bouchard, Louise; Savard, Jacinthe; Savard, Sébastien; Oukouomi, G.; Michel, J. N. (Université d'Ottawa, Chaire de recherche de l’Université d’Ottawa et de l’Institut du Savoir Montfort sur la santé des francophones de l’Ontario et Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2021)

Enjeux des services sociaux et de santé en contexte bilingue ou multilingue national. Revue de littérature - van Kemenade, Solange; Forest, Mariève (Secrétariat national du Consortium national de formation en santé, 2015)

Services de santé mentale et de dépendances à Terre-Neuve-et-Labrador. Les besoins des francophones et des Acadiens dans cinq communautés de la province - van Kemenade, Solange; Forest, Mariève (Sociopol, 2019)

Services de santé mentale et de dépendances à Terre-Neuve-et-Labrador. Les besoins des francophones et des Acadiens dans cinq communautés de la province (Sommaire) - van Kemenade, Solange; Forest, Mariève (Sociopol, 2019)

The Needs of Francophones and Acadians in Five Communities in the Province (Summary Report). - van Kemenade, Solange; Forest, Mariève (Sociopol, 2019)

Pratique # 23 : Navigateur francophone du système de santé (Terre-Neuve-et-Labrador) - van Kemenade, Solange; Michel, Jean Nephetaly; Savard, Jacinthe; Benoît, Josée (2021)

Les expériences de patients francophones qui se présentent fréquemment à l'urgence pour des raison de santé mentale - Vandyk, Amanda; Lightfoot, Sophie; Levesque, Kristine; Domecq, Marie-Cécile.; Jacob, Jean Daniel (Recherche en soins infirmiers, 2022)
Introduction: Language and communication are pivotal to the safe care and management of people with mental health disorders, particularly when these patients are linguistic minorities. Objectives/method: To explore these experiences within linguistic minority populations by completing a literature review and qualitative interviews. Interviews were conducted in Ottawa, Canada, with francophone patients. The studies included in the review represented the international literature on linguistic minorities in general. Results: Overall, the experiences described in the published articles were similar to the participants' own experiences, suggesting that barriers to care exist even in settings mandated to provide services in both official languages. Discussion/conclusion: There are many barriers to the provision of mental health care services, regardless of the dominant language. However, we identified an internalized sense of responsibility felt by linguistic minority patients, who feel compelled to compensate for or fill in the language gaps of providers. Keywords: health services accessibility; language; mental health; qualitative research; rapid review.

Comparing the rates of mental disorders among different linguistic groups in a representative Canadian population - Vasiliadis, Helen-Maria; Lepnurm, Marje; Tempier, Raymond; Kovess-Masfety, Viviane (Social psychiatry and psychiatric epidemiology, 2012)
Purpose We aimed to determine whether linguistic group influences reported prevalence rates for a number of common mental disorders. Methods Secondary data analyses of the Canadian Community Health Survey cycle 1.2 (CCHS 1.2) were carried out on representative bilingual French and English, monolingual French and English and other language groups in Canada. Past year prevalence of major depression, anxiety disorders (agoraphobia, social phobia, panic disorder) and alcohol abuse/dependence were ascertained using versions of the World Mental Health Composite International Diagnostic Interview (WMH-CIDI) questionnaire. Multivariate data analyses were used to model past year presence of a mental disorder as a function of linguistic group, defined as languages can converse in, and adjusting for socioeconomic, demographic and cultural factors. Results Overall, past year rates for the presence of a common mental disorder were 10.7% (9.7–11.7%) for the bilingual English; 9.0% (8.1–9.9%) for the bilingual French; 10.2% (9.8–10.6) for the monolingual English; 8.5% (7.7–9.3%) for the monolingual French; and 8.3% (6.1–10.4%) for the other language group. After adjusting for a number of socio-demographic, economic and cultural factors, the multivariate analyses showed that the linguistic groups were equally likely to report the presence of a past year common mental disorder. This was also true for comparisons between the bilingual participants responding in French and English. Conclusions The differences observed in the reported crude rates for the presence of mental disorders across the different linguistic groups in Canada were explained by socio-demographic, economic, and factors such as immigration, spoke a third language and province of residence, and not explained by language of interview.

Active offer, bilingualism, and organizational culture - Vézina, Sylvain (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Bilan de santé : une analyse descriptive de l’état de la recherche sur la santé et les communautés francophones en situation minoritaire - Vézina, Sylvain (Minorités linguistiques et société, 2015)
Ce texte présente un bilan des activités de recherche soutenues par le Consortium national de formation en santé (CNFS), selon l’orientation des connaissances produites et des pistes d’action qui en résultent. Nous y abordons la question de la participation du milieu à la planification de la recherche, sa réalisation et la mise en pratique des résultats. L’étude a été réalisée selon deux méthodes : une analyse du contenu des documents produits et une série d’entrevues avec des chercheurs et des représentants du milieu. L’objectif consiste à fournir quelques indications sur les atouts et les défis du rapprochement entre chercheurs et communautés dans la perspective de la recherche participative. Mots-clés : production en recherche, santé des minorités, minorité francophone du Canada, mise en pratique des connaissances, recherche participative, rapprochement chercheurs-communautés

Gouvernance, santé et minorités francophones: stratégies et nouvelles pratiques de gestion au Canada - Vézina, Sylvain (Les Éditions de la Francophonie, 2007)

Offre active, bilinguisme et culture organisationnelle - Vézina, Sylvain (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Dans ce texte, l’auteur aborde l’offre active sous l’angle de la culture organisationnelle. Il y présente les résultats d’une enquête menée auprès de professionnels de la santé oeuvrant au sein d’établissements hospitaliers anglophones et francophones du Nouveau-Brunswick. La culture organisationnelle y est traitée, à la lumière de la sociologie des organisations, non pas comme une fatalité, mais comme un construit, au même titre que les règles du jeu organisationnel (rapports hiérarchiques, définition des tâches, conventions collectives…). Cette recherche fait ressortir la prédominance d’une culture organisationnelle centrée sur le bilinguisme donnant lieu à la persistance d’une confusion entre les notions d’offre active et de bilinguisme. Or, du point de vue de l’auteur, si le bilinguisme est essentiel à l’offre de services de qualité dans les deux langues officielles, il peut être contre-productif quand il s’agit d’introduire une culture favorable à l’offre active. Il affirme, en effet, que l’accent mis sur le bilinguisme est souvent perçu par les personnes unilingues comme une menace à l’équilibre des forces au sein du système entraînant, le plus souvent, de la résistance envers toute mesure favorable à l’offre active. C’est pourquoi il en vient à suggérer la valorisation d’une culture d’offre active autour d’objectifs de sécurité et de qualité des soins dans les langues officielles. Mots-clés : professionnels de la santé, établissements hospitaliers, culture organisationnelle, bilinguisme, offre active, Nouveau-Brunswick

Vers une démarche concertée pour le renforcement de la recherche sur les langues officielles dans le secteur de la santé : bilan et pistes d’action - Vézina, Sylvain; Doiron Robichaud, Johannie (Bureau d’appui aux communautés de langue officielle de Santé Canada, 2011)

Active offer, actors, and the health and social service system: An analytical framework - Vézina, Sylvain; Savard, Sébastien (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Offre active, acteurs et système de santé et de services sociaux : un cadre d’analyse - Vézina, Sylvain; Savard, Sébastien (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé Ce chapitre présente un cadre théorique inspiré de l’analyse stratégique aussi nommée sociologie des organisations. Par cette approche, le chercheur tente de découvrir les objectifs et stratégies des acteurs en présence pour mieux saisir la dynamique du système d’action tout en prenant en compte les contraintes issues de la structure formelle. On y traite des concepts de système d’action, de pouvoir, de règle du jeu, de changement, de stratégie, d’acteur, d’enjeu, d’organisation et d’environnement, lesquels rendent compte de la complexité des défis entourant la pratique de l’offre active en santé et services sociaux. Une des contributions majeures de cette approche est qu’elle fournit un cadre d’analyse permettant de mieux saisir la relation entre l’acteur et le système, deux composantes essentielles tant à la compréhension de notre objet qu’à l’identification de stratégies d’action par les acteurs du milieu. Mots-clés : offre active, services sociaux et de santé, système d’action, pouvoir, zone d’incertitude, analyse stratégique, sociologie des organisations, changement, stratégie, acteur, enjeu, organisation, environnement.

Création d'une grille d'observation pour simulations sur l'offre active de services de santé en français - Vincent, Coralie; Bodnaruc, Alexandra Maria; Kengneson, Cris-Carelle; Savard, Jacinthe; Giroux, Isabelle (Reflets, 2021)
Au Canada, il fut démontré que les communautés francophones vivant en situation linguistique minoritaire éprouvent des difficultés à se prévaloir de services sociaux et de santé dans leur langue de préférence, ce qui peut négativement affecter la qualité et la sécurité des services. L’offre active est une pratique visant à contrer les effets de la minorisation linguistique en invitant, de manière proactive et dès le premier contact, les bénéficiaires à s’exprimer dans la langue officielle de leur choix. Il n’existe actuellement aucun outil validé permettant l’évaluation de cette compétence auprès des futurs professionnels des domaines de la santé et des services sociaux. Cet article présente les étapes de création et de validation de Grille d’observation des indicateurs de compétence la en offre active de services en français, laquelle vise à soutenir les programmes de formation dans l’enseignement et l’évaluation de cette compétence au moyen de simulations. Mots-clés : minorités linguistiques, offre active de services en français, langue et services, qualité des soins, formation professionnelle en santé et service social, grille d’observation, validation

Validation de l'équité d'accès des CLOSM aux professionnels de la santé dans les régions sociosanitaires du Canada - Warnke, Jan; Bouchard, Louise (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectifs Notre recherche utilise l’indicateur synthétique régional (IPSLOM) pour mesurer la capacité du système de santé à fournir un accès équitable aux professionnels de la santé pour les deux millions de personnes qui constituent des Communautés de langue officielle en situation minoritaire (CLOSM) dans 104 régions sociosanitaires du Canada. Méthode L’indicateur synthétique l’IPSLOM compare l’accès potentiel aux professionnels de la santé de la population de langue officielle minoritaire à l’accès potentiel de la population de langue officielle majoritaire. L’IPSLOM utilise 22 professions de santé, soit 79 % des effectifs de santé au Canada (Statistique Canada, 2006) qui ont à communiquer avec leur clientèle dans un but thérapeutique ou diagnostique. Résultats L’indice comparatif de l’IPSLOM a révélé que la population CLOSM de 10 des 13 provinces/territoires du Canada est désavantagée par rapport à la majorité linguistique quant à l’accès potentiel aux professionnels de la santé capable de les desservir en langue minoritaire. La population CLOSM est désavantagée en Ontario dans 13 régions sociosanitaires sur 14, au Québec dans 17 régions sur 18 et au Nouveau-Brunswick dans 3 des 7 régions sociosanitaires. Conclusion L’indicateur synthétique IPSLOM a permis d’identifier des inégalités d’accès aux professionnels de la santé entre la minorité de langue officielle et la majorité linguistique, à travers les régions sociosanitaires du système de santé au Canada. Des analyses plus fines de l’IPSLOM par professions spécifiques permettraient d’approfondir notre connaissance des inégalités de santé qui affectent les communautés de langue officielle en situation minoritaire.

Do nurses use discourse markers differently when using their second language as opposed to their first while interviewing patients? - Yeji, Han; Segalowitz, Norman; Khalil, Laura; Kehayia, Eva; Turner, Carolyn; Gatbonton, Elisabeth (The Canadian Modern Language Review, 2020)
Les auteurs se demandent si l’utilisation de marqueurs discursifs change, dans les interactions des infirmières avec les patients, en fonction de l’usage qu’elles font de leur langue maternelle (L1) ou de leur langue seconde (L2). Les marqueurs sont analysés à titre de marqueurs de maintien du tour de parole, indiquant la « prise en compte » et de marqueurs de transition dans le discours, indiquant un changement de sujet ou de locuteur dans la conversation. Ces deux catégories de marqueurs diffèrent sur le plan du degré de gestion du discours et du contrôle interactionnel. Seize infirmières mènent auprès d’un patient de L1 anglaise et d’un patient de L1 française un entretien visant l’évaluation de la douleur, entretien dans lequel les infirmières utilisent leur propre L1 dans un cas et leur propre L2, moins bien maîtrisée, dans l’autre. Les résultats de l’étude ne permettent pas de confirmer la première hypothèse, selon laquelle les infirmières devraient normalement utiliser les marqueurs discursifs plus fréquemment en L1 qu’en L2. Ils confirment toutefois la seconde hypothèse, selon laquelle les infirmières devraient utiliser les marqueurs de changement de sujet moins fréquemment en L2 qu’en L1, comparativement à leur usage (de base) des marqueurs de maintien du tour de parole. Les constatations des auteurs, en particulier l’attestation de la seconde hypothèse, pourraient avoir des répercussions sur le développement de la formation en L2 des professionnels de la santé.

Susciter chez les professionnels une prise de conscience critique des enjeux liés à la littératie en santé pour des francophones en situation de minorité linguistique en Ontario - Zanchetta, Margareth. S.; Maheu, C.; Fontaine, C.; Salvador-Watts, L.; Wong, N. (Maladies chroniques et blessures au Canada, 2014)

Construction of Francophone families’ health literacy in a linguistic minority situation - Zanchetta, Margareth. Santos; Kaszap, Margot; Mohamed, Mohamed; Racine, Louise; Maheu, Christine; Masny, Diana; Cèsar, Ines; Maltais, Claire; Sangwa-Lugoma, G.; Lussier, Nancy; Kinslikh, Diana (Alterstice, 2012)
With the  increase  in  international  mobility,  healthcare  systems  should  no  longer  be  ignoring  language  barriers.  In  addition  to  the  benefit  of  reducing  long‐term  costs,  immigrant‐friendly  organizations  should  be  concerned  with  mitigating  the  way  language  barriers  increase  individuals’  social  vulnerabilities  and  inequities  in  health  care  and  health  status.  This  paper  reports  the  findings  of  a  qualitative,  exploratory  study  of  the  health  literacy  of  28  Francophone  families  living  in  a  linguistic‐minority  situation  in  Canada.  Analysis  of  interviews  revealed  that  participants’  social  vulnerability,  mainly  due  to  their  limited  social  and  informational  networks,  influenced  the  construction  of  family  health  literacy.  Disparities  in  access  to  healthcare  services  could  be  decreased  by  having  health  professionals’  work  in  alliance  with  Francophone  community  groups  and  by  hiring  bilingual  health  professionals.  Linguistic  isolation  and  lack  of  knowledge  about  local  cultural  organizations  among  Francophone immigrants  were  two  important  findings  of  this  study.

Awakening professionals’ critical awareness of health literacy issues within a francophone linguistic-minority population in Ontario - Zanchetta, Margareth Santos; Maheu, Christine; Fontaine, C.; Salvador-Watts, Liana; Wong, N. (Chronic Diseases and Injuries in Canada, 2014)

Validation d’un questionnaire sur l’alphabétisme en santé des francophones en situation linguistique minoritaire - Zanchetta, Margareth; Maheu, Christine; Racine, Louise; Kaszap, Margot; Jbilou, Jalila; Giguère, Samuel; Reece, Daidre-Ann; Thélusma-Rémy, Marlene; Montgomery, Catherine; Xenocostas, Spyridoula; Parada, Henry; Talbot, Yves; et al. (Santé Publique, 2018)